Achtsamkeitstraining als psychotherapeutische Interventionsmethode: Konzeptklärung, klinische Anwendung und aktuelle empirische Befundlage - Berking, Matthias; von Känel, Miriam (Psychotherapie Psychosomatik Medizinische Psychologie, 2007)
With mindfulness-based interventions becoming increasingly popular this review outlines: 1. How mindfulness is defined and conceptualized, 2. How mindfulness is applied in psychotherapy, 3. How effective mindfulness-based interventions are and 4. How the effectiveness of these methods might be explained. Findings show that mindfulness can be seen as a multidimensional concept which is the core or an important component of several psychotherapeutical methods that have been shown to be effective in the treatment of different psychological problems and disorders. With regard to possible mechanisms of change it is argued that enhancing patients' skills to accept and tolerate aversive experiences can be seen as a specific and important effect of these approaches. Future research should try to clarify for whom these skills are particularly important, and how these skills can be taught to patients who are less open for mindfulness-based approaches. © Georg Thieme Verlag KG Stuttgart.
Created from Fastlane, Scopus look-up
Keywords: Effectiveness; Mindfulness; Psychotherapy; Review; Treatment-outcome

Adaptive emotion regulation mediates the relationship between self-compassion and depression in individuals with unipolar depression - Diedrich, Alice; Burger, Julian; Kirchner, Mareike; Berking, Matthias (Psychology and Psychotherapy: Theory, Research and Practice, 2016)
Objectives: To identify the mechanisms involved in the association between self-compassion and depression, we examined whether adaptive emotion regulation would mediate the relationship between self-compassion and depression in individuals with unipolar depression. Furthermore, we explored which specific emotion regulation skills would be most important in this relationship. Design and method: Sixty-nine individuals with unipolar depression were assessed with the Self-Compassion Scale and the Emotion Regulation Skills Questionnaire at baseline and with the Beck Depression Inventory-II 1 week later. Results: The results showed that successful application of emotion regulation skills mediates the association between self-compassion and depression. Among eight specific emotion regulation skills, only the ability to tolerate negative emotions was identified as a significant mediator in the self-compassion-depression relationship. Conclusions: These findings provide preliminary evidence that systematically fostering self-compassion might help depressed individuals cope with their symptoms by enhancing their abilities to tolerate undesired emotions. Practitioner points: Systematically fostering self-compassion through specific compassion-focused interventions might facilitate a reduction in depressive symptoms by improving the person's emotion regulation abilities, especially by improving his or her ability to tolerate negative emotions. Hence, compassion-focused interventions might be particularly promising in depressed patients with a tendency to avoid negative emotions and deficits in tolerating them.
Keywords: Depression; Emotion regulation; Mediator; Self-compassion; Unipolar depression

Additive effects of adjunctive app-based interventions for mental disorders - A systematic review and meta-analysis of randomised controlled trials - Fuhrmann, Lukas; Weisel, Kiona; Harrer, Mathias; Kulke, Jennifer; Baumeister, Harald; Cuijpers, Pim; Ebert, David D.; Berking, Matthias (Internet Interventions, 2024)
Background: It is uncertain whether app-based interventions add value to existing mental health care. Objective: To examine the incremental effects of app-based interventions when used as adjunct to mental health interventions. Methods: We searched PubMed, PsycINFO, Scopus, Web of Science, and Cochrane Library databases on September 15th, 2023, for randomised controlled trials (RCTs) on mental health interventions with an adjunct app-based intervention compared to the same intervention-only arm for adults with mental disorders or respective clinically relevant symptomatology. We conducted meta-analyses on symptoms of different mental disorders at postintervention. PROSPERO, CRD42018098545. Results: We identified 46 RCTs (4869 participants). Thirty-two adjunctive app-based interventions passively or actively monitored symptoms and behaviour, and in 13 interventions, the monitored data were sent to a therapist. We found additive effects on symptoms of depression (g = 0.17; 95 % CI 0.02 to 0.33; k = 7 comparisons), anxiety (g = 0.80; 95 % CI 0.06 to 1.54; k = 3), mania (g = 0.2; 95 % CI 0.02 to 0.38; k = 4), smoking cessation (g = 0.43; 95 % CI 0.29 to 0.58; k = 10), and alcohol use (g = 0.23; 95 % CI 0.08 to 0.39; k = 7). No significant effects were found on symptoms of depression within a bipolar disorder (g = -0.07; 95 % CI -0.37 to 0.23, k = 4) and eating disorders (g = -0.02; 95 % CI -0.44 to 0.4, k = 3). Studies on depression, mania, smoking, and alcohol use had a low heterogeneity between the trials. For other mental disorders, only single studies were identified. Only ten studies had a low risk of bias, and 25 studies reported insufficient statistical power. Discussion: App-based interventions may be used to enhance mental health interventions to further reduce symptoms of depression, anxiety, mania, smoking, and alcohol use. However, the effects were small, except for anxiety, and limited due to study quality. Further high-quality research with larger sample sizes is warranted to better understand how app-based interventions can be most effectively combined with established interventions to improve outcomes.
CRIS-Team Scopus Importer:2024-01-12
Keywords: Adjunct; App-based interventions; Blended; E-mental health; Mental disorder; Meta-analysis; Mobile

Adherence to internet-based mobile-supported stress management: A pooled analysis of individual participant data from three randomized controlled trials - Zarski, Anna-Carlotta; Lehr, Dirk; Berking, Matthias; Riper, Heleen; Cuijpers, Pim; Ebert, David (Journal of Medical Internet Research, 2016)
Background: Nonadherence to treatment is a prevalent issue in Internet interventions. Guidance from health care professionals has been found to increase treatment adherence rates in Internet interventions for a range of physical and mental disorders. Evaluating different guidance formats of varying intensity is important, particularly with respect to improvement of effectiveness and cost-effectiveness. Identifying predictors of nonadherence allows for the opportunity to better adapt Internet interventions to the needs of participants especially at risk for discontinuing treatment. Objective: The goal of this study was to investigate the influence of different guidance formats (content-focused guidance, adherence-focused guidance, and administrative guidance) on adherence and to identify predictors of nonadherence in an Internet-based mobile-supported stress management intervention (ie, GET.ON Stress) for employees. Methods: The data from the groups who received the intervention were pooled from three randomized controlled trials (RCTs) that evaluated the efficacy of the same Internet-based mobile-supported stress management intervention (N=395). The RCTs only differed in terms of the guidance format (content-focused guidance vs waitlist control, adherence-focused guidance vs waitlist control, administrative guidance vs waitlist control). Adherence was defined by the number of completed treatment modules (0-7). An ANOVA was performed to compare the adherence rates from the different guidance formats. Multiple hierarchical linear regression analysis was conducted to evaluate predictors of nonadherence, which included gender, age, education, symptom-related factors, and hope for improvement. Results: In all, 70.5% (93/132) of the content-focused guidance sample, 68.9% (91/132) of the adherence-focused guidance sample, and 42.0% (55/131) of the participants in the administrative guidance sample completed all treatment modules. Guidance had a significant effect on treatment adherence (F=11.64, P<.001; w=.05). Participants in the content-focused guidance (mean 5.70, SD 2.32) and adherence-focused guidance samples (mean 5.58, SD 2.33) completed significantly more modules than participants in the administrative guidance sample (mean 4.36, SD 2.78; t=4.53, P<.001; r=.29). Content-focused guidance was not significantly associated with higher adherence compared to adherence-focused guidance (t=0.42, P=.67; r=.03). The effect size of r=.03 (95% CI-0.09 to 0.15) did not pass the equivalence margin of r=.20 and the upper bound of the 95% CI lay below the predefined margin, indicating equivalence between adherence-focused guidance and content-focused guidance. Beyond the influence of guidance, none of the predictors significantly predicted nonadherence. Conclusions: Guidance has been shown to be an influential factor in promoting adherence to an Internet-based mobile-supported stress management intervention. Adherence-focused guidance, which included email reminders and feedback on demand, was equivalent to content-focused guidance with regular feedback while requiring only approximately a quarter of the coaching resources. This could be a promising discovery in terms of cost-effectiveness. However, even after considering guidance, sociodemographic, and symptom-related characteristics, most interindividual differences in nonadherence remain unexplained.
Keywords: Guidance; Internet intervention; Predictors; Stress management; Treatment adherence; Work-related stress

Advancing psychotherapy and evidence-based psychological interventions - Knappe, Susanne; Ollendick, Thomas; Hermans, Dirk; Riper, Heleen; Colom, Franscesc; Essau, Cecilia; Botella, Christina; Andersson, Gerhard; Berking, Matthias; Carlbring, Per; Lutz, Wolfgang; Banos Rivera, Rosa; et al. (International Journal of Methods in Psychiatric Research, 2014)
Psychological models of mental disorders guide research into psychological and environmental factors that elicit and maintain mental disorders as well as interventions to reduce them. This paper addresses four areas. (1) Psychological models of mental disorders have become increasingly transdiagnostic, focusing on core cognitive endophenotypes of psychopathology from an integrative cognitive psychology perspective rather than offering explanations for unitary mental disorders. It is argued that psychological interventions for mental disorders will increasingly target specific cognitive dysfunctions rather than symptom-based mental disorders as a result. (2) Psychotherapy research still lacks a comprehensive conceptual framework that brings together the wide variety of findings, models and perspectives. Analysing the state-of-the-art in psychotherapy treatment research, “component analyses” aiming at an optimal identification of core ingredients and the mechanisms of change is highlighted as the core need towards improved efficacy and effectiveness of psychotherapy, and improved translation to routine care. (3) In order to provide more effective psychological interventions to children and adolescents, there is a need to develop new and/or improved psychotherapeutic interventions on the basis of developmental psychopathology research taking into account knowledge of mediators and moderators. Developmental neuroscience research might be instrumental to uncover associated aberrant brain processes in children and adolescents with mental health problems and to better examine mechanisms of their correction by means of psychotherapy and psychological interventions. (4) Psychotherapy research needs to broaden in terms of adoption of large-scale public health strategies and treatments that can be applied to more patients in a simpler and cost-effective way. Increased research on efficacy and moderators of Internet-based treatments and e-mental health tools (e.g. to support “real time” clinical decision-making to prevent treatment failure or relapse) might be one promising way forward. Copyright © 2013 John Wiley & Sons, Ltd.
Keywords: cognitive endophenotypes; dimensional approaches; cognitive processing; models for psychopathology; cognitive behavioural therapy; effectiveness; children; adolescents; e-mental health

Affect Regulation Training - Berking, Matthias; Whitley, Brian (Springer, 2014)
Emotion Regulation is currently one of the most popular topics in clinical psychology. Numerous studies demonstrate that deficits in emotion regulation skills are likely to help maintain various forms of psychological disorders. Thus, enhancing emotion regulation has become a major target in psychotherapeutic treatments. For this purpose, a number of therapeutic strategies have been developed and shown to be effective. However, for practitioners it is often difficult to decide which of these strategies they should use or how they can effectively combine empirically-validated strategies. Thus, the authors developed the Affect Regulation Training as a transdiagnostic intervention which systematically integrates strategies from cognitive behavior therapy, mindfulness-based interventions, emotion-focused therapy, and dialectical behavioral therapy. The effectiveness of ART has been demonstrated in several high-quality studies.<br
Keywords: affective regulation; autonomic nervous system; awareness of emotions; brain; coping with stress; effect/consequence of negative emotions; emotion dysregulation; emotion regulation; emotion regulation abilities; emotion regulation skills; emotion regulation techniques; hippocampus; limbic system; mediation; negative emotions; neuroscience; parasympathetic; prefrontal cortex; psychotherapeutic group intervention; relationship between mental health and; emotion regulation; relaxation training; stress management; stress management training; sympathetic; training; program for emotion regulation; transdiagnostic treatment

Affect regulation training reduces symptom severity in depression – A randomized controlled trial - Berking, Matthias; Eichler, Eva; Luhmann, Maike; Diedrich, Alice; Hiller, Wolfgang; Rief, Winfried (PLoS ONE, 2019)
Deficits in general emotion regulation skills have been shown to be associated with various mental disorders. Thus, general affect-regulation training has been proposed as promising transdiagnostic approach to the treatment of psychopathology. In the present study, we aimed to evaluate the efficacy of a general affect-regulation as a stand-alone, group-based treatment for depression. For this purpose, we randomly assigned 218 individuals who met criteria for major depressive disorder (MDD) to the Affect Regulation Training (ART), to a waitlist control condition (WLC), or to a condition controlling for common factors (CFC). The primary outcome was the course of depressive symptom severity as assessed with the Hamilton Rating Scale for Depression and the Beck Depression Inventory. Multi-level analyses indicated that participation in ART was associated with a greater reduction of depressive symptom severity than was participation in WLC (d = 0.56), whereas the slight superiority of ART over CFC (d = 0.25) was not statistically significant. Mediation analyses indicated that changes in emotion regulation skills mediated the differences between ART/CFC and WLC. Thus, the findings provide evidence for enhancing emotion regulation skills as a common mechanism of change in psychological treatments for depression. The study was registered with ClinicalTrials.gov (NCT01330485) and was supported by grants from the German Research Association (DFG; BE 4510/3-1; HI 456/6-2). Future research should compare the (cost-) efficacy of ART with that of disorder-specific interventions.
CRIS-Team Scopus Importer:2019-09-03

A gamified smartphone-based intervention for depression: Randomized Controlled Pilot Trial. - Lukas, Christian; Eskofier, Björn; Berking, Matthias (JMIR Mental Health, 2021)
Background: Available smartphone-based interventions for depression predominantly use evidence-based strategies from cognitive-behavioral therapy (CBT), but patient engagement and reported effect sizes are small. Recently, studies have demonstrated that smartphone-based interventions combining CBT with gamified approach-avoidance bias modification training (AAMT) can foster patient engagement and reduce symptoms of several mental health problems. Objective: Based on these findings, we developed a gamified smartphone-based intervention, mentalis Phoenix (MT-Phoenix), and hypothesized the program would both engage patients and produce preliminary evidence for the reduction of depressive symptoms. Methods: To test this hypothesis, we evaluated MT-Phoenix in a randomized controlled pilot trial including 77 individuals with elevated depression scores (Patient Health Questionnaire-9 scores ≥5). Participants were either instructed to train for 14 days with MT-Phoenix or assigned to a waitlist control condition. Engagement with the intervention was measured by assessing usage data. The primary outcome was reduction in depressive symptom severity at postassessment. Results: Data from this pilot trial shows that participants in the intervention group used the smartphone-based intervention for 46% of all days (6.4/14) and reported a significantly greater reduction of depressive symptoms than did participants in the control condition (F1,74=19.34; P=.001), with a large effect size (d=1.02). Effects were sustained at a 3-month follow-up. Conclusions: A gamified smartphone-based intervention combining CBT with AAMT may foster patient engagement and effectively target depressive symptoms. Future studies should evaluate the effectiveness of this intervention in a phase 3 trial using clinical samples. Moreover, the intervention should be compared to active control conditions.
CRIS-Team Scopus Importer:2021-08-06
Keywords: smartphone technology; depression; cognitive behavioral therapy; approach/avoidance; gamification

A health economic outcome evaluation of an internet-based mobile-supported stress management intervention for employees. - Ebert, David; Kählke, Fanny; Buntrock, Claudia; Berking, Matthias; Smit, Filip; Heber, Elena; Baumeister, Harald; Funk, Burkhardt; Riper, Heleen; Lehr, Dirk (Scandinavian Journal of Work Environment & Health, 2018)
Objective This study aimed to estimate and evaluate the cost-effectiveness and cost-benefit of a guided internet- and mobile-supported occupational stress-management intervention (iSMI) for employees from the employer's perspective alongside a randomized controlled trial. Methods A sample of 264 employees with elevated symptoms of perceived stress (Perceived Stress Scale, PSS-10 ≥22) was randomly assigned either to the iSMI or a waitlist control (WLC) group with unrestricted access to treatment as usual. The iSMI consisted of seven sessions of problem-solving and emotion-regulation techniques and one booster session. Self-report data on symptoms of perceived stress and economic data were assessed at baseline, and at six months following randomization. A cost-benefit analysis (CBA) and a cost-effectiveness analysis (CEA) with symptom-free status as the main outcome from the employer's perspective was carried out. Statistical uncertainty was estimated using bootstrapping (N=5000). Results The CBA yielded a net-benefit of EUR181 [95% confidence interval (CI) -6043-1042] per participant within the first six months following randomization. CEA showed that at a willingness-to-pay ceiling of EUR0, EUR1000, EUR2000 for one additional symptom free employee yielded a 67%, 90%, and 98% probability, respectively, of the intervention being cost-effective compared to the WLC. Conclusion The iSMI was cost-effective when compared to WLC and even lead to cost savings within the first six months after randomization. Offering stress-management interventions can present good value for money in occupational healthcare.

A meta-analysis of cognitive-behavioural therapy for adult depression, alone and in comparison with other treatments - Cuijpers, Pim; Berking, Matthias; Andersson, Gerhard; Quigley, Leanne; Kleiboer, Annet; Dobson, Keith S. (Canadian Journal of Psychiatry-Revue Canadienne De Psychiatrie, 2013)
Objective: No recent meta-analysis has examined the effects of cognitive-behavioural therapy (CBT) for adult depression. We decided to conduct such an updated meta-analysis. Methods: Studies were identified through systematic searches in bibliographical databases (PubMed, PsycINFO, Embase, and the Cochrane library). We included studies examining the effects of CBT, compared with control groups, other psychotherapies, and pharmacotherapy. Results: A total of 115 studies met inclusion criteria. The mean effect size (ES) of 94 comparisons from 75 studies of CBT and control groups was Hedges g = 0.71 (95% CI 0.62 to 0.79), which corresponds with a number needed to treat of 2.6. However, this may be an overestimation of the true ES as we found strong indications for publication bias (ES after adjustment for bias was g = 0.53), and because the ES of higher-quality studies was significantly lower (g = 0.53) than for lower-quality studies (g = 0.90). The difference between high- and low-quality studies remained significant after adjustment for other study characteristics in a multivariate meta-regression analysis. We did not find any indication that CBT was more or less effective than other psychotherapies or pharmacotherapy. Combined treatment was significantly more effective than pharmacotherapy alone (g = 0.49). Conclusions: There is no doubt that CBT is an effective treatment for adult depression, although the effects may have been overestimated until now. CBT is also the most studied psychotherapy for depression, and thus has the greatest weight of evidence. However, other treatments approach its overall efficacy.
Created from Fastlane, Scopus look-up
Keywords: Cognitive-behavioural therapy; Depression; Major depressive disorder; Metaanalysis; Psychotherapy

A mobile application for panic disorder and agoraphobia: Insights from a multi-methods feasibility study - Ebenfeld, Lara; Kleine Stegemann, Stefan; Lehr, Dirk; Ebert, David; Funk, Burkhardt; Riper, Heleen; Berking, Matthias (Internet Interventions, 2020)
Background: Panic disorder with and without agoraphobia (PD) is a common psychological disorder. Internet-based interventions have the potential to offer highly scalable low-threshold evidence-based care to people suffering from PD. GET.ON Panic is a newly developed internet-based intervention addressing symptoms of PD. In order to transfer the training into the daily life of the individuals, we integrated mobile components in the training and created a so-called hybrid online training. The development and beta-testing of such a training requires a novel interdisciplinary approach between IT specialists and psychologists. From this point of view, we would like to share our experiences in this exploratory paper. Methods: This initial feasibility study (N = 10) offers, on the one hand, a brief overview of the interdisciplinary development phase of the mobile application and on the other hand, provides first insights into the usage, usability and acceptance of this mobile application using qualitative interview data as well quantitative measures of 8 completing participants. For these reasons, we used a pre-posttest design without a control group. Furthermore, we present initial clinical outcomes of the intervention on e.g. panic symptom severity, depressive symptoms as well additional anxiety measures. Finally, we end with implications for further research in the relatively new field of mobile mental health. Results: Overall, usability, user satisfaction, motivational value and technology acceptance of the app were perceived as high. The usage of app components was diverse: The use of interoceptive exposure exercises and daily summaries on anxiety and mood was highest while using in-vivo exposure exercises and monitoring panic symptoms was perceived as difficult. Furthermore, participants showed after the training less clinical symptoms as at baseline-assessment. Discussion: The current feasibility study contributes to an in-depth understanding of the potential of mobile technology in e-mental health. Overall, the GET.ON Panic app appears to be an acceptable and motivational part of a CBT-based hybrid online training for PD that has the potential to promote training success. After some suggested adjustments have been made, the efficacy should be investigated in a randomized controlled trial.
CRIS-Team Scopus Importer:2019-12-17
Keywords: Agoraphobia; Cognitive behavior therapy; Feasibility study; M-mental health; Panic disorder; Thematic analyses

An Anger-based Approach-Avoidance Modification Training Targeting Dysfunctional Beliefs in Adults with Elevated Stress – Results from a Randomized Controlled Pilot Study - Keinert, Eva Marie; Schindler-Gmelch, Lena; Eskofier, Björn; Berking, Matthias (International Journal of Cognitive Therapy, 2024)
We examined the feasibility, acceptability, and clinical potential of a smartphone-based Approach-Avoidance Modification Training (AAMT) that required users to deliberately display anger and positive emotions (AAMT-AP) to move (dys-)functional stress-related beliefs away from and towards themselves, respectively. The per protocol sample consisted of N = 30 participants randomized to an AAMT-AP condition, a swipe control condition, or an inactive control condition. Feasibility and acceptability of the intervention and study design were assessed directly and changes in clinical outcomes (perceived stress (primary outcome), dysfunctional beliefs, symptoms of depression, and emotion regulation skills) one week after intervention completion. The results indicated that AAMT-AP was feasible and acceptable to participants. Moreover, notable effect sizes for clinical outcomes in comparison with both control conditions provided preliminary evidence for its therapeutic potential. Future research should evaluate the efficacy of AAMT-AP in sufficiently powered randomized controlled trials.
CRIS-Team Scopus Importer:2024-07-19
Keywords: Anger; Approach-avoidance modification training; Dysfunctional beliefs; Emotions; Smartphone-based intervention; Stress

An anger-based approach-avoidance modification training targeting dysfunctional beliefs in individuals with elevated stress – Results from a randomized controlled pilot study - Keinert, Eva Marie; Böhme, Stephanie; Schindler-Gmelch, Lena; Streit, Hannah; Rupp, Lydia; Eskofier, Björn; Schuller, Bjorn W.; Berking, Matthias (Kongress der Deutschen Gesellschaft für Verhaltensmedizin 2022, 2022)

An app-based blended intervention to reduce body dissatisfaction: A randomized controlled pilot study - Kollei, Ines; Lukas, Christian; Loeber, Sabine; Berking, Matthias (Journal of Consulting and Clinical Psychology, 2017)
Keywords: Gamification; Body dissatisfaction; Eating disorders; Approach and avoidance; App-based intervention

An evaluation framework for the comparison of fine-grained predictive models in health care - van Breda, Ward R.J.; Hoogendoorn, Mark; Eiben, A. E.; Berking, Matthias (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics), 2015)
Within the domain of health care, more andmore fine-grained models are observed that predict the development of specific health (or disease-related) states over time. This is due to the increased use of sensors, allowing for continuous assessment, leading to a sharp increase of data. These specific models are oftenmuch more complex than high-level predictivemodels that e. g. give a general risk score for a disease, making the evaluation of thesemodels far from trivial. In this paper, we present an evaluation framework which is able to score fine-grained temporal models that aim at predicting multiple health states, considering their capability to describe data, their capability to predict, the quality of the models parameters, and the model complexity.
Created from Fastlane, Scopus look-up

An evaluation framework for the comparison of fine-grained predictive models in health care - van Breda, Ward R. J.; Hoogendoorn, Mark; Eiben, A. E.; Berking, Matthias (Artificial Intelligence in Medicine, 2015)

An Internet-Based Guided Self-Help for Vaginismus. Results of a Randomised Controlled Proof-of-Concept Trial - Zarski, Anna-Carlotta; Berking, Matthias; Fackiner, Christina; Rosenau, Christian; Ebert, David (European Health Psychologist, 2016)

App-based maintenance treatment for alcohol use disorder after acute inpatient treatment: Study protocol for a multicentre randomized controlled trial - Saur, Sebastian; Weisel, Kiona; Lang, Catharina; Fuhrmann, Lukas; Steins-Loeber, Sabine; Enewoldsen, Niklas; Reichl, Daniela; Zink, Mathias; Jakobi, Fabian; Rudolph, Melanie; Ahnert, Andreas; Braunwarth, Wolf Dietrich; et al. (Internet Interventions, 2022)
Background: Alcohol use disorder, a prevalent and disabling mental health problem, is often characterized by a chronic disease course. While effective inpatient and aftercare treatment options exist, the transferal of treatment success into everyday life is challenging and many patients remain without further assistance. App-based interventions with human guidance have great potential to support individuals after inpatient treatment, yet evidence on their efficacy remains scarce. Objectives: To develop an app-based intervention with human guidance and evaluate its usability, efficacy, and cost-effectiveness. Methods: Individuals with alcohol use disorder (DSM-5), aged 18 or higher, without history of schizophrenia, undergoing inpatient alcohol use disorder treatment (N = 356) were recruited in eight medical centres in Bavaria, Germany, between December 2019 and August 2021. Participants were randomized in a 1:1 ratio to either receive access to treatment as usual plus an app-based intervention with human guidance (intervention group) or access to treatment as usual plus app-based intervention after the active study phase (waitlist control/TAU group). Telephone-based assessments are conducted by diagnostic interviewers three and six weeks as well as three and six months after randomization. The primary outcome is the relapse risk during the six months after randomization assessed via the Timeline Follow-Back Interview. Secondary outcomes include intervention usage, uptake of aftercare treatments, AUD-related psychopathology, general psychopathology, and quality of life. Discussion: This study will provide further insights into the use of app-based interventions with human guidance as maintenance treatment in individuals with AUD. If shown to be efficacious, the intervention may improve AUD treatment by assisting individuals in maintaining inpatient treatment success after returning into their home setting. Due to the ubiquitous use of smartphones, the intervention has the potential to become part of routine AUD care in Germany and countries with similar healthcare systems.
CRIS-Team Scopus Importer:2022-03-11
Keywords: Alcohol use disorder; App-based intervention; Germany; Human guidance; Maintenance treatment; RCT

Approaching depression: An emotion-enhanced approach-avoidance modification training targeting dysfunctional cognitions in adult depressin – Pilot study - Keinert, Eva Marie; Hager, Malin; Berking, Matthias (3. Deutscher Psychotherapie Kongress, 2024)

Approaching depression: An emotion-enhanced approach-avoidance modification training targeting dysfunctional cognitions in adult depressin – Randomized controlled pilot study - Keinert, Eva Marie; Hager, Malin; Berking, Matthias (55. Annual International Meeting of the Society for Psychotherapy Research, 2024)

A smartphone application to reduce problematic drinking: a feasibility trial - Lukas, Christian; Blechert, Jens; Berking, Matthias (Pilot and Feasibility Studies, 2024)
Background: Problematic drinking is common among college students and associated with various somatic and mental health problems. Given significant evidence for the efficacy of smartphone-based interventions and the frequent use of smartphones among college students, it can be assumed that such interventions have great potential to facilitate access to evidence-based interventions for students suffering from problematic drinking. Thus, we developed a brief intervention that combined a counseling session with an app that utilizes approach-avoidance modification training to reduce alcohol consumption. Methods: To test the feasibility and explore the potential efficacy of the intervention, we conducted a before-after single-arm study with N = 11 participants reportedly engaging in problematic drinking, who were instructed to practice with the app for 14 days. Feasibility was assessed with the System Usability Scale (SUS). Outcomes included the reduction of self-reported problematic drinking behavior, dysfunctional attitudes about alcohol, and craving, as well as implicit associations between alcohol and self during the training period. Additionally, self-reported problematic drinking behavior was assessed at a 4-week follow-up. Results: On average, participants rated app usability on the SUS (possible range: 0 to 100) with M = 84.32 (SD = 6.53). With regard to efficacy, participants reported a significant reduction of problematic drinking behavior (dpre vs. post = 0.91) which was sustained at follow-up (dfollow-up vs. baseline = 1.07). Additionally, participants reported a significant reduction of dysfunctional attitudes about alcohol (dpre vs. post = 1.48). Results revealed no significant changes in craving nor in implicit associations regarding alcohol. Conclusions: Findings from this feasibility study provide preliminary evidence that smartphone-based interventions might help reduce problematic drinking in college students. Further research needs to replicate these findings with larger samples in randomized controlled trials. Trial registration: DRKS00014675 (retrospectively registered).
CRIS-Team Scopus Importer:2024-03-01
Keywords: Alcohol; Brief intervention; Mobile health; Problematic drinking; Smartphone-based intervention

Assessment of temporal predictive models for health care using a formal method - van Breda, Ward R. J.; Hoogendoorn, Mark; Eiben, A. E.; Berking, Matthias (Computers in Biology and Medicine, 2017)
Recent developments in the field of sensor devices provide new possibilities to measure a variety of health related aspects in a precise and fine-grained manner. Subsequently, more empirical data will be generated than ever before. While this greatly improves the opportunities for creating accurate predictive models, other types of models besides the more traditional machine learning approaches can provide insights into temporal relationships in the data. Models that express temporal relationships between states in a mathematical manner are examples of such models. However, the evaluation methods traditionally used in the field of predictive modeling are not appropriate for those models, making it difficult to distinguish them in terms of validity. Appropriate assessment methodology is therefore necessary to drive the research of mathematical modeling forward. In this paper we investigate the applicability of such a formalized method. The method takes into account important model aspects, namely descriptive and predictive capability, parameter sensitivity and model complexity. As a case study the method is applied to a mathematical model in the domain of mental health, showing that the method generates useful insights into the behavior of the model.<br
Keywords: Depression; Health care; Mathematical modeling; Model evaluation; Multi-objective optimization; Predictive modeling; Regression

Association of impulsivity with quality of life and well-being after alcohol withdrawal treatment - Reichl, Daniela; Enewoldsen, Niklas; Weisel, Kiona; Fuhrmann, Lukas; Lang, Catharina; Saur, Sebastian; Berking, Matthias; Zink, Mathias; Ahnert, Andreas; Falkai, Peter; Kraus, Thomas; Hillemacher, Thomas; et al. (Journal of Clinical Psychology, 2022)
Objectives Impulsivity is related to a higher risk of relapse in alcohol use disorders. However, besides drinking behavior, other recovery outcomes like physical and mental health-related quality of life are at least as important. The present study aimed to fill a research gap regarding the association of different impulsivity facets with health-related quality of life and well-being in alcohol use disorder. Methods Individuals with a primary alcohol use disorder diagnosis (n = 167) were interviewed with standardized self-report measures at the progressed stage of their withdrawal treatment and 6 weeks thereafter. Multiple regression models were calculated to examine the association of impulsivity, craving, and drinking patterns with health-related quality of life and well-being 6 weeks after withdrawal treatment, as well as the predictive role of impulsivity assessed during withdrawal for these two outcomes. Results Craving was associated with health-related quality of life and well-being 6 weeks after withdrawal. Likewise, non-planning and attentional impulsivity were associated with well-being 6 weeks after withdrawal. Motor impulsivity during withdrawal treatment predicted health-related quality of life 6 weeks thereafter. Conclusion Impulsivity seems to be negatively related to health-related quality of life and well-being in the first weeks after alcohol withdrawal treatment, probably to a higher extent than drinking patterns, but differentiating between its facets seems to be important. These findings emphasize the importance of treatment approaches aiming at reduced impulsivity in the early recovery process.
CRIS-Team WoS Importer:2022-02-04

A transdiagnostic internet-based maintenance treatment enhances the stability of outcome after inpatient cognitive behavioral therapy: A randomized controlled trial - Ebert, David Daniel; Tarnowski, Torsten; Gollwitzer, Mario; Sieland, Bernhard; Berking, Matthias (Psychotherapy and Psychosomatics, 2013)
Background: High relapse rates following acute treatment for common mental health disorders support the importance of developing maintenance phase interventions. Internet-based interventions have been effective for a broad range of mental disorders, but less is known about their potential to enhance long-term outcomes of traditional face-to-face therapy. Therefore, the goal of the present study was to evaluate a transdiagnostic Internet-based maintenance treatment (TIMT) with the purpose of fostering long-term effects of inpatient psychotherapy. Method: In this pragmatic randomized controlled trial, a sample of 400 inpatients with affective, neurotic, and/or behavioral disorders was assigned to either 12 weeks of TIMT + treatment as usual (TAU) or to TAU-only following hospital discharge. TIMT consists of a self-management module, asynchronous patient-coach communication, online patient support group, and online-based monitoring of psychopathological symptoms. Self-ratings of psychopathological symptoms were conducted at the beginning of inpatient treatment (t1), at discharge from inpatient treatment/start of TIMT (t2), and at 3-month (t3) and 12-month follow-ups (t4). Results: The TIMT + TAU group was superior to the TAU-only group with regard to differences in change of general psychopathological symptom severity from discharge to 3-and 12-month follow-up. Moreover, participants of the TIMT + TAU group showed less frequent symptom deteriorations and were more often in remission/recovery than controls. Conclusion: TIMT effectively enhances long-term outcome of inpatient psychotherapy.
Created from Fastlane, Scopus look-up
Keywords: Continuation treatment; Inpatient psychotherapy; Internet therapy; Internet-based guided self-help; Maintenance treatment; Pragmatic trial; Relapse prevention; Stepped care; Transdiagnostic treatment

Attitudes towards digital treatment for depression: A European stakeholder survey - Topooco, Naira; Riper, Heleen; Araya, Ricardo; Berking, Matthias; Brunn, Matthias; Chevreul, Karine; Cieslak, Roman; Ebert, David; Etchmendy, Ernestina; Herrero, Rocío; Kleiboer, Annet; Krieger, Tobias; et al. (Internet Interventions, 2017)
Background The integration of digital treatments into national mental health services is on the agenda in the European Union. The E-COMPARED consortium conducted a survey aimed at exploring stakeholders’ knowledge, acceptance and expectations of digital treatments for depression, and at identifying factors that might influence their opinions when considering the implementation of these approaches. Method An online survey was conducted in eight European countries: France, Germany, Netherlands, Poland, Spain, Sweden, Switzerland and The United Kingdom. Organisations representing government bodies, care providers, service-users, funding/insurance bodies, technical developers and researchers were invited to participate in the survey. The participating countries and organisations reflect the diversity in health care infrastructures and e-health implementation across Europe. Results A total of 764 organisations were invited to the survey during the period March–June 2014, with 175 of these organisations participating in our survey. The participating stakeholders reported moderate knowledge of digital treatments and considered cost-effectiveness to be the primary incentive for integration into care services. Low feasibility of delivery within existing care services was considered to be a primary barrier. Digital treatments were regarded more suitable for milder forms of depression. Stakeholders showed greater acceptability towards blended treatment (the integration of face-to-face and internet sessions within the same treatment protocol) compared to standalone internet treatments. Organisations in countries with developed e-health solutions reported greater knowledge and acceptability of digital treatments. Conclusion Mental health stakeholders in Europe are aware of the potential benefits of digital interventions. However, there are variations between countries and stakeholders in terms of level of knowledge about such interventions and their feasibility within routine care services. The high acceptance of blended treatments is an interesting finding that indicates a gradual integration of technology into clinical practice may fit the attitudes and needs of stakeholders. The potential of the blended treatment approach, in terms of enhancing acceptance of digital treatment while retaining the benefit of cost-effectiveness in delivery, should be further explored. Funding The E-COMPARED project has received funding from the European Union Seventh Framework Programme (FP7/2007–2013) under grant agreement no. 603098.
Keywords: Blended treatment; Comparative effectiveness research; Depression; Digital treatment; E-mental health; Internet-delivered

A Universal Digital Stress Management Intervention for Employees: Randomized Controlled Trial with Health-Economic Evaluation - Freund, Johanna; Smit, Filip; Lehr, Dirk; Zarski, Anna-Carlotta; Berking, Matthias; Riper, Heleen; Funk, Burkhardt; Ebert, David Daniel; Buntrock, Claudia (Journal of Medical Internet Research, 2024)
BACKGROUND: Stress is highly prevalent and known to be a risk factor for a wide range of physical and mental disorders. The effectiveness of digital stress management interventions has been confirmed; however, research on its economic merits is still limited. OBJECTIVE: This study aims to assess the cost-effectiveness, cost-utility, and cost-benefit of a universal digital stress management intervention for employees compared with a waitlist control condition within a time horizon of 6 months. METHODS: Recruitment was directed at the German working population. A sample of 396 employees was randomly assigned to the intervention group (n=198) or the waitlist control condition (WLC) group (n=198). The digital stress management intervention included 7 sessions plus 1 booster session, which was offered without therapeutic guidance. Health service use, patient and family expenditures, and productivity losses were self-assessed and used for costing from a societal and an employer's perspective. Costs were related to symptom-free status (PSS-10 [Perceived Stress Scale] score 2 SDs below the study population baseline mean) and quality-adjusted life years (QALYs) gained. The sampling error was handled using nonparametric bootstrapping. RESULTS: From a societal perspective, the digital intervention was likely to be dominant compared with WLC, with a 56% probability of being cost-effective at a willingness-to-pay (WTP) of €0 per symptom-free person gained. At the same WTP threshold, the digital intervention had a probability of 55% being cost-effective per QALY gained relative to the WLC. This probability increased to 80% at a societal WTP of €20,000 per QALY gained. Taking the employer's perspective, the digital intervention showed a probability of a positive return on investment of 78%. CONCLUSIONS: Digital preventive stress management for employees appears to be cost-effective societally and provides a favorable return on investment for employers. TRIAL REGISTRATION: German Clinical Trials Register DRKS00005699; https://drks.de/search/en/trial/DRKS00005699.
CRIS-Team Scopus Importer:2024-11-01
Keywords: cost-benefit; cost-effectiveness; cost-utility; economic evaluation; employees; internet-based; return-on-investment; stress management; universal prevention

A Web- and Mobile-Based Intervention for Comorbid, Recurrent Depression in Patients With Chronic Back Pain on Sick Leave (Get.Back): Pilot Randomized Controlled Trial on Feasibility, User Satisfaction, and Effectiveness - Schlicker, Sandra; Baumeister, Harald; Buntrock, Claudia; Sander, Lasse; Paganini, Sarah; Lin, Jiaxi; Berking, Matthias; Lehr, Dirk; Ebert, David (JMIR Mental Health, 2020)
Background: Chronic back pain (CBP) is linked to a higher prevalence and higher occurrence of major depressive disorder (MDD) and can lead to reduced quality of life. Unfortunately, individuals with both CBP and recurrent MDD are underidentified. Utilizing health care insurance data may provide a possibility to better identify this complex population. In addition, internet-and mobile-based interventions might enhance the availability of existing treatments and provide help to those highly burdened individuals.
CRIS-Team WoS Importer:2020-05-12

Barriers and Facilitators for Referrals of Primary Care Patients to Blended Internet-Based Psychotherapy for Depression: Mixed Methods Study of General Practitioners' Views - Titzler, Ingrid; Berking, Matthias; Schlicker, Sandra; Riper, Heleen; Ebert, David (JMIR Mental Health, 2020)
Background: Major depressive disorder (MDD) is highly prevalent and often managed by general practitioners (GPs). GPs mostly prescribe medication and show low referral rates to psychotherapy. Many patients remain untreated. Blended psychotherapy (bPT) combines internet-based interventions with face-to-face psychotherapy and could increase treatment access and availability. Effectively implementing bPT in routine care requires an understanding of professional users' perspectives and behavior.
CRIS-Team WoS Importer:2020-09-04

Barriers and facilitators for the implementation of blended psychotherapy for depression: A qualitative pilot study of therapists' perspective - Titzler, Ingrid; Saruhanjan, Karina; Berking, Matthias; Riper, Heleen; Ebert, David (Internet Interventions, 2018)
Keywords: Facilitators; Qualitative study; Blended therapy; Depression; Therapists' view; Barriers

Blended Psychotherapy: Treatment Concept and Case Report for the Integration of Internet- A nd Mobile-Based Interventions into Brief Psychotherapy of Depressive Disorders - Titzler, Ingrid; Egle, Viktoria; Berking, Matthias; Gumbmann, Corinna; Ebert, David (Verhaltenstherapie, 2019)
Background: Blended psychotherapy (bPT) is a treatment that integrates internet- A nd mobile-based interventions into out-/inpatient psychotherapy. It can enrich the therapy by using online-based treatment modules as therapeutic extension that patients use time- A nd location-independently between face-to-face sessions. It could potentially improve the efficacy of psychotherapy and increase the number of treated persons through saved therapist time. The case report aims to facilitate the understanding of the blended treatment components. Case Report: A 4-month short-time depression treatment with six face-to-face therapy sessions, six online lessons, and app ratings of a 48-year-old female patient is presented based on the CARE guidelines and quantitative and qualitative measures (treatment documentation). Depressive symptoms were clinically significantly reduced (PHQ-9, 0-27: T0 = 17; T1 = 7) from a moderately severe to a subclinical-mild degree, and no diagnostic criteria were met in the 12-month follow-up diagnostic interview. The patient showed a maximum treatment satisfaction (ZUF-8, 8-32: T1 = 32) and adherence and rated the therapeutic working alliance (WAI, 12-60: T1 = 57) highly positive. Conclusion: BPT reduced depressive symptoms for this patient. Strengths of the treatment were the facilitated use of the internet-based elements with a full-time job and the individualization within the face-to-face sessions through the therapist. Treatment success was limited by the predetermined six sessions, which hindered addressing all topics and conducting relapse prevention.
CRIS-Team Scopus Importer:2019-12-10
Keywords: Blended psychotherapy; Case report; Depressive disorder; Internet-/mobile-assisted brief psychotherapy

Blended Psychotherapy – verzahnte Psychotherapie: Behandlungskonzept und Fallbericht zur Integration von Internet- und Mobil-basierten Interventionen in die Kurzzeittherapie von depressiven Störungen - Titzler, Ingrid; Egle, Viktoria; Berking, Matthias; Gumbmann, Corinna; Ebert, David (Verhaltenstherapie, 2019)
Background: Blended psychotherapy (bPT) is a treatment that integrates internet- and mobile-based interventions into out-/inpatient psychotherapy. It can enrich the therapy by using online-based treatment modules as therapeutic extension that patients use time- and location-independently between face-to-face sessions. It could potentially improve the efficacy of psychotherapy and increase the number of treated persons through saved therapist time. The case report aims to facilitate the understanding of the blended treatment components. Case Report: A 4-month short-time depression treatment with six face-to-face therapy sessions, six online lessons, and app ratings of a 48-year-old female patient is presented based on the CARE guidelines and quantitative and qualitative measures (treatment documentation). Depressive symptoms were clinically significantly reduced (PHQ-9, 0-27: T0 = 17; T1 = 7) from a moderately-severe to a subclinical-mild degree, and no diagnostic criteria were met in the 12-month follow-up diagnostic interview. The patient showed a maximum treatment satisfaction (ZUF-8, 8-32: T1 = 32) and adherence and rated the therapeutic working alliance (WAI, 12-60: T1 = 57) highly positive. Conclusion: bPT reduced depressive symptoms for this patient. Strengths of the treatment were the facilitated use of the internet-based elements with a full-time job and the individualization within the face-to-face sessions through the therapist. Treatment success was limited by the predetermined six sessions, which hindered addressing all topics and conducting relapse prevention.
CRIS-Team Scopus Importer:2019-09-17
Keywords: Blended therapy; Case report; Depressive disorder; Internet-/mobile-assisted brief psychotherapy

Blending group-based psychoeducation with a smartphone intervention for the reduction of depressive symptoms: results of a randomized controlled pilot study - Lukas, Christian; Berking, Matthias (Pilot and Feasibility Studies, 2021)
Background: Given their ubiquity and technological facilities, smartphone-based interventions (SBIs) hold potential to support the cost-effective dissemination of evidence-based treatments for depression. As technologically enriched, blended approach–avoidance modification trainings (AAMTs) have recently been shown effective for symptom reduction in various mental health problems, we developed a blended SBI combining group-based psychoeducation and 14 days of app training utilizing principles from AAMT to reduce depressive symptoms. Methods: In this pilot trial, N = 16 individuals with heightened depression scores were randomized to either an intervention group using the mentalis Phoenix app or a wait list control condition. As outcomes, we descriptively explored usability of the app, engagement with the intervention, and possible reductions of depressive symptoms. Results: Data analyses suggest that the SBI tested in this pilot trial possesses high usability, is frequently engaged with, and reduces depressive symptoms in participants in the intervention group when compared to wait list controls. Conclusions: This pilot study provides preliminary evidence that an SBI utilizing AAMT can reduce depressive symptoms. Future studies should replicate these findings using larger samples and disentangle possible mechanisms of change. Trial registration: DRKS-ID: DRKS00021613 (retrospectively registered).
CRIS-Team Scopus Importer:2021-03-26
Keywords: Approach–avoidance; Depression; Intervention; Pilot study; Smartphone

Borderline Personality Features and Harmful Dysregulated Behavior: The Mediational Effect of Mindfulness - Wupperman, Peggilee; Fickling, Melissa; Klemanski, David H.; Berking, Matthias; Whitman, Jeannie B. (Journal of Clinical Psychology, 2013)
Objectives: The current preliminary study investigated whether deficits in mindfulness (awareness, attentiveness, and acceptance of the present experience) may underlie the relationship of borderline personality disorder (BPD) features to self-injury and overall acts of harmful dysregulated behavior. Method: Nonparametric bootstrapping procedures were used to examine theoretical relationships among variables in a psychiatric sample of adults (N = 70). Participants were asked to imagine themselves in distress-inducing situations and then write what they would actually do to decrease distress in such situations. Results: As hypothesized, mindfulness statistically mediated the relationship of BPD features to reported acts of (a) self-injury and (b) overall harmful dysregulated behaviors. Conclusions: Difficulties in the ability to be aware, attentive, and accepting of ongoing experience may play a role in the relationship of BPD features to harmful dysregulated behaviors. Future research should clarify potential reciprocal effects between BPD features and mindfulness with prospective, multioccasion designs. © 2013 Wiley Periodicals, Inc.
Created from Fastlane, Scopus look-up
Keywords: Borderline personality; Dysregulation; Impulsivity; Mindfulness; Self-injury; Substance

Bouldering psychotherapy is not inferior to cognitive behavioural therapy in the group treatment of depression: A randomized controlled trial - Luttenberger, Katharina; Berking, Matthias; Kind, Leona; Weiss, Maren; Kornhuber, Johannes; Dorscht, Lisa; Karg-Hefner, Nina (British Journal of Clinical Psychology, 2021)
Objectives: Bouldering has shown promising results in the treatment of various health problems. In previous research, bouldering psychotherapy (BPT) was shown to be superior to a waitlist control group and to physical exercise with regard to reducing symptoms of depression. The primary aim of this study was to compare group BPT with group cognitive behavioural psychotherapy (CBT) to test the hypothesis that BPT would be equally as effective as CBT. Design: We conducted a randomized, controlled, assessor-blinded non-inferiority trial in which 156 outpatients meeting the criteria of a depressive episode according to the Diagnostic and Statistical Manual of Mental Disorders (DSM-IV) were randomly assigned to one of the two intervention groups (CBT: N = 77, BPT: N = 79). Methods: Intervention groups were manualized and treated for 10 weeks with a maximum of 11 participants and two therapists. The primary outcome was depressive symptom severity assessed with the Montgomery–Åsberg Depression Rating Scale (MADRS) and the Patient Health questionnaire (PHQ-9) at the beginning and end of the treatment phase as well as one year after the end of treatment. Result: In both groups, depressive symptoms improved significantly by an average of one severity level, moving from moderate to mild depressive symptoms after therapy (MADRS difference scores: BPT −8.06, 95% CI [−10.85, −5.27], p <.001; CBT −5.99, 95% CI [−8.55, −3.44], p <.001). The non-inferiority of BPT in comparison with CBT was established on the basis of the lower bound of the 95% confidence interval falling above all of the predefined margins. BPT was found to be effective in both the short (d = 0.89) and long term (d = 1.15). Conclusion: Group BPT was found to be equally as effective as group CBT. Positive effects were maintained until at least 12 months after the end of therapy. Thus, BPT is a promising approach for broadening the therapeutic field of therapies for depression. Practitioner points: Physical activity is effective in the treatment of depression and current guidelines explicitly recommend it as a complementary method for the treatment of depression. Nevertheless, body-related interventions are still underrepresented in current treatments for depression. Bouldering psychotherapy (BPT) combines physical activity with psychotherapeutic content. Its concept relies on proven effective factors from CBT such as exposure training, problem solving and practicing new functional behaviours and is thus an enrichment and implementation of CBT methods on the bouldering wall. The positive effect of group bouldering psychotherapy (BPT) in reducing depressive symptoms in outpatients with depression is not inferior to the effect of group cognitive behavioural therapy (CBT). Additionally the 10-weeks BPT-programme significantly improved symptoms of anxiety and interpersonal sensitivity as well as health-related quality of life, coping, body image, self-efficacy, and global self-esteem.
Created from Fastlane, Scopus look-up
Keywords: bouldering; cognitive behavioural therapy; depression; exercise; Group; physical activity; psychotherapy; rock climbing; sports

Breathe your stress away. Preliminary results of a randomized controlled study investigating a breath-based approach-avoidance modification training in individuals with elevated stress - Keinert, Eva Marie; Böhme, Stephanie; Eskofier, Björn; Schuller, Björn W.; Berking, Matthias (2. Deutscher Psychotherapie Kongress, 2023)

Can a One-Item Mood Scale Do the Trick? Predicting Relapse over 5.5-Years in Recurrent Depression - van Rijsbergen, Gerard D.; Bockting, Claudi L.H.; Berking, Matthias; Koeter, Maarten W.J.; Schene, Aart H. (PLoS ONE, 2012)
Background: To examine whether a simple Visual Analogue Mood Scale (VAMS) is able to predict time to relapse over 5.5-years. Methodology/Principal Findings: 187 remitted recurrently depressed out-patients were interviewed using the Structured Clinical Interview for DSM-IV Axis I Disorders (SCID-I) and the 17-item Hamilton Depression rating scale (HAM-D) to verify remission status (HAM-D <10). All patients rated their current mood with the help of a Visual Analogue Mood Scale (VAMS) at baseline and at a follow-up assessment three months later. Relapse over 5.5-years was assessed by the SCID-I. Cox regression revealed that both the VAMS at baseline and three months later significantly predicted time to relapse over 5.5-years. Baseline VAMS even predicted time to relapse when the number of previous depressive episodes and HAM-D scores were controlled for. The baseline VAMS explained 6.3% of variance in time to relapse, comparable to the HAM-D interview. Conclusions/Significance: Sad mood after remission appears to play a pivotal role in the course of depression. Since a simple VAMS predicted time to relapse, the VAMS might be an easy and time-effective way to monitor mood and risk of early relapse, and offers possibilities for daily monitoring using e-mail and SMS. Trial Registration: International Standard Randomized Controlled Trial Register Identifier: ISRCTN68246470. © 2012 van Rijsbergen et al.
Created from Fastlane, Scopus look-up

Case report for an internet- and mobile-based intervention for internet use disorder - Bernstein, Karina; Zarski, Anna-Carlotta; Pekarek, Emilia; Schaub, Michael Patrick; Berking, Matthias; Baumeister, Harald; Ebert, David Daniel (Frontiers in Psychiatry, 2023)
Background and aims: Internet use disorder (IUD), characterized as the inability to control one’s internet use, is associated with reduced quality of life and mental health comorbidities such as depression, substance abuse, or anxiety. Evidence-based treatment options are scarce due to the novelty of the diagnosis. Internet- and mobile-based interventions (IMI) may be an effective means to deliver psychological treatment to individuals with IUD as they address affected individuals in their online setting. This study presents a newly developed IMI for IUD disclosing treatment satisfaction and preliminary effects by exemplifying with a case report. Methods: The case of a female participant with IUD, characterized by an excessive use of social media, is analyzed. The case report follows the CARE guidelines and presents qualitative and quantitative outcomes regarding potential symptom reduction measured by the Internet Addiction Test (IAT) and Compulsive Internet Use Scale (CIUS), treatment satisfaction measured by the Client Satisfaction Questionnaire (CSQ) and feasibility by analyzing participant’s written feedback during treatment. Results: The case report shows that internet- and mobile-based interventions may be feasible in supporting an individual in reducing symptoms of IUD as well as depressive symptoms, anxiety and procrastination behavior. Treatment satisfaction was reported as good. Discussion and conclusions: This case report illustrates that IMIs can have the potential to be an easily accessible and possibly effective treatment option for IUD. Case studies on IMIs may provide insights into important mechanisms for symptom change. Further studies are needed to expand our understanding of this diverse disorder to provide adequate treatment. Clinical Trial Registration: https://clinicaltrials.gov/,DRKS00015314.
CRIS-Team Scopus Importer:2023-08-18
Keywords: case report; internet use disorder; internet- and mobile-based intervention; social media use; student

CBASP@home: Ein internetbasiertes Situationsanalysen-Training zur Stabilisierung des Therapieerfolgs nach stationärer Therapie für chronisch depressive Patienten - Brakemeier, Eva Lotta; Marchner, Janina; Gutgsell, Simone; Engel, Vera; Radtke, Martina; Tuschen-Caffier, Brunna; Normann, Claus; Berking, Matthias (Verhaltenstherapie, 2013)
Hintergrund: Aufbauend auf einer ambulanten CBASP-Behandlung wurde ein stationäres multidisziplinäres Konzept zur Behandlung chronischer Depression entwickelt. Eine Pilotstudie zeigte positive Ergebnisse hinsichtlich der Wirkung dieses Konzepts, jedoch berichteten einige Patienten, dass die 12-wöchige Therapie zu kurz und die Zeit unmittelbar nach Entlassung schwierig sei. Daher wurde CBASP@home als ein internetbasiertes Situationsanalysen (SA)-Training zur Stabilisierung des erzielten Behandlungserfolgs konzipiert. CBASP@home ist eine 3-monatige Step-down-Onlineintervention. Die Patienten werden dabei unterstützt, die erlernten SA zu Hause fortzuführen und in den Alltag zu transferieren. An insgesamt 9 Terminen füllten die Patienten das SA-Formular über einen Sicherheitsserver aus und erhielten von ihrem stationären Psychotherapeuten zeitnah Rückmeldung. Fallbericht: In der vorliegenden Phase-I-Studie wurde die Akzeptanz und Durchführbarkeit von CBASP@home an 2 Einzelfällen untersucht. CBASP@home wurde von beiden Patienten sehr gut angenommen und als sinnvolle Unterstützung bewertet. Zudem konnte bei beiden Patienten eine zunehmende Leistungssteigerung in der SA-Durchführung bei gleichzeitig rückläufiger depressiver Symptomatik bis zur Remission beobachtet werden. Schlussfolgerungen: Die beiden Einzelfallauswertungen liefern Hinweise, dass CBASP@home Transferprozesse vom stationären Setting in den Alltag erleichtern, Behandlungserfolge beibehalten bzw. Rückfällen vorbeugen kann. Wenn sich diese positiven Erfahrungen in zukünftigen Studien bestätigen sollten, kann CBASP@home wesentlich zur Verbesserung der langfristigen Versorgung chronisch depressiver Patienten beitragen. © 2013 S. Karger GmbH, Freiburg.
Created from Fastlane, Scopus look-up
Keywords: CBASP; Chronische Depression; Internetbasierte Psychotherapie; Rückfallprophylaxe; Situationsanalyse

Clinical and Cost-Effectiveness of Personalized Tele-Based Coaching for Farmers, Foresters and Gardeners to Prevent Depression: Study Protocol of an 18-Month Follow-Up Pragmatic Randomized Controlled Trial (TEC-A) - Thielecke, Janika; Buntrock, Claudia; Titzler, Ingrid; Braun, Lina; Freund, Johanna; Berking, Matthias; Baumeister, Harald; Ebert, David (Frontiers in Psychiatry, 2020)
Background: Farmers show high levels of depressive symptoms and mental health problems in various studies. This study is part of a nationwide prevention project carried out by a German social insurance company for farmers, foresters, and gardeners (SVLFG) to implement internet- and tele-based services among others to improve mental health in this population. The aim of the present study is to evaluate the (cost-)effectiveness of personalized tele-based coaching for reducing depressive symptom severity and preventing the onset of clinical depression, compared to enhanced treatment as usual.
CRIS-Team WoS Importer:2020-05-02

Cognitive Behaviour Therapy Complemented with Emotion Regulation Training for Patients with Persistent Physical Symptoms: A Randomised Clinical Trial - Kleinstäuber, Maria; Allwang, Christine; Bailer, Josef; Berking, Matthias; Brünahl, Christian; Erkic, Maja; Gitzen, Harald; Gollwitzer, Mario; Gottschalk, Japhia Marie; Heider, Jens; Hermann, Andrea; Lahmann, Claas; et al. (Psychotherapy and Psychosomatics, 2019)
INTRODUCTION: Persistent medically unexplained symptoms (MUS) are a major burden for health care. Cognitive behaviour therapy (CBT) is efficacious for patients with MUS, with small to medium effects. The current study investigates whether therapy outcomes of a CBT for MUS patients can be improved by complementing it with emotion regulation training. METHODS: In a multicentre trial 255 patients with at least three persisting MUS were randomised to 20 sessions of either conventional CBT (n = 128) or CBT complemented with emotion regulation training (ENCERT; n = 127). Somatic symptom severity and secondary outcomes were assessed at pre-treatment, therapy session 8, end of therapy, and 6-month follow-up. RESULTS: Linear mixed-effect models revealed medium to large effects in both study arms for almost all outcomes at the end of therapy and 6-month follow-up. ENCERT and CBT did not differ in their effect on the primary outcome (d = 0.20, 95% CI: -0.04 to 0.44). Significant time × group cross-level interactions suggested ENCERT to be of more benefit than conventional CBT for a few secondary outcomes. Moderator analyses revealed higher effects of ENCERT in patients with co-morbid mental disorders. DISCUSSION/CONCLUSIONS: Current findings are based on a representative sample. Results demonstrate that both CBT and ENCERT can achieve strong effects on primary and secondary outcomes in MUS patients. Our results do not indicate that adding a training in emotion regulation skills generally improves the effect of CBT across all patients with MUS. Large effect sizes of both treatments and potential specific benefits of ENCERT for patients with co-morbid mental disorders are discussed.
CRIS-Team Scopus Importer:2019-10-08
Keywords: Cognitive behaviour therapy; Emotion regulation; Persistent physical symptoms; Randomised controlled trial; Somatic symptom severity

Cognitive interference and a food-related memory bias in binge eating disorder. - Svaldi, Jennifer; Schmitz, Florian; Trentowska, Monika; Tuschen-Caffier, Brunna; Berking, Matthias; Naumann, Eva (Appetite, 2014)
The present study was concerned with cognitive interference and a specific memory bias for eating-related stimuli in binge eating disorder (BED). Further objectives were to find out under which circumstances such effects would occur, and whether they are related with each other and with reported severity of BED symptoms. A group of women diagnosed with BED and a matched sample of overweight controls completed two paradigms, an n-back task with lures and a recent-probes task. The BED group generally experienced more interference in the n-back task. Additionally, they revealed selectively increased interference for food items in the recent-probes task. Findings can be reconciled with the view that control functions are generally impaired in BED, and that there is an additional bias for eating-related stimuli, both of which were related with reported severity of BED symptoms.

Comparison of psychotherapies for adult depression to pill placebo control groups: a meta-analysis. - Mohr, D. C.; Hofmann, S. G.; Berking, Matthias; Andersson, Gerhard; Coyne, J.; Turner, E. H.; Cuijpers, Pim (Psychological Medicine, 2014)
BACKGROUND: The effects of antidepressants for treating depressive disorders have been overestimated because of selective publication of positive trials. Reanalyses that include unpublished trials have yielded reduced effect sizes. This in turn has led to claims that antidepressants have clinically insignificant advantages over placebo and that psychotherapy is therefore a better alternative. To test this, we conducted a meta-analysis of studies comparing psychotherapy with pill placebo. METHOD: Ten 10 studies comparing psychotherapies with pill placebo were identified. In total, 1240 patients were included in these studies. For each study, Hedges' g was calculated. Characteristics of the studies were extracted for subgroup and meta-regression analyses. RESULTS: The effect of psychotherapy compared to pill placebo at post-test was g = 0.25 [95% confidence interval (CI) 0.14-0.36, I² = 0%, 95% CI 0-58]. This effect size corresponds to a number needed to treat (NNT) of 7.14 (95% CI 5.00-12.82). The psychotherapy conditions scored 2.66 points lower on the Hamilton Depression Rating Scale (HAMD) than the placebo conditions, and 3.20 points lower on the Beck Depression Inventory (BDI). Some indications for publication bias were found (two missing studies). We found no significant differences between subgroups of the studies and in meta-regression analyses we found no significant association between baseline severity and effect size. CONCLUSIONS: Although there are differences between the role of placebo in psychotherapy and pharmacotherapy research, psychotherapy has an effect size that is comparable to that of antidepressant medications. Whether these effects should be deemed clinically relevant remains open to debate.

Comparison of speech elicitation tasks for machine learning-based depression classification - Bauer, Jonathan; Gerczuk, Maurice; Schuller, Björn; Berking, Matthias (International Medicine and Health Sciences Congress IMHSC 2024, 2024)
Machine learning-based depression classification based on paralinguistic speech parameters yields a novel approach to detect depression. However, there is uncertainty about the effect of different types of speech recordings on classification accuracy. We suggest that recordings of free speech containing antidepressive statements may be particularly suitable for depression classification. To test this hypothesis, we conducted Structured Clinical Interviews for DSM-5 to determine depression diagnoses on suitable candidates, resulting in a final sample of 48 clinically depressed individuals, 48 sub-clinically depressed individuals, and 48 non-depressed individuals. Participants from each group completed four different speech tasks: Participants read aloud neutral texts, they read aloud scripted depressive statements, they came up with and expressed anti-depressive statements, and 50% of participants read aloud scripted anti-depressive statements. Separate classification models aimed at classifying current depression were trained for each speech type and with two different state-of-the-art machine learning methods. We found that training a depression classification model on recordings of anti-depressive statements was not superior to training models on other types of speech recordings. We only found a significantly better accuracy for the depression classification model trained on recordings of neutral read speech compared to the model trained on recordings of depressive read speech. We could not confirm our hypothesis that recordings of antidepressive statements would result in superior depression classification accuracy compared to recordings of neutral text reading. Eliciting depression-related speech may reduce affective variability in individuals’ responses and therefore diminish depression-discriminative information. Our findings provide important directions for future research aimed to optimize speech elicitation tasks for depression classificatio
Keywords: Depression; Speech; Voice; Machine Learning; Speech Elicitation

Comparison of the Working Alliance in Blended Cognitive Behavioral Therapy and Treatment as Usual for Depression in Europe: Secondary Data Analysis of the E-COMPARED Randomized Controlled Trial - Doukani, Asmae; Quartagno, Matteo; Sera, Francesco; Free, Caroline; Kakuma, Ritsuko; Riper, Heleen; Kleiboer, Annet; Cerga-Pashoja, Arlinda; van Schaik, Anneke; Botella, Cristina; Berger, Thomas; Chevreul, Karine; et al. (Journal of Medical Internet Research, 2024)
BACKGROUND: Increasing interest has centered on the psychotherapeutic working alliance as a means of understanding clinical change in digital mental health interventions in recent years. However, little is understood about how and to what extent a digital mental health program can have an impact on the working alliance and clinical outcomes in a blended (therapist plus digital program) cognitive behavioral therapy (bCBT) intervention for depression. OBJECTIVE: This study aimed to test the difference in working alliance scores between bCBT and treatment as usual (TAU), examine the association between working alliance and depression severity scores in both arms, and test for an interaction between system usability and working alliance with regard to the association between working alliance and depression scores in bCBT at 3-month assessments. METHODS: We conducted a secondary data analysis of the E-COMPARED (European Comparative Effectiveness Research on Blended Depression Treatment versus Treatment-as-usual) trial, which compared bCBT with TAU across 9 European countries. Data were collected in primary care and specialized services between April 2015 and December 2017. Eligible participants aged 18 years or older and diagnosed with major depressive disorder were randomized to either bCBT (n=476) or TAU (n=467). bCBT consisted of 6-20 sessions of bCBT (involving face-to-face sessions with a therapist and an internet-based program). TAU consisted of usual care for depression. The main outcomes were scores of the working alliance (Working Alliance Inventory-Short Revised-Client [WAI-SR-C]) and depressive symptoms (Patient Health Questionnaire-9 [PHQ-9]) at 3 months after randomization. Other variables included system usability scores (System Usability Scale-Client [SUS-C]) at 3 months and baseline demographic information. Data from baseline and 3-month assessments were analyzed using linear regression models that adjusted for a set of baseline variables. RESULTS: Of the 945 included participants, 644 (68.2%) were female, and the mean age was 38.96 years (IQR 38). bCBT was associated with higher composite WAI-SR-C scores compared to TAU (B=5.67, 95% CI 4.48-6.86). There was an inverse association between WAI-SR-C and PHQ-9 in bCBT (B=-0.12, 95% CI -0.17 to -0.06) and TAU (B=-0.06, 95% CI -0.11 to -0.02), in which as WAI-SR-C scores increased, PHQ-9 scores decreased. Finally, there was a significant interaction between SUS-C and WAI-SR-C with regard to an inverse association between higher WAI-SR-C scores and lower PHQ-9 scores in bCBT (b=-0.030, 95% CI -0.05 to -0.01; P=.005). CONCLUSIONS: To our knowledge, this is the first study to show that bCBT may enhance the client working alliance when compared to evidence-based routine care for depression that services reported offering. The working alliance in bCBT was also associated with clinical improvements that appear to be enhanced by good program usability. Our findings add further weight to the view that the addition of internet-delivered CBT to face-to-face CBT may positively augment experiences of the working alliance. TRIAL REGISTRATION: ClinicalTrials.gov NCT02542891, https://clinicaltrials.gov/study/NCT02542891; German Clinical Trials Register DRKS00006866, https://drks.de/search/en/trial/DRKS00006866; Netherlands Trials Register NTR4962, https://www.onderzoekmetmensen.nl/en/trial/25452; ClinicalTrials.Gov NCT02389660, https://clinicaltrials.gov/study/NCT02389660; ClinicalTrials.gov NCT02361684, https://clinicaltrials.gov/study/NCT02361684; ClinicalTrials.gov NCT02449447, https://clinicaltrials.gov/study/NCT02449447; ClinicalTrials.gov NCT02410616, https://clinicaltrials.gov/study/NCT02410616; ISRCTN Registry ISRCTN12388725, https://www.isrctn.com/ISRCTN12388725?q=ISRCTN12388725&filters=&sort=&offset=1&totalResults=1&page=1&pageSize=10; ClinicalTrials.gov NCT02796573, https://classic.clinicaltrials.gov/ct2/show/NCT02796573. INTERNATIONAL REGISTERED REPORT IDENTIFIER (IRRID): RR2-10.1186/s13063-016-1511-1.
CRIS-Team Scopus Importer:2024-06-14
Keywords: blended psychotherapy; cognitive behavioral therapy; depression; digital mental health interventions; mental health; program usability; psychotherapy; therapeutic alliance; usability heuristics; working alliance

Corrigendum to “The influence of emotion regulation on posttraumatic stress symptoms among Japanese people” [Journal of Affective Disorders 277 (2020) 577–583] (Journal of Affective Disorders (2020) 277 (577–583), (S0165032720326628), (10.1016/j.jad.2020.08.056)) - Fujisato, Hiroko; Ito, Masaya; Berking, Matthias; Horikoshi, Masaru (Journal of Affective Disorders, 2021)
The authors regret the errors in Table 4 of the original article. The t values and asterisks for “PTSS at baseline” and “PTSS four months later” were wrongly denoted. Please see the corrected table below. The authors would like to apologise for any inconvenience caused.
CRIS-Team Scopus Importer:2021-01-29

Declaring „war“ on stress: Preliminary results of a randomized controlled study investigating a speech-based approach-avoidance modification training targeting dysfunctional beliefs in individuals with elevated stress - Keinert, Eva Marie; Berking, Matthias (4. Deutscher Psychotherapie Kongress, 2025)

Deficits in general emotion regulation skills–Evidence of a transdiagnostic factor - Lukas, Christian; Ebert, David; Trevisi, Hugo; Caspar, Franz; Berking, Matthias (Journal of Clinical Psychology, 2018)
Objective: Deficits in emotion regulation (ER) skills are discussed as a transdiagnostic factor contributing to the development and maintenance of various mental disorders. However, systematic comparisons of a broad range of ER skills across diagnostic groups that are based on comparable definitions and measures of ER are still rare. Method: Therefore, we conducted two studies assessing a broad range of ER skills with the Emotion Regulation Skills Questionnaire in individuals meeting criteria for mental disorders (N-1=1448; N-2=137) and in a general population sample (N=214). Results: Consistent across the two studies, participants in the clinical samples reported lower general and lower specific ER skills than participants in the general population sample. Also consistent across the two studies, diagnostic subgroups of the clinical samples differed significantly with regard to general and specific ER skills. Conclusion: The studies provide evidence that deficits in ER are associated with various forms of psychopathology. However, mental disorders seem to differ with regard to how strongly they are linked to ER skills.
Keywords: mental disorders; emotion regulation; skills; psychopathology; transdiagnostic

Developing a digital assistive tool for dementia patients and their caregivers: A qualitative study on needs, potential functions, practical requirements, user acceptance, and ethical considerations - Wichmann, Lenka; Reiff, Nele; Zintl, Sophie; Berking, Matthias (AAIC 2021: Technology and Dementia Preconference, 2021)

Development and evaluation of an emotion regulation app - Böhme, Stephanie; Berking, Matthias (Prävention und Gesundheitsförderung, 2021)
Background Individuals with mental disorders have limited competence in dealing with difficult emotions. Berking (2017) provides a well-structured treatment manual to train emotional competencies across a broad range of mental disorders: Affect Regulation Training (ART). In studies, ART has been demonstrated to improve emotional competence and reduce symptom severity in patients with mental disorders. Due to the well-defined structure of ART, it is suitable for digital application. Objectives Among other goals, an ART app could bridge the gap between waiting lists and the initiation of treatment and also better exploit the potential of therapy-related exercises. Currently, there is a smartphone-based version of ART that can be complementarily used to provide support to ART group training. The long-term goal is to develop a complete standalone version of the ART app. Materials For this purpose, research findings will be implemented to address and minimize the hitherto problems of smartphone-based health promotion. Clinical trials will then be conducted to test the effectiveness of the ART app. Results Preliminary findings indicate that the ART training app is well-accepted by users when embedded in the group training. Results concerning effectiveness of the standalone version of the ART app are still pending. Conclusion The effectiveness of the ART app should be evaluated in individuals with mental disorders who are on treatment waiting lists and in the context of aftercare. In the long-term, the ART app is expected to benefit from the ongoing development of sensory technology and artificial intelligence and will enable the app to measure and provide feedback on biosignals of emotional processes.
CRIS-Team WoS Importer:2021-07-09

Die Entwicklung, Validierung und Reliabilität von Kurzformen gängiger psychometrischer Instrumente zur Evaluation des therapeutischen Fortschritts in Psychotherapie und Psychiatrie - Lutz, Wolfgang; Tholen, Sven; Schürch, Eva; Berking, Matthias (Diagnostica, 2006)
In recent years several scientist-practitioner networks and outcome management programs in behavioral health were established in order to improve clinical services in routine practice. In these programs and networks the use of a short but still multidimensional and change-sensitive outcome measure is crucial. In this article, we discuss the development of several short versions of currently widely used measures in German-speaking outpatient centres and mental health hospitals in order to make them more usable for continuous progress assessment (those are the Symptom-Checklist, SCL-90-R; the Inventory of Emotional Distress, EMI; the Inventory of Interpersonal Problems, IIP; and the Questionnaire of Incongruence, INK). Validity, reliability, and change-sensitivity of the short questionnaires were assessed on several datasets and results are reported (a community sample, n = 436; a sample of patients in outpatient psychotherapy, n = 169; and a sample of n = 134 patients in inpatient therapy). The psychometric characteristics as well as the resulting total score of general psychological distress admit the combined use of those instruments for outcomes management in routine care. © Hogrefe Verlag Göttingen 2006.
Created from Fastlane, Scopus look-up
Keywords: Change sensitivity; Quality assurance; Reliability and outcomes management with short questionnaires; Validity

Digital prevention of depression for farmers? A qualitative study on participants' experiences regarding determinants of acceptance and satisfaction with a tailored guided internet intervention program - Freund, Johanna; Buntrock, Claudia; Braun, Lina; Thielecke, Janika; Baumeister, Harald; Berking, Matthias; Ebert, David; Titzler, Ingrid (Internet Interventions, 2022)
Introduction: Farmers, forest workers and gardeners have a higher risk of developing depression compared to other occupational populations. As part of the German pilot project "With us in balance", the potential of six guided internet- and mobile-based interventions (IMIs) to prevent depression among their insurants is examined. The IMI program is tailored to various risk factors of depression, individual symptoms, and needs. Although IMIs have been shown to be effective in reducing depressive symptoms, there is little qualitative research about the acceptance of digital preventive IMIs. The aim of this qualitative study is to gain insights into participants' experiences with the guided IMIs by focusing on determinants for acceptance and satisfaction.
CRIS-Team WoS Importer:2022-09-02

Disgust-based approach-avoidance modification training for individuals suffering from elevated stress: A randomized controlled pilot study - Streit, Hannah; Keinert, Eva Marie; Rupp, Lydia; Schindler-Gmelch, Lena; Böhme, Stephanie; Eskofier, Björn; Schuller, Björn; Berking, Matthias (Kongress der Deutschen Gesellschaft für Verhaltensmedizin, 2022)

Disgust-based approach-avoidance modification training for individuals suffering from elevated stress: A randomized controlled pilot study - Streit, Hannah; Keinert, Eva Marie; Rupp, Lydia; Schindler-Gmelch, Lena; Böhme, Stephanie; Eskofier, Björn; Schuller, Björn W.; Berking, Matthias (52. Kongress der European Association for Behavioral and Cognitive Therapies, 2022)

Disgust-based approach-avoidance modification training for individuals suffering from elevated stress: A randomized controlled pilot study - Streit, Hannah; Keinert, Eva Marie; Schindler-Gmelch, Lena; Eskofier, Björn; Berking, Matthias (Stress and Health, 2024)
Perceived stress, a global health problem associated with various mental disorders, is assumed to be influenced by dysfunctional beliefs. It can be hypothesized that these beliefs can be modified with the help of approach-avoidance modification trainings (AAMTs). In the present study (conducted 2020–2022), we aimed to clarify whether the efficacy of AAMTs can be enhanced by utilizing the expression of emotions to move AAMT stimuli. For this purpose, we tested the feasibility and acceptability of a new AAMT paradigm in which the expression of disgust is used to move stress-increasing beliefs away from oneself and the expression of positive emotions is used to move stress-reducing beliefs towards oneself (AAMT-DP). Additionally, we explored the therapeutic potential of the AAMT-DP intervention by comparing it to an inactive control condition and to a conventional AAMT in which stimuli are moved by swipe movements (n = 10 in each condition). The primary outcome was perceived stress 1 week after the training as assessed with the Perceived Stress Scale. Findings indicate sufficient feasibility and acceptability of the intervention and that the decrease in perceived stress in the AAMT-DP condition was greater than in the inactive control condition (g = 0.72 [0.10, 1.72]) and than in the swipe control condition (g = 0.64 [0.01, 1.41]). In sum, findings provide preliminary evidence for the feasibility, acceptability, and the therapeutic potential of the AAMT-DP intervention.
CRIS-Team Scopus Importer:2024-03-08
Keywords: approach-avoidance modification training; disgust; emotions; smartphone-based intervention; stress

Does cognitive behaviour therapy have an enduring effect that is superior to keeping patients on continuation pharmacotherapy? A meta-analysis - Cuijpers, Pim; Hollon, Steven D.; Van Straten, Annemieke; Bockting, Claudi; Berking, Matthias; Andersson, Gerhard (BMJ Open, 2013)
Objectives: Although cognitive behaviour therapy (CBT) and pharmacotherapy are equally effective in the acute treatment of adult depression, it is not known how they compare across the longer term. In this meta-analysis, we compared the effects of acute phase CBT without any subsequent treatment with the effects of pharmacotherapy that either were continued or discontinued across 6-18 months of follow-up. Design: We conducted systematic searches in bibliographical databases to identify relevant studies, and conducted a meta-analysis of studies meeting inclusion criteria. Setting: Mental healthcare. Participants: Patients with depressive disorders. Interventions: CBT and pharmacotherapy for depression. Outcome measures: Relapse rates at long-term follow-up. Results: 9 studies with 506 patients were included. The quality was relatively high. Short-term outcomes of CBT and pharmacotherapy were comparable, although drop out from treatment was significantly lower in CBT. Acute phase CBT was compared with pharmacotherapy discontinuation during follow-up in eight studies. Patients who received acute phase CBT were significantly less likely to relapse than patients who were withdrawn from pharmacotherapy (OR=2.61, 95% CI 1.58 to 4.31, p<0.001; numbersneeded- to-be-treated, NNT=5). The acute phase CBT was compared with continued pharmacotherapy at follow-up in five studies. There was no significant difference between acute phase CBT and continued pharmacotherapy, although there was a trend (p<0.1) indicating that patients who received acute phase CBT may be less likely to relapse following acute treatment termination than patients who were continued on pharmacotherapy (OR=1.62, 95% CI 0.97 to 2.72; NNT=10). Conclusions: We found that CBT has an enduring effect following termination of the acute treatment. We found no significant difference in relapse after the acute phase CBT versus continuation of pharmacotherapy after remission. Given the small number of studies, this finding should be interpreted with caution pending replication.
Created from Fastlane, Scopus look-up

Does SMS-Support Make a Difference? Effectiveness of a Two-Week Online-Training to Overcome Procrastination. A Randomized Controlled Trial - Eckert, Marcus; Ebert, David; Lehr, Dirk; Sieland, Bernhard; Berking, Matthias (Frontiers in Psychology, 2018)
The primary purpose of this randomized controlled trial (RCT) was to evaluate the efficacy of an unguided, 2-week internet-based training program to overcome procrastination, called ON. TOP. Because adherence is a typical problem among individuals who tend to procrastinate, especially with internet-based interventions, the secondary purpose of the present study was to investigate whether adding SMS support increases subjects' frequency of engagement in training. In a three-armed RCT (N = 161), the effects of the intervention alone and intervention with daily SMS-support were compared to a waiting list control condition in a sample of students. The primary outcome of interest was procrastination. The secondary outcome of interest was the extent of training behavior. Baseline (T0), immediate post-treatment (T1) and 8-week post-treatment (T2) assessments were conducted. Results indicated that procrastination decreased significantly only with intervention group with daily SMS support, relative to control. Moreover, incorporating SMS support also may enhance extent of training behavior.
Keywords: procrastination; online-training; SMS support; adherence; Rubicon model

Do guided internet-based interventions result in clinically relevant changes for patients with depression? An individual participant data meta-analysis. - Karyotaki, Eirini; Ebert, David; Donkin, Liesje; Riper, Heleen; Twisk, Jos; Burger, Simone; Rozental, Alexander; Lange, Alfred; Williams, Alishia D.; Zarski, Anna-Carlotta; Geraedts, Anna; Van Straten, Annemieke; et al. (Clinical Psychology Review, 2018)
Little is known about clinically relevant changes in guided Internet-based interventions for depression. Moreover, methodological and power limitations preclude the identification of patients' groups that may benefit more from these interventions. This study aimed to investigate response rates, remission rates, and their moderators in randomized controlled trials (RCTs) comparing the effect of guided Internet-based interventions for adult depression to control groups using an individual patient data meta-analysis approach. Literature searches in PubMed, Embase, PsycINFO and Cochrane Library resulted in 13,384 abstracts from database inception to January 1, 2016. Twenty-four RCTs (4889 participants) comparing a guided Internet-based intervention with a control group contributed data to the analysis. Missing data were multiply imputed. To examine treatment outcome on response and remission, mixed-effects models with participants nested within studies were used. Response and remission rates were calculated using the Reliable Change Index. The intervention group obtained significantly higher response rates (OR = 2.49, 95% CI 2.17-2.85) and remission rates compared to controls (OR = 2.41, 95% CI 2.07-2.79). The moderator analysis indicated that older participants (OR = 1.01) and native-born participants (1.66) were more likely to respond to treatment compared to younger participants and ethnic minorities respectively. Age (OR = 1.01) and ethnicity (1.73) also moderated the effects of treatment on remission.Moreover, adults with more severe depressive symptoms at baseline were more likely to remit after receiving internet-based treatment (OR = 1.19). Guided Internet-based interventions lead to substantial positive treatment effects on treatment response and remission at post-treatment. Thus, such interventions may complement existing services for depression and potentially reduce the gap between the need and provision of evidence-based treatments.

Do Nonsuicidal Severely Depressed Individuals with Diabetes Profit from Internet-Based Guided Self-Help? Secondary Analyses of a Pragmatic Randomized Trial - Schlicker, Sandra; Weisel, Kiona; Buntrock, Claudia; Berking, Matthias; Nobis, Stephanie; Lehr, Dirk; Baumeister, Harald; Snoek, Frank J.; Riper, Heleen; Ebert, David (Journal of Diabetes Research, 2019)

DSM-IV und DSM-5: Was hat sich tatsächlich verändert? - Ehret, Anna M.; Berking, Matthias (Verhaltenstherapie, 2013)
The fifth edition of the American Psychiatric Association's Diagnostic and Statistical Manual of Mental Disorders (DSM-5) was published in May 2013. To enable researchers and practitioners to appropriately evaluate and account for advantages and disadvantages, both groups should be informed about amendments to the previous version DSM-IV. In the present paper, we describe the main differences between DSM-IV and DSM-5. Major changes in the overall structure include the discontinuation of the multiaxial system and the revised order of categories. On the level of specific disorders, main differences include the introduction of Major and Mild Neurocognitive Disorders, the extinction of bereavement as an exclusion criterion for Major Depressive Disorder, and the inclusion of Agoraphobia as a distinct disorder. Further additional diagnoses in DSM-5 include Binge-Eating Disorder, Premenstrual Dysphoric Disorder, Disruptive Mood Dysregulation Disorder, Hoarding Disorder, Excoriation (Skin Picking) Disorder, and Caffeine Withdrawal. Categories no longer included in the DSM-5 include Sexual Aversion Disorder and Undifferentiated Somatoform Disorder. Finally, for almost all disorders diagnostic criteria were slightly modified and nosological information was updated. When evaluating the revision, the multiple purposes of the DSM-5 have to be taken into account. As many of these purposes are in conflict or even mutually exclusive, controversial discussions of the new edition by the various interest groups are to be expected.
Created from Fastlane, Scopus look-up
Keywords: Classification systems; Diagnostics; DSM-5; DSM-IV; Mental disorders

Economic Evaluation of an Internet-Based Stress Management Intervention Alongside a Randomized Controlled Trial - Kählke, Fanny; Buntrock, Claudia; Smit, Filip; Berking, Matthias; Lehr, Dirk; Heber, Elena; Funk, Burkhardt; Riper, Heleen; Ebert, David (JMIR Mental Health, 2019)
Background: Work-related stress is widespread among employees and associated with high costs for German society. Internet-based stress management interventions (iSMIs) are effective in reducing such stress. However, evidence for their cost-effectiveness is scant.
CRIS-Team WoS Importer:2019-06-18

Effectiveness and cost-effectiveness of a guided internet- and mobile-based depression intervention for individuals with chronic back pain: protocol of a multi-centre randomised controlled trial - Lin, Jiaxi; Sander, Lasse; Paganini, Sarah; Schlicker, Sandra; Ebert, David; Berking, Matthias; Bengel, Juergen; Nobis, Stephanie; Lehr, Dirk; Mittag, Oskar; Riper, Heleen; Baumeister, Harald (BMJ Open, 2017)
Introduction Depression often co-occurs with chronic back pain (CBP). Internet and mobile-based interventions (IMIs) might be a promising approach for effectively treating depression in this patient group. In the present study, we will evaluate the effectiveness and cost-effectiveness of a guided depression IMI for individuals with CBP (eSano BackCare-D) integrated into orthopaedic healthcare.Methods and analysis In this multicentre randomised controlled trial of parallel design, the groups eSano BackCare-D versus treatment as usual will be compared. 210 participants with CBP and diagnosed depression will be recruited subsequent to orthopaedic rehabilitation care. Assessments will be conducted prior to randomisation and 9 weeks (post-treatment) and 6 months after randomisation. The primary outcome is depression severity (Hamilton Rating Scale for Depression-17). Secondary outcomes are depression remission and response, health-related quality of life, pain intensity, pain-related disability, self-efficacy and work capacity. Demographic and medical variables as well as internet affinity, intervention adherence, intervention satisfaction and negative effects will also be assessed. Data will be analysed on an intention-to-treat basis with additional per-protocol analyses. Moreover, a cost-effectiveness and cost-utility analysis will be conducted from a societal perspective after 6 months.Ethics and dissemination All procedures are approved by the ethics committee of the Albert-Ludwigs-University of Freiburg and the data security committee of the German Pension Insurance (Deutsche Rentenversicherung). The results will be published in peer-reviewed journals and presented on international conferences.

Effectiveness and Moderators of an Internet-Based Mobile-Supported Stress Management Intervention as a Universal Prevention Approach: Randomized Controlled Trial - Ebert, David Daniel; Franke, Marvin; Zarski, Anna-Carlotta; Berking, Matthias; Riper, Heleen; Cuijpers, Pim; Funk, Burkhardt; Lehr, Dirk (Journal of Medical Internet Research, 2021)
Background: Emerging evidence indicates the effectiveness of internet-based mobile-supported stress management interventions (iSMIs) in highly stressed employees. It is yet unclear, however, whether iSMIs are also effective without a preselection process in a universal prevention approach, which more closely resembles routine occupational health care. Moreover, evidence for whom iSMIs might be suitable and for whom not is scarce.
CRIS-Team WoS Importer:2022-01-21

Effectiveness of a guided multicomponent internet and mobile gratitude training program - A pragmatic randomized controlled trial - Lehr, Dirk; Freund, Henning; Sieland, Bernhard; Kalon, Lina; Berking, Matthias; Riper, Heleen; Ebert, David Daniel (Internet Interventions, 2024)
Objective: To investigate the effectiveness of a guided, internet- and smartphone-based gratitude intervention on the transdiagnostic risk-factor ‘repetitive negative thinking’. The multicomponent intervention integrates a variety of gratitude exercises, targeting the cognitive, emotional and behavioural facets of gratitude. Method: Two hundred adults with pronounced repetitive negative thinking were recruited from the general population. Participants were randomly assigned to either a four-session guided gratitude intervention (n = 100) or waiting list (n = 100). The primary outcome was repetitive negative thinking three months after randomization, with exploratory assessments at six weeks and six months, the latter just for participants in the intervention group. Results: Following the intention-to-treat principle, by analyses of covariance (ANCOVA), the gratitude intervention group exhibited significantly lower levels of repetitive negative thinking than controls at three months, with d = 0.66, 95 % CI [0.37, 0.94] maintained at six-month follow-up. Significant and meaningful beneficial effects were observed in symptoms of depression (d = 0.42) and generalized anxiety (d = 0.38). These effects were notably stronger in intervention completers who finished at least three sessions. Conclusions: Results suggest that a multicomponent gratitude intervention is effective at reducing repetitive negative thinking. Multicomponent interventions may be a next step needed to fully realize the potential of gratitude interventions. Such interventions could expand the repertoire of transdiagnostic interventions, especially for repetitive negative thinking. Furthermore, due to its positive connotations, gratitude is a candidate for an indirect intervention aimed at reducing the burden of depression in the general population. Trial registration: The study is registered in the German Clinical Trial Register (approved primary register of the WHO) as DRKS00006825. The trial protocol can be assessed at: https://www.drks.de/
CRIS-Team Scopus Importer:2024-11-22
Keywords: Gratitude; Internet and mobile intervention; Positive psychology; Repetitive negative thinking; Transdiagnostic

Effectiveness of an Internet- and App-Based Intervention for College Students With Elevated Stress: Randomized Controlled Trial - Harrer, Mathias; Adam, Sophia; Fleischmann, Rebecca Jessica; Baumeister, Harald; Auerbach, Randy; Bruffaerts, Ronny; Cuijpers, Pim; Kessler, Ronald C.; Berking, Matthias; Lehr, Dirk; Ebert, David (Journal of Medical Internet Research, 2018)
Background: Mental health problems are highly prevalent among college students. Most students with poor mental health, however, do not receive professional help. Internet-based self-help formats may increase the utilization of treatment.Objective: The aim of this randomized controlled trial was to evaluate the efficacy of an internet-based, app-supported stress management intervention for college students.Methods: College students (n=150) with elevated levels of stress (Perceived Stress Scale 4-item version, PSS-4 >= 8) were randomly assigned to either an internet- and mobile-based stress intervention group with feedback on demand or a waitlist control group. Self-report data were assessed at baseline, posttreatment (7 weeks), and 3-month follow-up. The primary outcome was perceived stress posttreatment (PSS-4). Secondary outcomes included mental health outcomes, modifiable risk and protective factors, and college-related outcomes. Subgroup analyses were conducted in students with clinically relevant symptoms of depression (Center for Epidemiological Studies' Depression Scale >17).Results: A total of 106 participants (76.8%) indicated that they were first-time help-seekers, and 77.3% (intervention group: 58/75; waitlist control group: 58/75) showed clinically relevant depressive symptoms at baseline. Findings indicated significant effects of the intervention compared with the waitlist control group for stress (d=0.69; 95% CI 0.36-1.02), anxiety (d=0.76; 95% CI 0.43-1.09), depression (d=0.63; 95% CI 0.30-0.96), college-related productivity (d=0.33; 95% CI 0.01-0.65), academic work impairment (d=0.34; 95% CI 0.01-0.66), and other outcomes after 7 weeks (posttreatment). Response rates for stress symptoms were significantly higher for the intervention group (69%, 52/75) compared with the waitlist control group (35%, 26/75, P<.001; number needed to treat=2.89, 95% CI 2.01-5.08) at posttest (7 weeks). Effects were sustained at 3-month follow-up, and similar findings emerged in students with symptoms of depression.Conclusions: Internet-and mobile-based interventions could be an effective and cost-effective approach to reduce consequences of college-related stress and might potentially attract students with clinically relevant depression who would not otherwise seek help.
Keywords: randomized controlled trial; stress; psychological; depression; telemedicine; students; help-seeking behavior

Effectiveness of a Web-based Cognitive Behavioral Intervention for the Prevention of Depression: Pragmatic Randomized Controlled Trial - Buntrock, Claudia; Ebert, David; Lehr, Dirk; Heleen, Riper; Smit, Filip; Berking, Matthias; Cuijpers, Pim (JAMA Psychiatry, 2017)

Effectiveness of a Web-Based Cognitive Behavioural Intervention for Subthreshold Depression: Pragmatic Randomised Controlled Trial - Buntrock, Claudia; Smit, Filip; Ebert, David; Lehr, Dirk; Heleen, Riper; Cuijpers, Pim; Berking, Matthias (Psychotherapy and Psychosomatics, 2015)
Background: Research on the effectiveness of treatments for subthreshold depression (sD) is still scarce. The aim of the study was to evaluate the efficacy of a web-based guided self-help intervention (GET. ON Mood Enhancer) in the treatment of sD. Methods: Participants with sD (n = 406) recruited from the general population via a large health insurance company were randomly allocated to a web-based cognitive behavioural intervention or to enhanced care-as-usual. The primary outcome was the reduction in depressive symptom severity as measured with the Center for Epidemiological Studies Depression Scale at post-treatment and at 6-month follow-up. Results: Participants in the intervention group showed a significantly greater pre-post reduction in depressive symptom severity (d = 1.06; 95% CI: 0.86-1.27) compared to the control condition (d = 0.29; 95% CI: 0.10-0.49). The corresponding between-group effect size was d = 0.69 (95% CI: 0.49-0.89). At 6-month follow-up the effect was reduced to d = 0.28 (95% CI: 0.09-0.48) but was still statistically significant (F-1,F-403 = 9.240, p = 0.003). Conclusions: This study lends support to the idea that problem solving coupled with behavioural activation is an effective treatment for sD. In addition, the delivery of this intervention over the Internet might be a promising strategy for the dissemination of psychological interventions for sD on a large scale. (C) 2015 S. Karger AG, Basel
Keywords: Subthreshold depression; Treatment; Psychological intervention; Cognitive behavioural intervention; Web-based guided self-help; Randomised controlled trial

Effectiveness of Web- and Mobile-Based Treatment of Subthreshold Depression With Adherence-Focused Guidance: A Single-Blind Randomized Controlled Trial - Ebert, David; Buntrock, Claudia; Lehr, Dirk; Smit, Filip; Riper, Heleen; Baumeister, Harald; Cuijpers, Pim; Berking, Matthias (Behavior Therapy, 2018)
Evidence for the impact of psychological Interventions for subthreshold depression (sD) is conflicting. Moreover, human resources to deliver such treatments are limited. This study aimed to evaluate the effectiveness of a web-based intervention with adherence-focused guidance in the treatment of sD. Participants with sD (CES-D. ≥ 16, no Major Depressive Disorder according to DSM-IV criteria, N = 204) recruited via a large health insurance were randomly allocated to a web-based mobile-supported cognitive-behavioral intervention or to a waitlist control condition with unrestricted access to usual care. The primary outcome was the reduction in depressive symptom severity as measured by blind diagnostic raters using the Quick Inventory of Depressive Symptomatology (QIDS) at posttreatment. There was a statistically significant between-group difference in QIDS scores at posttreatment in favor of the intervention group, F(1, 201) = 11.31, p = .001, corresponding to a medium effect size of d = 0.37 (95% CI 0.09-0.64) and a NNT of 7 (95%-CI 3.7-41.2). Significant effects in favour of the intervention group were also found for secondary outcomes such as quality of life, anxiety, and insomnia severity. Web-based self-help interventions with adherence-focused guidance could be an acceptable and effective approach to reduce a range of negative consequences associated with subclinical depressio
Keywords: Clinician-rated; Minor depression; Subthreshold depression; Web-based intervention

Effect of a web-based guided self-help intervention for prevention of major depression in adults with subthreshold depression a randomized clinical trial - Buntrock, Claudia; Ebert, David; Lehr, Dirk; Smit, Filip; Riper, Heleen; Berking, Matthias; Cuijpers, Pim (Journal of the American Medical Association, 2016)
Importance Evidence-based treatments for major depressive disorder (MDD) are not very successful in improving functional and health outcomes. Attention has increasingly been focused on the prevention of MDD. OBJECTIVE To evaluate the effectiveness of a web-based guided self-help intervention for the prevention of MDD. DESIGN, SETTING, AND PARTICIPANTS Two-group randomized clinical trial conducted between March 1, 2013, and March 4, 2015. Participants were recruited in Germany from the general population via a large statutory health insurance company (ie, insurance funded by joint employer-employee contributions). Participants included 406 self-selected adults with subthreshold depression (Centre for Epidemiologic Studies Depression Scale score≥16, no current MDD according to Diagnostic and Statistical Manual of Mental Disorders [Fourth Edition, Text Revision] criteria). INTERVENTIONS All participants had unrestricted access to usual care (visits to the primary care clinician) and were randomized to either a web-based guided self-help intervention (cognitive-behavioral and problem-solving therapy supported by an online trainer; n = 202) or a web-based psychoeducation program (n = 204). MAIN OUTCOMES AND MEASURES The primary outcome was time to onset of MDD in the intervention group relative to the control group over a 12-month follow-up period as assessed by blinded diagnostic raters using the telephone-administered Structured Clinical Interview for DSM-IV Axis Disorders at 6-and 12-month follow-up, covering the period to the previous assessment. RESULTS Among 406 randomized patients (mean age, 45 years; 73.9%women), 335 (82%) completed the telephone follow-up at 12 months. Fifty-five participants (27%) in the intervention group experienced MDD compared with 84 participants (41%) in the control group. Cox regression analyses controlling for baseline depressive symptom severity revealed a hazard ratio of 0.59 (95%CI, 0.42-0.82; P =.002) at 12-month follow-up. The number needed to treat to avoid 1 new case of MDD was 5.9 (95%CI, 3.9-14.6). CONCLUSIONS AND RELEVANCE Among patients with subthreshold depression, the use of a web-based guided self-help intervention compared with enhanced usual care reduced the incidence of MDD over 12 months. Further research is needed to understand whether the effects are generalizable to both first onset of depression and depression recurrence as well as efficacy without the use of an online trainer.

Effect of a Web-Based Guided Self-Help Intervention for Prevention of Major Depression in Adults with Subthreshold Depression: A Randomized Clinical Trial - Buntrock, Claudia; Ebert, David; Lehr, Dirk; Smit, Filip; Riper, Heleen; Berking, Matthias; Cuijpers, Pim (Obstetrical and Gynecological Survey, 2016)

Effects of Emotion Regulation Skills on Abstinence after Inpatient Treatment for Alcohol Use Disorder: A Latent Difference Score Analysis - Rupp, Lydia; Saur, Sebastian; Berking, Matthias (3. Deutscher Psychotherapiekongress (DPK), 2024)
Theoretischer Hintergrund: Alcohol use disorder (AUD) is a debilitating mental health problem, frequently developing into a chronic disorder (McKay & Hiller-Sturmhofel, 2011). While behavioral and cognitive treatments have been proven to be effective treatment approaches (Witkiewitz et al., 2019), barriers to adequate aftercare may increase risk for relapse and, thus, chronic development of the disorder (Buchholz et al., 2019). Therefore, understanding the mechanisms contributing to relapse risk may inform the development of effective aftercare and prevention strategies. A promising factor are emotion regulation skills, which have been shown to predict abstinence after psychotherapy for AUD (Berking et al., 2012). Fragestellung: Can emotion regulation skills predict abstinence in individuals with AUD after inpatient treatment? Methoden: We will use data of n = 356 individuals with AUD from a large randomized controlled trial on aftercare after inpatient treatment for AUD (Saur et al., 2022). AUD was diagnosed using the Structured Clinical Interview for DSM-5 Disorders-Clinician Version (First et al., 2016). Emotion regulation skills were assessed with the German version of the Emotion Regulation Skills Questionnaire (Berking & Znoj, 2008). Relapse and abstinence were assessed with the Timeline Follow-Back Alcohol interview (Sobell & Sobell, 1992). Outcomes were assessed before aftercare treatment (T1), mind-intervention (T2), six weeks after randomization (T3), and three (T4) and six months after randomization (T5). Data will be analysed using a Latent Difference Score approach (Hamagami & McArdle, 2001) to assess effects of emotion regulation skills on abstinence over time. Ergebnisse: Data analysis is underway and results will be presented. Diskussion: This analysis will build on and extend previous findings on the effects of emotion regulation skills on abstinence (Berking et al., 2012). We will replicate the results using a larger sample and a different analysis approach. The findings may help to develop more tailored and effective strategies for relapse prevention in AUD. This study addresses the limitations of the previous study (Berking et al., 2012) by including an untreated control group and using a standardized clinical interview for the diagnosis of AUD

Effects of Internet-Based Cognitive Behavioral Therapy in Routine Care for Adults in Treatment for Depression and Anxiety: Systematic Review and Meta-Analysis - Etzelmueller, Anne; Vis, Christiaan; Karyotaki, Eirini; Baumeister, Harald; Titov, Nickolai; Berking, Matthias; Cuijpers, Pim; Riper, Heleen; Ebert, David (Journal of Medical Internet Research, 2020)
BACKGROUND: Although there is evidence for the efficacy of internet-based cognitive behavioral therapy (iCBT), the generalizability of results to routine care is limited. OBJECTIVE: This study systematically reviews effectiveness studies of guided iCBT interventions for the treatment of depression or anxiety. METHODS: The acceptability (uptake, participants' characteristics, adherence, and satisfaction), effectiveness, and negative effects (deterioration) of nonrandomized pre-post designs conducted under routine care conditions were synthesized using systematic review and meta-analytic approaches. RESULTS: A total of 19 studies including 30 groups were included in the analysis. Despite high heterogeneity, individual effect sizes of investigated studies indicate clinically relevant changes, with effect sizes ranging from Hedges' g=0.42-1.88, with a pooled effect of 1.78 for depression and 0.94 for anxiety studies. Uptake, participants' characteristics, adherence, and satisfaction indicate a moderate to high acceptability of the interventions. The average deterioration across studies was 2.9%. CONCLUSIONS: This study provides evidence supporting the acceptability and effectiveness of guided iCBT for the treatment of depression and anxiety in routine care. Given the high heterogeneity between interventions and contexts, health care providers should select interventions that have been proven in randomized controlled clinical trials. The successful application of iCBT may be an effective way of increasing health care in multiple contexts.
CRIS-Team Scopus Importer:2020-10-16
Keywords: acceptability; anxiety; depression; effectiveness; internet-based interventions; routine care

Efficacy and cost-effectiveness of a web-based and mobile stress-management intervention for employees: Design of a randomized controlled trial - Heber, Elena; Ebert, David Daniel; Lehr, Dirk; Nobis, Stephanie; Berking, Matthias; Riper, Heleen (BMC Public Health, 2013)
Background: Work-related stress is associated with a variety of mental and emotional problems and can lead to substantial economic costs due to lost productivity, absenteeism or the inability to work. There is a considerable amount of evidence on the effectiveness of traditional face-to-face stress-management interventions for employees; however, they are often costly, time-consuming, and characterized by a high access threshold. Web-based interventions may overcome some of these problems yet the evidence in this field is scarce. This paper describes the protocol for a study that will examine the efficacy and cost-effectiveness of a web-based guided stress-management training which is based on problem solving and emotion regulation and aimed at reducing stress in adult employees. Methods. The study will target stressed employees aged 18 and older. A randomized controlled trial (RCT) design will be applied. Based on a power calculation of d=.35 (1-β of 80%, α =.05), 264 participants will be recruited and randomly assigned to either the intervention group or a six-month waitlist control group. Inclusion criteria include an elevated stress level (Cohen's Perceived Stress Scale-10 ≥ 22) and current employment. Exclusion criteria include risk of suicide or previously diagnosed psychosis or dissociative symptoms. The primary outcome will be perceived stress, and secondary outcomes include depression and anxiety. Data will be collected at baseline and seven weeks and six months after randomization. An extended follow up at 12 months is planned for the intervention group. Moreover, a cost-effectiveness analysis will be conducted from a societal perspective and will include both direct and indirect health care costs. Data will be analyzed on an intention-to-treat basis and per protocol. Discussion. The substantial negative consequences of work-related stress emphasize the necessity for effective stress-management trainings. If the proposed internet intervention proves to be (cost-) effective, a preventative, economical stress-management tool will be conceivable. The strengths and limitations of the present study are discussed. Trial registration. German Register of Clinical Studies (DRKS): DRKS00004749. © 2013 Heber et al.; licensee BioMed Central Ltd.
Created from Fastlane, Scopus look-up
Keywords: Cost-effectiveness; Depression; Efficacy; Internet intervention; Occupational health; Prevention; Stress management; Work-related stress

Efficacy and cost-effectiveness of a web-based intervention with mobile phone support to treat depressive symptoms in adults with diabetes mellitus type 1 and type 2: Design of a randomised controlled trial - Nobis, Stephanie; Lehr, Dirk; Ebert, David D.; Berking, Matthias; Heber, Elena; Baumeister, Harald; Becker, Annette; Snoek, Frank; Riper, Heleen (BMC Psychiatry, 2013)
Background: A diagnosis of diabetes mellitus types 1 or 2 doubles the odds of a comorbid depressive disorder. The combined diseases have a wide range of adverse outcomes, such as a lower quality of life, poorer diabetes outcomes and increased healthcare utilisation. Diabetes patients with depression can be treated effectively with psychotherapy, but access to psychological care is limited. In this study we will examine the efficacy and cost-effectiveness of a newly developed web-based intervention (GET.ON Mood Enhancer Diabetes) for people with diabetes and comorbid depressive symptoms.Methods/Design: A two-arm randomised controlled trial will be conducted. Adults with diabetes (type 1 or type 2) with increased depression scores (> 22 on the German version of the Center for Epidemiological Studies Depression Scale (CES-D)) will be included. Eligible participants will be recruited through advertisement in diabetes patient journals and via a large-scale German health insurance company. The participants will be randomly assigned to either a 6-week minimally guided web-based self-help program or an online psychoeducation program on depression. The study will include 260 participants, which will enable us to detect a statistically significant difference with a group effect size of d = 0.35 at a power of 80% and a significance level of p = 0.05. The primary outcome measure will be the level of depression as assessed by the CES-D. The secondary outcome measures will be: diabetes-specific emotional distress, glycaemic control, self-management behaviour and the participants' satisfaction with the intervention. Online self-assessments will be collected at baseline and after a 2 months period, with additional follow-up measurements 6 and 12 months after randomisation. The data will be analysed on an intention-to-treat basis and per protocol. In addition, we will conduct an economic evaluation from a societal perspective.Discussion: If this intervention is shown to be cost-effective, it has considerable potential for implementing psychological care for large numbers of people with diabetes and comorbid depression in routine practice and improve health outcomes.Trial registration: German Clinical Trial Register (DRKS): DRKS00004748. © 2013 Nobis et al.; licensee BioMed Central Ltd.
Created from Fastlane, Scopus look-up
Keywords: Cost-effectiveness; Depression; Diabetes; Efficacy; Guided web-based self-help; Internet; Randomised controlled trial

Efficacy and cost-effectiveness of guided and unguided internet- and mobile-based indicated transdiagnostic prevention of depression and anxiety (ICare Prevent): A three-armed randomized controlled trial in four European countries - Weisel, Kiona; Zarski, Anna-Carlotta; Berger, Thomas; Krieger, Tobias; Schaub, Michael P.; Moser, Christian T.; Berking, Matthias; Dey, Michelle; Botella, Cristina; Banos, Rosa; Herrero, Rocio; Etchemendy, Ernestina; et al. (Internet Interventions, 2019)
Background: Depression and anxiety are highly prevalent and often co-occur. Several studies indicate the potential of disorder-specific psychological interventions for the prevention of each of these disorders. To treat comorbidity, transdiagnostic treatment concepts seem to be a promising approach, however, evidence for transdiagnostic concepts of prevention remains inconclusive. Internet-and mobile-based interventions (IMIs) may be an effective means to deliver psychological interventions on a large scale for the prevention of common mental disorders (CMDs) such as depression and anxiety. IMIs have been shown to be effective in treating CMDs, e.g. in reducing symptoms of depression and anxiety. However, there is a lack of studies examining the efficacy of interventions reducing the incidence of CMDs. Moreover, the comparative cost-effectiveness of guided versus unguided IMIs for the prevention of depression and anxiety has not been studied yet. Hence, this study aims at investigating the (cost-) effectiveness of guided and unguided internet-and mobile-based transdiagnostic individually tailored indicated prevention of depression and anxiety.Methods: A multi-country three-armed randomized controlled trial will be conducted to compare a guided and unguided intervention to treatment as usual (TAU). Both active conditions are based on the same intervention, ICare Prevent, and differ only with regard to guidance format. Altogether, 954 individuals with subclinical symptoms of depression (CES-D >= 16) and anxiety (GAD-7 >= 5) who do not have a full-blown disorder will be recruited in Germany, Switzerland, Spain and the Netherlands, and randomized to one of three conditions (guided intervention, unguided intervention, or TAU). The TAU arm will receive access to the training after a 12-month waiting period. The primary outcome will be time to CMD onset (any depression/anxiety disorder) within a follow-up period of 12 months after baseline. Secondary outcomes will include disorder-specific symptom severity (depression/anxiety) assessed by diagnostic raters blinded to intervention condition at post-intervention, self-reports, acceptability, health related quality of life, and psychosocial variables associated with developing a CMD. Assessments will take place at baseline, mid-intervention (5 weeks into the intervention), post- intervention (8 weeks after randomization) and follow-up (6 and 12 months after randomization). Data will be analyzed on an intention-to-treat basis and per protocol. Cost-effectiveness will be evaluated from a public health and a societal perspective, including both direct and indirect costs.Discussion: The present study will further enhance the evidence-base for transdiagnostic preventive interventions and provide valuable information about optimal trade-off between treatment outcome and costs. Trial registration: German Clinical Trial Registration (DRKS - http://www.drks.de/drks_web/): DRKS00011099.
Keywords: Prevention; Transdiagnostic; Depression; Anxiety; Internet-based; Randomized controlled trial

Efficacy and cost-effectiveness of minimal guided and unguided internet-based mobile supported stress-management in employees with occupational stress: a three-armed randomised controlled trial - Ebert, David; Lehr, Dirk; Smit, Filip; Zarski, Anna-Carlotta; Heleen, Riper; Heber, Elena; Cuijpers, Pim; Berking, Matthias (BMC Public Health, 2014)
Discussion: Online-based (guided) self-help interventions could be an acceptable, effective and economically sustainable approach to offer evidence-based intervention alternatives to reduce the negative consequences associated with work-related stress. This study evaluates the (cost-) effectiveness of two versions of an iSMI, minimal guided and unguided iSMI. Thus, the present study will further enhance the evidence-base for iSMI and provide valuable information about the optimal balance between outcome and economic costs.
Keywords: Guided self-help; Unguided self-help; Occupational health; Stress management; Internet-based; Randomised controlled trial; Cost-effectiveness

Efficacy of a hybrid online training for panic symptoms and agoraphobia: study protocol for a randomized controlled trial - Ebenfeld, Lara; Stegemann, Stefan Kleine; Lehr, Dirk; Ebert, David Daniel; Jazaieri, Hooria; Van Ballegooijen, Wouter; Funk, Burkhardt; Riper, Heleen; Berking, Matthias (Trials, 2014)
Discussion: To our knowledge, this RCT is one of the first to examine the efficacy of a hybrid online training for adult PD. This study seeks to contribute to the emerging field of hybrid online training. If the intervention is efficacious, then research on this hybrid online training should be extended. The cost-effectiveness analysis will also indicate whether online training is an economical tool for treating PD among adults.
Keywords: Panic disorder; Agoraphobia; Sub-clinical; Internet; Mobile; Smartphone; Hybrid

Efficacy of an Internet- and Mobile-Based Intervention for Subclinical Anxiety and Depression (ICare Prevent) with Two Guidance Formats: Results from a Three-Armed Randomized Controlled Trial - Zarski, Anna Carlotta; Weisel, Kiona; Berger, Thomas; Krieger, Tobias; Schaub, Michael P.; Berking, Matthias; Görlich, Dennis; Jacobi, Corinna; Ebert, David D. (Psychotherapy and Psychosomatics, 2024)
Introduction: Limited research exists on intervention efficacy for comorbid subclinical anxiety and depressive disorders, despite their common co-occurrence. Internet- and mobile-based interventions (IMIs) are promising to reach individuals facing subclinical symptoms. Objective: This study aimed to evaluate the efficacy of a transdiagnostic and self-tailored IMI in reducing subclinical anxiety and depressive symptom severity with either individualized (IG-IMI) or automated (AG-IMI) guidance compared to a waitlist control group with care-as-usual access (WLC). Methods: Participants included 566 adults with subclinical anxiety (GAD-7 ≥ 5) and/or depressive (CES-D ≥16) symptoms, who did not meet criteria for a full-syndrome depressive or anxiety disorder. In a three-arm randomized clinical trial, participants were randomized to a cognitive behavioral 7-session IMI plus booster session with IG-IMI (n = 186) or AG-IMI (n = 189) or WLC (n = 191). Primary outcomes included observer-rated anxiety (HAM-A) and depressive (QIDS) symptom severity 8 weeks after randomization assessed by blinded raters via telephone. Follow-up outcomes at 6 and 12 months are reported. Results: Symptom severity was significantly lower with small to medium effects in IG-IMI (anxiety: d = 0.45, depression: d = 0.43) and AG-IMI (anxiety: d = 0.31, depression: d = 0.32) compared to WLC. No significant differences emerged between guidance formats in primary outcomes. There was a significant effect in HAM-A after 6 months favoring AG-IMI. On average, participants completed 85.38% of IG-IMI and 77.38% of AG-IMI. Conclusions: A transdiagnostic, self-tailored IMI can reduce subclinical anxiety and depressive symptom severity, but 12-month long-term effects were absent. Automated guidance holds promise for enhancing the scalability of IMIs in broad prevention initiatives.
CRIS-Team Scopus Importer:2024-05-24
Keywords: Internet intervention; Subclinical anxiety; Subclinical depression; Subthreshold disorders; Transdiagnostic prevention

Efficacy of an internet-based problem-solving training for teachers: results of a randomized controlled trial - Ebert, David; Lehr, Dirk; Boss, Leif; Riper, Heleen; Cuijpers, Pim; Andersson, Gerhard; Thiart, Hanne; Heber, Elena; Berking, Matthias (Scandinavian Journal of Work Environment & Health, 2014)
Conclusion iPST is effective in reducing symptoms of depression among teachers. Disseminated on a large scale, iPST could contribute to reducing the burden of stress-related mental health problems among teachers. Future studies should evaluate iPST approaches for use in other working populations.
Keywords: depression; depressive symptom; mental health; occupational health; RCT; web-based

Efficacy of an internet-based self-help intervention to reduce co-occurring alcohol misuse and depression symptoms in adults: Study protocol of a three-arm randomised controlled trial - Schaub, Michael P.; Blankers, Matthijs; Lehr, Dirk; Boss, Leif; Riper, Heleen; Dekker, Jack; Goudriaan, Anna E.; Maier, Larissa J.; Haug, Severin; Amann, Manuel; Dey, Michelle; Wenger, Andreas; et al. (BMJ Open, 2016)
Introduction: In the general population, alcohol use disorder and depression more often occur together than any other combination of a mental illness with a substance use disorder. It is important to have a cost-effective intervention that is able to reach at-risk individuals in the early stages of developing alcohol use disorders and depression disorders. Methods and analysis: This paper presents the protocol for a 3-arm multicentre randomised controlled trial (RCT) to test the efficacy and cost-effectiveness of the combined internet-based self-help intervention Take Care of You (TCOY) to reduce alcohol misuse and depression symptoms in comparison with a waiting list control group and a comparable intervention focusing on problematic alcohol use only. The active interventions consist of modules designed to reduce alcohol use, based on the principles of motivational interviewing and methods of cognitive behavioural therapy, together with additional modules in the combined study arm to reduce symptoms of depression. Data will be collected at baseline, as well as at 3 and 6 months postrandomisation. The primary outcome is the quantity of alcohol used in the past 7 days. A number of secondary outcome measures will be studied. These include the Centre of Epidemiologic Studies of Depression Scale (CES-D) and a combined measure with the criteria of values below the cut-off for severe alcohol use disorder and for CES-D. Data analysis will follow the intention-to-treat principle using (generalised) linear mixed models. In order to investigate the interventions' cost-utility and cost-effectiveness, a full economic evaluation will be performed. Ethics and dissemination: This RCT will be executed in compliance with the Helsinki Declaration and has been approved by 2 local Ethics Committees. Results will be reported at conferences and in peer-reviewed publications. Participant-friendly summaries of trial findings will be published on the TCOY websites. Trial registration number: ISRCTN10323951.

Efficacy of an unguided internet-based self-help intervention for social anxiety disorder in university students: A randomized controlled trial. - Kählke, Fanny; Berger, Thomas; Schulz, Ava; Baumeister, Harald; Berking, Matthias; Auerbach, Randy P.; Bruffaerts, Ronny; Cuijpers, Pim; Kessler, Ronald C.; Ebert, David (International Journal of Methods in Psychiatric Research, 2019)
Internet- and mobile-based interventions (IMIs) offer the opportunity to deliver mental health treatments on a large scale. This randomized controlled trial evaluated the efficacy of an unguided IMI (StudiCare SAD) for university students with social anxiety disorder (SAD). University students (N = 200) diagnosed with SAD were randomly assigned to an IMI or a waitlist control group (WLC) with full access to treatment as usual. StudiCare SAD consists of nine sessions. The primary outcome was SAD symptoms at posttreatment (10 weeks), assessed via the Social Phobia Scale (SPS) and the Social Interaction Anxiety Scale (SIAS). Secondary outcomes included depression, quality of life, fear of positive evaluation, general psychopathology, and interpersonal problems. Results indicated moderate to large effect sizes in favor of StudiCare SAD compared with WLC for SAD at posttest for the primary outcomes (SPS: d = 0.76; SIAS: d = 0.55, p < 0.001). Effects on all secondary outcomes were significant and in favor of the intervention group. StudiCare SAD has proven effective in reducing SAD symptoms in university students. Providing IMIs may be a promising way to reach university students with SAD at an early stage with an effective treatment. OBJECTIVES METHODS RESULTS CONCLUSION

Efficacy of a smartphone-based Cognitive Bias Modification program for emotion regulation: A randomized-controlled crossover trial - Dietel, Fanny Alexandra; Rupprecht, Raphael; Seriyo, Alexander Mohamed; Post, Malte; Sudhoff, Bastian; Reichart, Jacqueline; Berking, Matthias; Buhlmann, Ulrike (Internet Interventions, 2024)
Previous research has identified maladaptive emotion regulation as a key factor in psychopathology. Thus, addressing emotion regulation via scalable, low-threshold digital interventions – such as smartphone-based Cognitive Bias Modification (CBM) – holds important therapeutic potential. Using a randomized-controlled crossover trial, we tested the efficacy of an integrated CBM module within the Affect Regulation Training (ART, i.e., CBM-ART) that targeted emotion regulation through elements of appraisal-based and approach avoidance training. Undergraduate students reporting elevated stress were randomized to a one-week active intervention (Mindgames; including psychoeducation, a quiz, and CBM-ART; n = 40), active control training (Emo Shape; including placebo psychoeducation, a quiz, and a placebo swiping task; n = 36) or waitlist (n = 25). Before and after the intervention, we assessed emotion regulation, interpretation bias, stress and depression. We further tested post-training stress reactivity using an anagram task. Results indicated that the active intervention improved negative (OR = 0.35) and positive (OR = 2.40) interpretation biases and symptom measures (d = 0.52–0.87). However, active control training showed attenuated concurrent pre-post changes on interpretation biases (i.e., OR = 0.53 for negative, and OR = 1.49 for positive interpretations) and symptom measures (d = 0.26–0.91). The active intervention was rated positively in terms of acceptability and usability. These findings provide initial evidence for the efficacy and acceptability of an integrated app-based CBM intervention for emotion regulation in reducing interpretation biases and psychopathological symptoms, including stress. However, future studies should disentangle specific mechanisms underlying interventional effects.
CRIS-Team Scopus Importer:2024-02-23
Keywords: Affect regulation training; Cognitive Bias Modification; E-mental health; Emotion regulation; Stress

Efficacy of a smartphone-based reappraisal training against depression and benefits of enhancing it with facial expression - Rupp, Lydia; Capito, Klara; Gmelch, Lena Marie; Böhme, Stephanie; Richer, Robert; Sadeghi, Misha; Rahimi, Farnaz; Abel, Luca; Eskofier, Björn; Berking, Matthias (Society for Psychotherapie Research 54th International Annual Meeting, 2023)

Efficacy of a smartphone-based reappraisal training against depressed mood and benefits of enhancing it with facial expression–a feasibility study - Capito, Klara; Gmelch, Lena Marie; Rupp, Lydia; Sadeghi, Misha; Eskofier, Björn; Berking, Matthias (Deutscher Psychotherapiekongress, 2022)

Efficacy of a web-based intervention with and without guidance for employees with risky drinking: results of a three-arm randomized controlled trial. - Boss, Leif; Lehr, Dirk; Schaub, Michael Patrick; Castro, Raquel Paz; Riper, Heleen; Berking, Matthias; Ebert, David (Addiction, 2018)
To test the efficacy of a web-based alcohol intervention with and without guidance. Three parallel groups with primary end-point after 6 weeks. Open recruitment in the German working population. Adults (178 males/256 females, mean age 47 years) consuming at least 21/14 weekly standard units of alcohol (SUA) and scoring ≥ 8/6 on the Alcohol Use Disorders Identification Test. Five web-based modules including personalized normative feedback, motivational interviewing, goal setting, problem-solving and emotion regulation during 5 weeks. One intervention group received an unguided self-help version (n=146) and the second received additional adherence-focused guidance by eCoaches (n=144). Controls were on a waiting list with full access to usual care (n=144). Primary outcome was weekly consumed SUA after 6 weeks. SUA after 6 months was examined as secondary outcome, next to numbers of participants drinking within the low-risk range, and general and work-specific mental health measures. All groups showed reductions of mean weekly SUA after 6 weeks (unguided: -8.0; guided: -8.5; control: -3.2). There was no significant difference between the unguided and guided intervention (P=0.324). Participants in the combined intervention group reported significantly fewer SUA than controls [B=-4.85, 95% confidence interval (CI)=-7.02 to -2.68, P < 0.001]. The intervention groups also showed significant reductions in SUA consumption after 6 months (B=-5.72, 95% CI=-7.71 to -3.73, P < 0.001) and improvements regarding general and work-related mental health outcomes after 6 weeks and 6 months. A web-based alcohol intervention, administered with or without personal guidance, significantly reduced mean weekly alcohol consumption and improved mental health and work-related outcomes in the German working population. AIMS DESIGN SETTING PARTICIPANTS INTERVENTION MEASUREMENTS FINDINGS CONCLUSIONS

Efficacy of a Web-Based Intervention With Mobile Phone Support in Treating Depressive Symptoms in Adults With Type 1 and Type 2 Diabetes: A Randomized Controlled Trial - Stephanie, Nobis; Lehr, Dirk; Ebert, David; Baumeister, Harald; Snoek, Frank; Heleen, Riper; Berking, Matthias (Diabetes Care, 2015)
OBJECTIVEDepression is common in diabetes and linked to adverse health outcomes. This study evaluated the efficacy of a guided web-based intervention in reducing depression in adults with type 1 and type 2 diabetes.RESEARCH DESIGN AND METHODSA total of 260 participants with diabetes and elevated depressive symptoms (Center for Epidemiologic Studies Depression Scale [CES-D 23]) were randomly assigned to the GET.ON Mood Enhancer Diabetes (a guided self-help intervention, n = 130) or a brief online unguided psychoeducation program for depression (n = 130). The primary outcome was depressive symptoms severity (CES-D). The secondary outcomes included diabetes-specific emotional distress (Problem Areas in Diabetes [PAID] scale) and participant satisfaction (adaption CSQ-8). Data were collected at baseline and 2 months after randomization. To identify differences in outcome between the groups, we used analyses of covariance with the baseline CES-D score as covariate on both intent-to-treat (ITT) and per-protocol (PP) basis.RESULTSCompared with the control group, the intervention group showed significantly less depressive symptom severity at posttreatment based on ITT (d = 0.89) and PP analyses (d = 1.00). The intervention participants displayed a significantly larger reduction in diabetes-specific emotional distress (d = 0.58, ITT). The intervention appeared to be acceptable to the participants; 95% (n = 121) would recommend the training to a friend with diabetes in need of psychological help.CONCLUSIONSA guided, web-based intervention to reduce depression in adults with type 1 and type 2 diabetes is effective in reducing both depressive symptoms and diabetes-specific emotional distress.

Efficacy of internet-based guided treatment for genito-pelvic pain/penetration disorder: Rationale, treatment protocol, and design of a randomized controlled trial - Zarski, Anna-Carlotta; Berking, Matthias; Ebert, David (Frontiers in Psychiatry, 2018)
Keywords: Dyspareunia; Internet intervention; Genito-pelvic pain/penetration disorder; Sexual dysfunction; Randomized controlled trial; Vaginismus

Efficacy of Internet-Based Treatment for Genito-Pelvic Pain/Penetration Disorder: Results of a Randomized Controlled Trial - Zarski, Anna-Carlotta; Berking, Matthias; Ebert, David Daniel (Journal of Consulting and Clinical Psychology, 2021)
Objective: The aim of this study was to evaluate the efficacy of an internet-based treatment for Genito-Pelvic Pain/Penetration Disorder (GPPPD) which adversely affects women's sexuality and is associated with reduced well-being and mental health comorbidities. Method: Two-hundred women with GPPPD (no penetrative intercourse >= 6 months) were randomly allocated to the intervention group (IG) or a waitlist control group (WCG). The intervention included eight modules and one booster session and was delivered through an eHealth platform. Participants were supported by an eCoach regarding treatment adherence. The primary outcome was intercourse penetration behavior. Online assessments were scheduled at baseline (T1), after Session 8/12 weeks (T2), and 6 months (T3) after randomization. Intention-to-treat analyses were reported. Results: Significantly more participants (31.00%, n = 31/100) in the IG were able to have sexual intercourse at T2 compared to those in the WCG, 13.00%, n = 13/100; chi(2)(1) = 9.44, p < .01. At T3, still more participants in the IG had sexual intercourse (29%) compared to those in the WCG (20%) but the groups no longer differed significantly, chi(2)(1) = 2.19, p = .19. Genital pain, painful and noncoital penetration behavior, and negative penetration-related cognitions significantly improved with medium to large effects at T2 (d = 0.66-1.25) and small to large effects at T3 (d = 0.23-1.32), whereas fear of sexuality, overall sexual functioning, trait anxiety, and well-being improved with small to medium effects (T2: d = 0.20-0.49, T3: d = 0.23-0.46) in the IG compared to the WCG. On average, participants completed 79% of the intervention. Conclusion: Internet-based treatment has been shown to be effective for GPPPD symptoms and could therefore be a promising treatment modality.
CRIS-Team WoS Importer:2021-12-17

Eine emotionsbasierte Variante des Annäherungs-Vermeidungs-Modifikationstrainings als Maßnahme zur Reduktion erhöhten Stresserlebens: eine Pilotstudie - Keinert, Eva Marie; Streit, Hannah; Böhme, Stephanie; Rupp, Lydia; Schindler-Gmelch, Lena; Capito, Klara; Eskofier, Björn; Schuller, Björn W.; Berking, Matthias (1. Deutscher Psychotherapiekongress, 2022)

Ein internetbasiertes Programm zur Prävention von Depression bei Diabetes mellitus Typ 2 Patienten - Konzept und Design einer randomisierten klinischen Studie - Nobis, Stephanie; Lehr, Dirk; Ebert, David; Bürckner, D; Riper, Heleen; Baumeister, Harald; Becker, Annette; Cuijpers, Pim; Funk, Burkhardt; Snoek, Frank J.; Berking, Matthias (Gesundheitswesen, 2012)
Zwischen 10% und 20% aller Diabetespatienten sind an einer Major Depression (MD) erkrankt. Es wird davon ausgegangen, dass die Prävalenz von früheren Stadien der Depression (subklinisch) weitaus höher liegt. Die Komorbidität Diabetes und Depression geht einher mit einer geringeren Lebensqualität, schlechteren Blutzuckereinstellung sowie einem erhöhten Risiko für diabetesbezogene Komplikationen. Depressive Diabetespatienten verursachen viermal so hohe Kosten im Vergleich zu einfachen Diabetespatienten. Aufgrund der Studienlage kann konstatiert werden, dass die Inzidenz von MD in Risikogruppen von 25% auf ca. 15% durch präventive Maßnahmen reduziert werden kann. Die Wirksamkeit von internetbasierten psychotherapeutischen Interventionen zur Prävention von depressiven Störungen konnte in mehreren Meta-Analysen nachgewiesen werden. Neben einer geringen Nutzungsschwelle für Betroffene besitzen internetbasierte Interventionen das Potential eine breite und evidenzbasierte Versorgung bereitzustellen, die vergleichsweise kostengünstig ist. Dennoch sind flächendeckende und bedarfsgerechte Versorgungskonzepte derzeit sowohl im Bereich der Prävention als auch im Bereich der Behandlung nur unzureichend etabliert. Diese Studie verfolgt das Ziel die Effektivität einer Mobiltelefon/Smartphone-gestützten internetbasierten präventiven Depressions-Intervention zu testen. In einer weiteren Analyse wird die Kosteneffektivität aus Sicht der Krankenkassen sowie aus gesamtgesellschaftlicher Sicht dargelegt.<br

Emotieregulatie - Berking, Matthias (2017)
Dit boek biedt psychotherapeuten, klinisch psychologen en psychiaters een wetenschappelijke onderbouwing en een concreet stappenplan voor een emotieregulatietraining. Deze training kan helpen bij de behandeling van angstproblemen, depressieve klachten, eetstoornissen, agressieregulatie of persoonlijkheidsstoornissen. Het eerste deel van Emotieregulatie gaat in op de samenhang tussen tekorten in de emotieregulatie en psychische stoornissen. Ook de implicaties daarvan voor de therapeutische praktijk worden belicht. Het tweede deel van het boek biedt een handleiding voor de Training Emotionele Competenties. De uitleg in deze handleiding is zo concreet, dat ervaren professionals er meteen mee aan de slag kunnen. Het derde deel beschrijft onder meer de huidige stand van het wetenschappelijk onderzoek naar de effectiviteit van de training. Matthias Berking is psychotherapeut en professor Klinische Psychologie en Psychotherapie aan de Universiteit van Erlangen-Nürnberg (Duitsland). De afgelopen 10 jaar heeft hij zich gefocust op het verklaren van de relevantie van emotieregulatievaardigheden voor de ontwikkeling en instandhouding van psychische stoornissen. Hij publiceerde verschillende onderzoeksartikelen en boeken over dit onderwer
Keywords: emotieregulatie; emotionele competenties; reguleren van emoties; emotieregulatiestrategieen; emoties

Emotieregulatietraining bij kinderen en adolescenten - Braet, Caroline; Berking, Matthias (Bohn Stafleu van Loghum Houten, 2019)
Emotieregulatietraining bij kinderen en adolescenten<br

Emotion regulation and mental health: current evidence and beyond - Berking, Matthias (World Psychiatry, 2024)
CRIS-Team Scopus Importer:2024-09-27

Emotion regulation and mental health: Recent findings, current challenges, and future directions - Berking, Matthias; Wupperman, Peggilee (Current Opinion in Psychiatry, 2012)
Purpose of review: In recent years, deficits in emotion regulation have been studied as a putative maintaining factor and promising treatment target in a broad range of mental disorders. This article aims to provide an integrative review of the latest theoretical and empirical developments in this rapidly growing field of research. Recent Findings: Deficits in emotion regulation appear to be relevant to the development, maintenance, and treatment of various forms of psychopathology. Increasing evidence demonstrates that deficits in the ability to adaptively cope with challenging emotions are related to depression, borderline personality disorder, substance-use disorders, eating disorders, somatoform disorders, and a variety of other psychopathological symptoms. Unfortunately, studies differ with regard to the conceptualization and assessment of emotion regulation, thus limiting the ability to compare findings across studies. Future research should systematically work to use comparable methods in order to clarify the following: which individuals have; what kinds of emotion regulation difficulties with; which types of emotions; and what interventions are most effective in alleviating these difficulties. Summary: Despite some yet to be resolved challenges, the concept of emotion regulation has a broad and significant heuristic value for research in mental health. © 2012 Wolters Kluwer Health | Lippincott Williams & Wilkins.
Created from Fastlane, Scopus look-up
Keywords: emotion regulation; mental disorders; psychopathology; review; skills

Emotion regulation and psychopathology: Investigating differential associations between emotion regulation skills and psychological symptoms using a network approach - Trautmann, Sebastian; Muehlhan, Markus; Berking, Matthias; Miethe, Sandra; Wigger, Janna; Dragan, Małgorzata (British Journal of Clinical Psychology, 2024)
Objectives: Emotion regulation plays an important role in the development and maintenance of psychopathology. However, the question whether specific ER skills are related to specific psychological symptoms has rarely been studied, but has important implications for targeted interventions. This analysis aims to explore potential differential associations between various ER skills and psychological symptoms using a network analysis approach. Methods: Routine data from a transdiagnostic clinical sample of 716 patients (460 females, 256 males) from an outpatient clinic for psychotherapy were analysed. Nine ER skills were assessed with the Emotion Regulation Skills Questionnaire, and nine symptom dimension scores were obtained using the Brief Symptom Inventory. A regularized partial correlation network models including ER skills and individual symptom domains were calculated. Bridge expected influence was calculated to estimate the strength of association of each ER skill with psychological symptoms. Results: Only the following ER skills were most strongly related to psychological symptoms (bridge expected influence): Tolerance, Confrontation and Modification. All other ER skills were indirectly connected to symptom severity through these four skills. The strongest direct edges between ER skills and symptoms were Modification—Depression, Confrontation—Obsession-Compulsion and Tolerance—Interpersonal Sensitivity, which were significantly stronger than the vast majority of other associations between ER skills and psychological symptoms. Conclusions: These exploratory findings provide valuable targets for future studies to investigate specific associations between ER skills and psychological symptoms which could help to improve outcome monitoring and efficacy of interventions targeting ER.
CRIS-Team Scopus Importer:2024-10-04
Keywords: emotion regulation; network analysis; psychological symptoms; psychopathology

Emotion regulation: An overview of and critical reflection on the current state of research - Heber, Elena; Lehr, Dirk; Riper, Heleen; Berking, Matthias (Zeitschrift für Klinische Psychologie und Psychotherapie, 2014)
The topic of emotion regulation has become increasingly popular in clinical psychology. However, the question arises to what extent the popularity of the construct is consistent with its validity and actual heuristic value. Thus, the aim of the present review is to provide a current overview of conceptualizations of emotion regulation, of available assessment methods, of research investigating the association between emotion regulation and mental health, and of therapeutic utilizations of the paradigm. Based on a critical reflection of these research areas, suggestions are formulated on how the validity and fruitfulness of this innovative concept can be further enhanced.
Keywords: Emotion regulation; Overview; Psychological disorder; Review

Emotion regulation mediates the effect of childhood trauma on depression - Hopfinger, Lisa; Berking, Matthias; Bockting, Claudi L. H.; Ebert, David (Journal of Affective Disorders, 2016)
Background Childhood trauma increases the risks of both depression and dysfunctional emotion regulation, which is a factor that has been strongly linked to depression. Because of these demonstrated relationships, it can be hypothesized that dysfunctional emotion regulation is a mediator of the association between childhood trauma and depression. Methods To test this hypothesis, we assessed the indirect effect of emotion regulation (Emotion Regulation Skills Questionnaire) on the relationship between childhood trauma (Childhood Trauma Questionnaire) and depression severity (24-item Hamilton Rating Scale for Depression) as well as depression lifetime persistency (i.e., lifetime percentage spent in major depressive episodes; assessed via SCID and Life Chart Interviews) in 269 patients with major depressive disorder (MDD). Results Bootstrapping-enhanced mediation analyses indicated that deficits in general emotion regulation mediated the association of childhood trauma to both depression severity and depression lifetime persistency. Further exploratory analyses indicated that specific emotion regulation skills (such as the ability to mindfully observe, accept, and tolerate undesired emotions or the willingness to voluntarily confront situations that prompt negative emotions in order to attain personally relevant goals) significantly mediated the association between childhood trauma and depression severity. Willingness to confront was a mediator for both depression outcomes (depression severity and lifetime persistency). Limitations The employed mediation analyses are cross-sectional in nature, which limits any firm conclusions regarding causality. Conclusions The findings support the assumption that a sophisticated emotion regulation may help prevent the onset or unfavorable course of depression in individuals who have experienced childhood trauma.
Keywords: Childhood trauma; Depression lifetime persistency; Depression severity; Emotion regulation; Mediator; Regression

Emotion regulation predicts anxiety over a five-year interval: A cross-lagged panel analysis - Wirtz, Carolin Maria; Hofmann, Stefan; Riper, Heleen; Berking, Matthias (Depression and Anxiety, 2014)
Background Emotion regulation (ER) deficits have been linked to symptoms of anxiety in cross-sectional studies. However, the direction of the relationship between ER and anxiety symptom severity (ASS) is unclear. Methods In order to clarify the relationship between ER skills and ASS symptoms, we assessed skills and symptoms in 131 individuals twice over a 5-year interval. Cross-lagged panel analyses were conducted to test whether ER skills were a significant predictor of subsequent ASS or vice versa. Additionally, we explored whether specific ER skills differed in regard to the strength of prospective associations with subsequent ASS. Results ER skills negatively predicted subsequent ASS over and above the effects of baseline ASS (whereas anxiety symptoms did not predict subsequent ER deficits). Acceptance, tolerance, and willingness to confront had the strongest prospective effects on lower subsequent ASS. Conclusions General ER skills may play an important role in the development and maintenance of anxiety disorders. © 2013 Wiley Periodicals, Inc.
Keywords: anxiety; emotion regulation; predictor; prospective study; risk factors; skills

Emotion regulation predicts symptoms of depression over five years - Berking, Matthias; Wirtz, Carolin Maria; Svaldi, Jennifer; Hofmann, Stephan (Behaviour Research and Therapy, 2014)
Deficits in emotion regulation have been identified as an important risk and maintaining factor for depression. The aim of this study was to examine the long-term effects of emotion regulation on symptoms of depression. Moreover, we investigated which specific emotion regulation skills were associated with subsequent symptoms of depression. Participants were 116 individuals (78% women, average age 35.2 years) who registered for an online-based assessment of depression and its risk-factors and reported at least some symptoms of depression. Successful application of emotion regulation skills and depressive symptom severity were assessed twice over a 5-year period. We utilized cross-lagged panel analyses to assess whether successful skills application would be negatively associated with subsequent depressive symptom severity. Cross-lagged panel analyses identified successful skills application as a significant predictor for depressive symptom severity even when controlling for the effects of initial symptoms of depression. A comparison of the effect sizes for different emotion regulation skills on subsequent depressive symptoms suggests that most of the skills included have similar predictive value. These findings provide preliminary evidence for the hypotheses that deficits in emotion regulation may contribute to the development of depression and that interventions systematically enhancing adaptive emotion regulation skills may help prevent and treat depressive symptoms. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Emotion regulation; Depression; Risk factors; Skills; Prospective study

Emotion Regulation Protects Against Recurrence of Depressive Symptoms Following Inpatient Care for Major Depressive Disorder - Ebert, David; Hopfinger, Lisa; Berking, Matthias (Behavior Therapy, 2017)
Relapse following response in psychotherapy for major depressive disorder (MDD) is a major concern. Emotion regulation (ER) has been discussed as a putative emerging and maintaining factor for depression. The purpose of the present study was to examine whether ER protects against recurrence of depression over and above residual symptoms of depression following inpatient care for MDD. ER skills (ERSQ-ES) and depression (HEALTH-49) were assessed in 193 patients with MDD (age, M = 47.4, SD = 9.6, 75.1% female, 100% Caucasian) at treatment discontinuation, 3 and 12 months after treatment. Multiple hierarchical regressions were used to examine general and specific ER as predictors of depressive symptoms at follow-ups. Higher general ER predicted lower depression over and beyond residual symptoms of depression at 3-month follow-up among treatment responders but not among treatment nonresponders. With regard to specific ER skills, readiness to confront and a. cceptance of undesired emotions predicted lower depressive symptoms beyond residual symptoms of depression 12 months, respectively 3 and 12 months after treatment. Findings of the present study indicate that targeting general ER might be more important for remitted and less important for nonremitted patients. Enhancing ER should hence be realized in a sequential treatment design, in which a continuation phase treatment with a specific focus on ER directly follows, once patients sufficiently responded to treatment. Acceptance of undesired emotion and readiness to confront situations that cue these emotions appear to be particularly important for protecting against recurrence of depression. Future research should clarify whether findings can be generalized to outpatient care.
Keywords: Acceptance; Depression; Emotion regulation; Psychotherapy; Relapse

Emotion-regulation skills as a treatment target in psychotherapy - Berking, Matthias; Wupperman, Peggilee; Reichardt, Alexander; Pejic, Tanja; Dippel, Alexandra; Znoj, Hansjörg (Behaviour Research and Therapy, 2008)
Background: Deficits in emotion-regulation skills have been shown to be integral to the development and maintenance of a wide range of mental disorders. Aim: To evaluate the importance of these skills as a treatment target in psychotherapeutic interventions. Method: Nine specific emotion-regulation skills were assessed in a sample of 289 inpatients before and after cognitive-behavioural treatment. Self-reports of success in pretreatment skills application were first compared to those of 246 non-clinical controls. Pretreatment skills application and change in skills application during therapy were then related to a variety of outcome measures. Finally, the effects of integrating a brief training of general emotion-regulation skills into the CBT-based treatment were evaluated in a controlled trial. Results: Uni- and multivariate analyses identified the skills of acceptance, tolerance, and active modification of negative emotions as particularly important for current mental health and treatment outcome. Replacing parts of the standard CBT treatment with the emotion-regulation training enhanced the effects of the CBT treatment on skills application and on other measures of mental health. Conclusion: Incorporating interventions that directly target general emotion-regulation skills may improve the effectiveness of psychotherapeutic interventions. © 2008 Elsevier Ltd.
Created from Fastlane, Scopus look-up
Keywords: Emotion regulation; Emotion-regulation skills; Mental health; Psychotherapy; Skills training

EMOTION REGULATION SKILLS IN PATIENTS WITH MEDICALLY UNEXPLAINED PHYSICAL SYMPTOMS - Schwarz, Jeanine; Radkovsky, Anna; Berking, Matthias; Rief, Winfried; Kleinstauber, Maria (2016)

Emotion regulation skills training enhances the efficacy of inpatient cognitive behavioral therapy for major depressive disorder: A randomized controlled trial - Berking, Matthias; Ebert, David; Cuijpers, Pim; Hofmann, Stefan G. (Psychotherapy and Psychosomatics, 2013)
Background: Deficits in emotion regulation skills are possible factors maintaining major depressive disorder (MDD). Therefore, the aim of the study was to test whether integrating a systematic emotion regulation training (ERT) enhances the efficacy of routine inpatient cognitive behavioral therapy (CBT) for MDD. Methods: In a prospective randomized controlled trial, 432 inpatients meeting criteria for MDD were assigned to receive either routine CBT or CBT enriched with an intense emotion regulation skills training (CBT-ERT). Results: Participants in the CBT-ERT condition demonstrated a significantly greater reduction in depression (response rates-CBT: 75.5%, CBT-ERT: 84.9%; remission rates-CBT: 51.1%, CBT-ERT: 65.1%). Moreover, CBT-ERT participants demonstrated a significantly greater reduction of negative affect, as well as a greater increase of well-being and emotion regulation skills particularly relevant for mental health. Conclusions: Integrating strategies that target emotion regulation skills improves the efficacy of CBT for MDD.
Created from Fastlane, Scopus look-up
Keywords: Cognitive behavioral therapy; Depression; Emotion regulation; Routine clinical care; Skills training

Emotion regulation strategies in bulimia nervosa: an experimental investigation of mindfulness, self-compassion, and cognitive restructuring - Hessler-Kaufmann, Johannes Baltasar; Heese, Julia; Berking, Matthias; Voderholzer, Ulrich; Diedrich, Alice (Borderline Personality Disorder and Emotion Dysregulation, 2020)
Background: While improving emotion regulation (ER) is a central goal in the therapy of bulimia nervosa (BN), there is no experimental evidence on the efficacy of different ER strategies. (1) We hypothesized that mindfulness as well as self-compassion as contextual strategies and cognitive restructuring as classical cognitive behavioral strategy would outperform waiting in improving emotional and eating disorder related outcomes after an unpleasant mood induction. Further, we explored (2) whether contextual strategies outperformed cognitive restructuring and (3) whether comorbid mental disorders and previous treatment for BN influenced the efficacy of contextual ER strategies compared to cognitive restructuring.
CRIS-Team WoS Importer:2020-07-31

Emotionsregulation – Trend in der Psychotherapie - Lammers, Claas-Hinrich; Berking, Matthias (Psychotherapie im Dialog, 2018)

Emotionsregulation: Überblick und kritische Reflexion des aktuellen Forschungsstandes - Heber, Elena; Lehr, Dirk; Heleen, Riper; Berking, Matthias (Zeitschrift für Klinische Psychologie und Psychotherapie, 2014)

Empirically based guidelines for goal-finding procedures in psychotherapy: Are some goals easier to attain than others? - Berking, Matthias; Grosse Holtforth, Martin; Jacobi, Claus; Kroener-Herwig, Birgit (Psychotherapy Research, 2005)
Treatment goals are either proposed by a patient or deduced from the case formulation of the therapist. To optimize goal-finding procedures in psychotherapy, therapists need an empirical point of reference to estimate the degree of goal attainment that can be expected for a specific treatment goal. To establish such an empirical basis, treatment goal categories of the primary treatment goals of 2,770 inpatients undergoing cognitive-behavioral therapy were categorized by the Bern Inventory of Treatment Goals. The levels of goal attainment were then compared with respect to 48 different goal categories. The results indicate that goal attainment differs according to treatment goal categories, even if confounding characteristics of the patient are controlled for. © 2005 Society for Psychotherapy Research.
Created from Fastlane, Scopus look-up

EmpkinS-EKSpression-BioFACEBack: Ergebnisse eines randomisiert-kontrollierten Trials zu gesichtsmuskelfokussiertem Biofeedback bei depressiven Erkrankungen - Schindler-Gmelch, Lena; Rupp, Lydia; Rahimi, Farnaz; Sadeghi, Misha; Keinert, Eva Marie; Hager, Malin; Capito, Klara; Richer, Robert; Eskofier, Björn; Berking, Matthias (4. Deutscher Psychotherapie Kongress, 2025)

EmpkinS-EKSpression: Ergebnisse einer Randomisiert-kontrollierten klinischen Studie eines Emotions-gestützten Trainings zur Kognitiven Umstrukturierung - Rupp, Lydia; Schindler-Gmelch, Lena; Sadeghi, Misha; Rahimi, Farnaz; Keinert, Eva Marie; Hager, Malin; Capito, Klara; Richer, Robert; Eskofier, Björn; Berking, Matthias (4. Deutscher Psychotherapie Kongress, 2025)

EmpkinS - Empathokinästhetische Sensorik für Biofeedback bei Depression - Gmelch, Lena Marie; Böhme, Stephanie; Capito, Klara; Rupp, Lydia; Richer, Robert; Sadeghi, Misha; Eskofier, Björn; Berking, Matthias (Deutscher Psychotherapiekongress (DPK), 2022)

EmpkinS: empatho-kinesthetic sensory systems for biofeedback in depression - Gmelch, Lena Marie; Capito, Klara; Rupp, Lydia; Richer, Robert; Sadeghi, Misha; Eskofier, Björn; Berking, Matthias; Böhme, Stephanie (EmpkinS: empatho-kinesthetic sensory systems for biofeedback in depression, 2022)

Enhancing Emotion-Regulation Skills in Police Officers: Results of a Pilot Controlled Study - Berking, Matthias; Meier, Caroline; Wupperman, Peggilee (Behavior Therapy, 2010)
Police officers are routinely exposed to situations that elicit intense negative emotions; thus, officers have a particularly strong need for effective methods of regulating such emotions. The main purpose of this study was to investigate whether a manualized emotion-regulation training (Integrative Training of Emotional Competencies; iTEC; Berking, 2010a) can improve the emotion-regulation skills of police officers. First, self-reports of 9 emotion-regulation skills were assessed in a sample of officers (N=31) and compared to those of a matched community-based control group. Then, the effects of the training on the emotion-regulation skills of officers were evaluated in a time-staggered design with a waitlist control condition. Results indicate that, compared to controls, officers have difficulties in accepting and tolerating negative emotions, supporting themselves in distressing situations, and confronting emotionally challenging situations. The training significantly enhanced successful skill application, especially some skills with which officers reported difficulty applying. These findings suggest that a focus on emotion-regulation skills may be an important component for programs aimed at preventing mental-health problems in police officers. © 2010.
Created from Fastlane, Scopus look-up

Enriching Cognitive Behavior Therapy with Emotion Regulation Training for Patients with Multiple Medically Unexplained Symptoms (ENCERT): Design and implementation of a multicenter, randomized, active-controlled trial - Kleinstaeber, Maria; Gottschalk, Japhia; Berking, Matthias; Rau, Joern; Rief, Winfried (Contemporary Clinical Trials, 2016)
Introduction: Although cognitive behavior therapy (CBT) is the best evidenced psychological treatment for medically unexplained symptoms (MUS), effect sizes are rather moderate. Empirically evidenced deficits in emotion processing in patients with MUS make a CBT enriched with an emotion regulation training (ENCERT) a promising approach to increase treatment effects. Methods and design: This protocol describes the development and implementation of a multicenter, randomized, active-controlled study with blinded outcome assessors to compare the efficacy of ENCERT with a conventional CBT for MUS. Individuals presenting with ≥ 3 disabling, chronic MUS and fulfilling other predefined inclusion criteria are randomized to 20 sessions either of ENCERT or conventional CBT. Power calculations are based on the severity index of the Screening of Somatoform Disorders-7T and obtained an optimal sample size of N= 244. Questionnaires on symptom severity, symptom-related psychological features, and emotion regulation skills are administered at baseline, end of therapy, and 6-months follow-up. An every-session monitoring of therapy progress, and regular patients'/therapists' ratings of quality of therapy, working alliance, outcome expectations, and adverse events are conducted. Primary statistical analysis shall verify the hypothesis of ENCERT being more efficacious than conventional CBT regarding symptom severity. Discussion: Enriching CBT with transdiagnostic therapeutic strategies addressing emotion regulation is a promising and new approach to target not only somatic symptom coping but also symptom-associated problems and comorbid mental disorders. The current trial will not only allow examining the efficacy of ENCERT but also important variables and mechanisms of the process of therapy.Trial registration: NCT01908855.
Keywords: Active-controlled trial; Cognitive behavior therapy; Emotion regulation; Medically unexplained symptoms; Multicenter trial; Randomized controlled trial

Entwicklung und Validierung eines Fragebogens zur emotionsspezifischen Selbsteinschätzung emotionaler Kompetenzen (SEK-ES) - Ebert, David Daniel; Christ, Oliver; Berking, Matthias (Diagnostica, 2013)
Numerous studies demonstrate the importance of emotion regulation skills for mental health. Unfortunately, many of these studies rely on self-report measures assessing ways of coping with emotions or mood states in general. Thus, it remains unclear which emotions participants refer to when completing these measures and whether skill level varies across specific emotional states. The aim of the present study is the development and validation of a questionnaire that allows an economic assessment of both emotion-specific and general emotion regulation skills. Based on the general emotion regulation skills questionnaire (ERSQ-27; Berking & Znoj, 2008) we developed an emotion-specific instrument (ERSQ-ES) to assess adaptive ways of coping with general distress, anxiety, anger, sadness, and depressed mood. Item characteristics, reliability, validity, and sensitivity to change of the ERSQ-ES were investigated in a nonclinical (N=358) and a clinical sample (N=579). Findings suggest good-to-very-good psychometric properties of the ERSQ-ES and demonstrate the need to systematically assess emotion regulation skills for specific emotions. © 2013 Hogrefe Verlag ,Göttingen.
Created from Fastlane, Scopus look-up
Keywords: Assessment; Emotion regulation; Emotion regulation skills; Emotions; Psychotherapy

Entwicklung und Validierung eines Fragebogens zur standardisierten Selbsteinschätzung emotionaler Kompetenzen (SEK-27) - Berking, Matthias; Znoj, Hansjörg (Zeitschrift für Psychiatrie, Psychologie und Psychotherapie, 2008)
Background: Deficits and resources in general emotion-regulation skills have been shown to be important for the development, maintenance and treatment of mental disorders. Objective: In order to be able to economically assess a wide range of helpful ways of dealing with negative emotions, the Fragebogen zur Selbsteinschätzung Emotionaler Kompetenzen (SEK-27) has been developed and validated. Methods: Using data from two normal control samples (N = 952) and three clinical samples (N = 238), a variety of indicators of test quality were computed. Results: Findings confirm the reliability, validity and change sensitivity of the questionnaire. Conclusions: The SEK-27 is an economical self-report measure with appropriate psychometric properties that can be used to assess a broad range of adaptive ways of dealing with negative emotions. © 2008 by Verlag Hans Huber, Hogrefe AG.
Created from Fastlane, Scopus look-up
Keywords: Assessment; Emotion regulation; Emotion regulation skills; Emotional intelligence; Psychotherapy

Erweiterung der kognitiven Verhaltenstherapie um Emotionsregulationstraining bei Patienten mit multiplen somatoformen Symptomen: Ergebnisse einer kontrollierten Pilotstudie - Gottschalk, Japhia-Marie; Bleichhardt, Gaby; Kleinstauber, Maria; Berking, Matthias; Rief, Winfried (Verhaltenstherapie, 2015)
Hintergrund: Kognitive Verhaltenstherapie (KVT) ist bei Patienten mit multiplen somatoformen Symptomen (MSS) erwiesenermaßen wirksam, bisher jedoch nur mit moderaten Effekten. Da sich bei diesen Patienten Hinweise für ein Emotionswahrnehmungsdefizit und Regulationsdefizit finden, wurde an der Universität Marburg ein Behandlungsmanual für Patienten mit MSS entwickelt, das KVT-Elemente und ein spezielles Emotionsregulationstraining verbindet. In diesem soll der Umgang mit Emotionen durch Strategien der bewertungsfreien Wahrnehmung, Akzeptanz und Achtsamkeit gefördert werden. Ziel der vorliegenden Studie war, die Durchführbarkeit des Behandlungsprogramms ENCERT (Enriching CBT with Emotion Regulation Training) zu testen sowie die Veränderungen über die Zeit unter ENCERT mit denen einer klassischen KVT zu vergleichen. Patienten und Methoden: 20 ENCERT-Patienten und 22 KVT-Patienten (mit ≥3 somatoformen Symptomen, seit ≥6 Monaten) nahmen im Rahmen einer nicht randomisierten Gruppenvergleichsstudie an 20 wöchentlichen Einzeltherapiesitzungen im ambulanten Setting teil. Zu Therapiebeginn und -ende wurden relevante Daten erhoben. Die primären Outcomemaße waren das Screening für somatoforme Störungen (SOMS-7T), der Fragebogen zur Selbsteinschätzung emotionaler Kompetenzen (SEK-27) und visuelle Analogskalen (VAS) zur Einschätzung der Symptomintensität und zur empfundenen Beeinträchtigung. Ergebnisse: Beide Gruppen verbesserten sich im Therapieverlauf signifikant bezüglich der Beeinträchtigungsintensität (ENCERT d = 0,70; KVT d = 0,46) und Beschwerdeanzahl (ENCERT d = 0,72; KVT d = 0,50). Gruppenunterschiede zu Therapieende zeigten sich nicht: Unter Berücksichtigung klinisch relevanter Baselinevariablen zeigte sich zu Therapieende ein Hinweis auf einen signifikanten Unterschied in der Beeinträchtigungsintensität (ANCOVA: F (1,37) = 4,058, p = 0,051; ENCERT überlegen). ENCERT-Patienten verbesserten sich zudem signifikant auf stündlich erhobenen visuellen Analogskalen (Beschwerdeintensität d = 0,59; Beeinträchtigung durch Beschwerden d = 1,25) und in ihren Emotionsregulationskompetenzen (d = 1,14). Schlussfolgerung: Patienten mit MSS verbesserten sich während ENCERT und KVT, mit tendenziell höheren Effektstärken für ENCERT, jedoch auch höheren Ausgangswerten in Depressivität und Angst. Gruppenunterschiede zeigten sich nicht, möglicherweise aufgrund geringer Power. Diese Ergebnisse ermutigen zur Durchführung einer größeren randomisierten und kontrollierten Multicenterstudie.
Keywords: Multiple somatoform symptoms; Pilot study; CBT; Emotion regulation; Effectiveness

European COMPARative Effectiveness research on blended Depression treatment versus treatment-as-usual (E-COMPARED): Study protocol for a randomized controlled, non-inferiority trial in eight European countries - Kleiboer, Annet; Jan, Smit; Bosmans, Judith; Ruwaard, Jeroen; Andersson, Gerhard; Topooco, Naira; Berger, Thomas; Krieger, Tobias; Botella, Christina; Banos Rivera, Rosa; Chevreul, Karine; Araya, Ricardo; et al. (Trials, 2016)
Keywords: Adults; Blended treatment; Cognitive behavioral treatment (CBT); Comparative effectiveness research (CER); Cost-effectiveness; Depression; EHealth; ICBT; Internet-based treatment; Randomized controlled trial (RCT)

Evaluating a hybrid web-based training program for panic disorder and agoraphobia: Randomized controlled trial - Ebenfeld, Lara; Lehr, Dirk; Ebert, David Daniel; Stegemann, Stefan Kleine; Riper, Heleen; Funk, Burkhardt; Berking, Matthias (Journal of Medical Internet Research, 2021)
Background: Previous studies provide evidence for the effectiveness of web-based interventions for panic disorder with and without agoraphobia. Smartphone-based technologies hold significant potential for further enhancing the accessibility and efficacy of such interventions. Objective: This randomized controlled trial aims to evaluate the efficacy of a guided, hybrid web-based training program based on cognitive behavioral therapy for adults with symptoms of panic disorder. Methods: Participants (N=92) with total scores in the Panic and Agoraphobia Scale ranging from 9 to 28 were recruited from the general population and allocated either to a hybrid intervention (GET.ON Panic) or to a wait-list control group. The primary outcome was the reduction in panic symptoms, as self-assessed using a web-based version of the Panic and Agoraphobia Scale. Results: Analysis of covariance-based intention-to-treat analyses revealed a significantly stronger decrease in panic symptoms posttreatment (F=9.77; P=.002; Cohen d=0.66; 95% CI 0.24-1.08) in the intervention group than in the wait-list control group. Comparisons between groups of the follow-up measures at 3 and 6 months yielded even stronger effects (3-month follow-up: F=17.40, P<.001, Cohen d=0.89, 95% CI 0.46-1.31; 6-month follow-up: F=14.63, P<.001, Cohen d=0.81, 95% CI 0.38-1.24). Conclusions: Hybrid web-based training programs may help reduce the symptoms of panic disorder and hence play an important role in improving health care for patients with this debilitating disorder.
CRIS-Team Scopus Importer:2021-03-26
Keywords: Agoraphobia; Internet; Mobile phone; Panic disorder; Randomized controlled trial; Treatment

Evaluating a multimodal, clinical and work-directed intervention (RTW-PIA) to support sustainable return to work among employees with mental disorders: study protocol of a multicentre, randomised controlled trial - Starke, Fiona; Sikora, Alexandra; Stegmann, Ralf; Knebel, Leonie; Buntrock, Claudia; de Rijk, Angelique; Houkes, Inge; Szycik, Gregor R.; Unger, Hans Peter; Schumacher, Jan Ole; Stark, Heiko; Hauth, Iris; et al. (BMC Psychiatry, 2023)
Background: Mental disorders (MDs) are one of the leading causes for workforce sickness absence and disability worldwide. The burden, costs and challenges are enormous for the individuals concerned, employers and society at large. Although most MDs are characterised by a high risk of relapse after treatment or by chronic courses, interventions that link medical-psychotherapeutic approaches with work-directed components to facilitate a sustainable return to work (RTW) are rare. This protocol describes the design of a study to evaluate the (cost-)effectiveness and implementation process of a multimodal, clinical and work-directed intervention, called RTW-PIA, aimed at employees with MDs to achieve sustainable RTW in Germany. Methods: The study consists of an effectiveness, a health-economic and a process evaluation, designed as a two-armed, multicentre, randomised controlled trial, conducted in German psychiatric outpatient clinics. Sick-listed employees with MDs will receive either the 18-month RTW-PIA treatment in conjunction with care as usual, or care as usual only. RTW-PIA consists of a face-to-face individual RTW support, RTW aftercare group meetings, and web-based aftercare. Assessments will be conducted at baseline and 6, 12, 18 and 24 months after completion of baseline survey. The primary outcome is the employees´ achievement of sustainable RTW, defined as reporting less than six weeks of working days missed out due to sickness absence within 12 months after first RTW. Secondary outcomes include health-related quality of life, mental functioning, RTW self-efficacy, overall job satisfaction, severity of mental illness and work ability. The health-economic evaluation will be conducted from a societal and public health care perspective, as well as from the employer’s perspective in a cost–benefit analysis. The design will be supplemented by a qualitative effect evaluation using pre- and post-interviews, and a multimethod process evaluation examining various predefined key process indicators from different stakeholder perspectives. Discussion: By applying a comprehensive, multimethodological evaluation design, this study captures various facets of RTW-PIA. In case of promising results for sustainable RTW, RTW-PIA may be integrated into standard care within German psychiatric outpatient clinics. Trial registration: The study was prospectively registered with the German Clinical Trials Register (DRKS00026232 , 1 September 2021).
CRIS-Team Scopus Importer:2023-06-09
Keywords: Mental disorders; Multimodal Intervention; Protocol; RCT; Relapse prevention; Return to work; Sickness absence; SRTW; Sustainability

Evaluating the (cost-)effectiveness of guided and unguided Internet-based self-help for problematic alcohol use in employees - a three arm randomized controlled trial - Boß, Leif; Lehr, Dirk; Berking, Matthias; Heleen, Riper; Schaub, Michael; Ebert, David (BMC Public Health, 2015)
Discussion: There is a need to identify effective low-threshold solutions to improve ill-health and reduce the negative economic consequences due to problematic alcohol drinking in workforces. If the proposed web-based intervention proves both to be efficacious and cost-effective, it may be a useful tool to increase utilization rates of interventions for problematic drinking in occupational settings.
Keywords: Internet intervention; Alcohol; Work-related stress; Occupational health; Cost-effectiveness; Self-help; Problematic alcohol use; Alcohol use disorders; Randomized controlled trial

Evaluating the efficacy and cost-effectiveness of web-based indicated prevention of major depression: design of a randomised controlled trial. - Buntrock, Claudia; Ebert, David; Lehr, Dirk; Cuijpers, Pim; Riper, Heleen; Smit, Filip; Berking, Matthias (BMC Psychiatry, 2014)
BACKGROUND Major depressive disorder (MDD) imposes a considerable disease burden on individuals and societies. Web-based interventions have shown to be effective in reducing depressive symptom severity. However, it is not known whether web-based interventions may also be effective in preventing the onset of MDD. The aim of this study is to evaluate the (cost-) effectiveness of an indicated web-based guided self-help intervention (GET.ON Mood Enhancer Prevention) on the onset of MDD. METHODS/DESIGN A randomised controlled trial (RCT) will be conducted to compare the (cost-) effectiveness of the GET.ON Mood Enhancer Prevention training with a control condition exclusively receiving online-based psychoeducation on depression. Adults with subthreshold depression (N = 406) will be recruited from the general population and randomised to one of the two conditions. The primary outcome is time to onset of MDD within a 12-months follow-up period. MDD will be assessed according to DSM-IV criteria as assessed by the telephone-administered Structured Clinical Interview for DSM-IV (SCID). Time to onset of MDD will be assessed using life charts. Secondary outcomes include changes on various indicators of depressive symptom severity, anxiety and quality of life from baseline to post-treatment, to a 6-month and a 12-month follow up. Additionally, an economic evaluation using a societal perspective will be conducted to examine the intervention's cost-effectiveness. DISCUSSION This is one of the first randomised controlled trials that examines the effect of an indicated guided self-help web-based intervention on the incidence of major depression. If shown to be effective, the intervention will contribute to reducing the disease burden due to MDD in the general population. TRIAL REGISTRATION German Clinical Trial Registration DRKS00004709.

Evaluating the feasibility and exploring the efficacy of an emotion-based approach-avoidance modification training (eAAMT) in the context of perceived stress in an adult sample — protocol of a parallel randomized controlled pilot study - Keinert, Eva Marie; Eskofier, Björn; Schuller, Björn W.; Böhme, Stephanie; Berking, Matthias (Pilot and Feasibility Studies, 2023)
Background: Stress levels and thus the risk of developing related physical and mental health conditions are rising worldwide. Dysfunctional beliefs contribute to the development of stress. Potentially, such beliefs can be modified with approach-avoidance modification trainings (AAMT). As previous research indicates that effects of AAMTs are small, there is a need for innovative ways of increasing the efficacy of these interventions. For this purpose, we aim to evaluate the feasibility of the intervention and study design and explore the efficacy of an innovative emotion-based AAMT version (eAAMT) that uses the display of emotions to move stress-inducing beliefs away from and draw stress-reducing beliefs towards oneself. Methods: We will conduct a parallel randomized controlled pilot study at the Friedrich-Alexander-Universität Erlangen-Nürnberg, Germany. Individuals with elevated stress levels will be randomized to one of eight study conditions (n = 10 per condition) — one of six variants of the eAAMT, an active control intervention (swipe-based AAMT), or an inactive control condition. Participants in the intervention groups will engage in four sessions of 20–30 min (e)AAMT training on consecutive days. Participants in the inactive control condition will complete the assessments via an online tool. Non-blinded assessments will be taken directly before and after the training and 1 week after training completion. The primary outcome will be perceived stress. Secondary outcomes will be dysfunctional beliefs, symptoms of depression, emotion regulation skills, and physiological stress measures. We will compute effect sizes and conduct mixed ANOVAs to explore differences in change in outcomes between the eAAMT and control conditions. Discussion: The study will provide valuable information to improve the intervention and study design. Moreover, if shown to be effective, the approach can be used as an automated smartphone-based intervention. Future research needs to identify target groups benefitting from this intervention utilized either as stand-alone treatment or an add-on intervention that is combined with other evidence-based treatments. Trial registration: The trial has been registered in the German Clinical Trials Register (Deutsches Register Klinischer Studien; DRKS00023007 ; September 7, 2020).
CRIS-Team Scopus Importer:2023-09-29
Keywords: Approach-avoidance modification; Dysfunctional beliefs; Emotion; Parallel randomized controlled pilot trial; Perceived stress; Smartphone-based intervention

Evaluation of a text-message-based maintenance intervention for Major Depressive Disorder after inpatient cognitive behavioral therapy - Schlicker, Sandra; Ebert, David; Middendorf, Thomas; Titzler, Ingrid; Berking, Matthias (Journal of Affective Disorders, 2017)
Keywords: Intervention; Relapse maintenance; Depression; Emotion regulation; Text messages

Examining risk and resilience factors for depression: The role of self-criticism and self-compassion - Ehret, Anna; Joormann, Jutta; Berking, Matthias (Cognition & Emotion, 2015)
Whereas self-criticism has been proposed as an important risk factor for major depressive disorder (MDD), self-compassion has been suggested as a resilience factor that protects against the development and maintenance of depressive episodes. This study aimed to test the hypothesis that frequent self-criticism and low habitual self-compassion are related to concurrent depression and to vulnerability to depression by comparing groups of currently, remitted and never depressed individuals. As expected, both currently and remitted depressed individuals reported higher levels of self-criticism and lower self-compassion than never depressed controls. Individual differences in self-criticism and self-compassion were related to depression status above and beyond additional potential correlates of MDD (i.e., perfectionistic beliefs and cognitions, rumination and overall adaptive emotion regulation). The findings provide support for the idea that increased self-criticism and decreased self-compassion place certain individuals at increased risk for experiencing depression repeatedly or chronically over the course of their lives.
Keywords: Depression; Vulnerability; Self-criticism; Self-compassion

Exploring the Capabilities of a Language Model-Only Approach for Depression Detection in Text Data - Sadeghi, Misha; Egger, Bernhard; Agahi, Reza; Richer, Robert; Capito, Klara; Rupp, Lydia; Gmelch, Lena Marie; Berking, Matthias; Eskofier, Björn (IEEE EMBS International Conference on Biomedical and Health Informatics (BHI), 2023)
Depression is a prevalent and debilitating mental health condition that requires accurate and efficient detection for timely and effective treatment. In this study, we utilized the E-DAIC (Extended Distress Analysis Interview Corpus-Wizard-of-Oz) dataset, an extended version of the DAIC-WOZ dataset, which consists of semi-clinical interviews conducted by an animated virtual interviewer called Ellie, controlled by a human interviewer in another room. With 275 participants, the E-DAIC dataset represents a valuable resource for investigating depression detection methods. Our aim is to predict PHQ-8 scores through text analysis. Leveraging state-of-the-art speech processing, LLM-based text summarization, and a specialized depression detection module, we demonstrate the transformative potential of language data analysis in enhancing depression screening. By overcoming the limitations of manual feature extraction methods, our automated techniques provide a more efficient and effective means of evaluating depression. In our evaluation, we achieve robust accuracy on the development set of the E-DAIC dataset, with a Mean Absolute Error (MAE) of 3.65 in estimating PHQ-8 scores from recorded interviews. This remarkable performance highlights the efficacy of our approach in automatically predicting depression severity. Our research contributes to the growing evidence supporting the use of LLMs in mental health assessment, showcasing the role of innovative technologies in advancing patient care for depression.<br
Keywords: Depression detection; mental health; large language models; text analysis; DAIC dataset; GPT-based models; DepRoBERTa

Exploring the Capabilities of a Language Model-Only Approach for Depression Detection in Text Data - Sadeghi, Misha; Egger, Bernhard; Agahi, Reza; Richer, Robert; Capito, Klara; Rupp, Lydia; Gmelch, Lena Marie; Berking, Matthias; Eskofier, Björn (Deutscher Psychotherapiekongress (DPK), 2024)

Facing depression: evaluating the efficacy of the EmpkinS-EKSpression reappraisal training augmented with facial expressions – protocol of a randomized controlled trial - Keinert, Eva Marie; Schindler-Gmelch, Lena; Rupp, Lydia; Sadeghi, Misha; Capito, Klara; Hager, Malin; Rahimi, Farnaz; Richer, Robert; Egger, Bernhard; Eskofier, Björn; Berking, Matthias (BMC Psychiatry, 2024)
Background Dysfunctional depressogenic cognitions are considered a key factor in the etiology and maintenance of depression. In cognitive behavioral therapy (CBT), the current gold-standard psychotherapeutic treatment for depression, cognitive restructuring techniques are employed to address dysfunctional cognitions. However, high drop-out and non-response rates suggest a need to boost the efficacy of CBT for depression. This might be achieved by enhancing the role of emotional and kinesthetic (i.e., body movement perception) features of interventions. Therefore, we aim to evaluate the efficacy of a cognitive restructuring task augmented with the performance of anti-depressive facial expressions in individuals with and without depression. Further, we aim to investigate to what extent kinesthetic markers are intrinsically associated with and, hence, allow for the detection of, depression. Methods In a four-arm, parallel, single-blind, randomized controlled trial (RCT), we will randomize 128 individuals with depression and 128 matched controls without depression to one of four study conditions: (1) a cognitive reappraisal training (CR); (2) CR enhanced with instructions to display anti-depressive facial expressions (CR + AFE); (3) facial muscle training focusing on anti-depressive facial expressions (AFE); and (4) a sham control condition. One week after diagnostic assessment, a single intervention of 90–120-minute duration will be administered, with a subsequent follow-up two weeks later. Depressed mood will serve as primary outcome. Secondary outcomes will include current positive mood, symptoms of depression, current suicidality, dysfunctional attitudes, automatic thoughts, emotional state, kinesthesia (i.e., facial expression, facial muscle activity, body posture), psychophysiological measures (e.g., heart rate (variability), respiration rate (variability), verbal acoustics), as well as feasibility measures (i.e., treatment integrity, compliance, usability, acceptability). Outcomes will be analyzed with multiple methods, such as hierarchical and conventional linear models and machine learning. Discussion If shown to be feasible and effective, the inclusion of kinesthesia into both psychotherapeutic diagnostics and interventions may be a pivotal step towards the more prompt, efficient, and targeted treatment of individuals with depressio

Facing the Dreaded: Does Mindfulness Facilitate Coping with Distressing Experiences? A Moderator Analysis - Bergomi, Claudia; Ströhle, Gunnar; Michalak, Johannes; Funke, Friedrich; Berking, Matthias (Cognitive Behaviour Therapy, 2013)
Increasing evidence shows that mindfulness is positively related to mental health; however, the nature of this relationship is not fully understood. The current study used structural equation modeling to investigate the hypothesis that mindfulness moderates the association between the occurrence of unavoidable distressing experiences (UDE) and mental health. Participants from a community sample (N = 376) completed the Freiburg Mindfulness Inventory, the Positive and Negative Affect Scale, the Brief Symptom Inventory, the Inventory of Approach and Avoidance Motivation, and the Incongruence Scale. Results indicated that mindfulness moderated the association between unavoidable distressing events and psychopathological symptoms/negative affect. Thus, mindfulness may contribute to enhance the ability to cope with UDE and thus mitigate the detrimental effects of these experiences on mental health. © 2013 Copyright Swedish Association for Behaviour Therapy.
Created from Fastlane, Scopus look-up
Keywords: avoidance; distressing experiences; mental health; mindfulness; moderation

Forgiveness and psychological adjustment following interpersonal transgressions: A longitudinal analysis - Orth, Ulrich; Berking, Matthias; Walker, Nadine; Meier, Laurenz L.; Znoj, Hansjörg (Journal of research in personality, 2008)
Forgiveness is often assumed to be adaptive for psychological adjustment following interpersonal transgressions. Three hundred and forty seven individuals who had experienced a recent interpersonal transgression were surveyed on four occasions over the course of six weeks. Forgiveness was assessed with scales measuring interpersonal avoidance and revenge motivation and psychological adjustment was assessed with scales measuring depression and rumination. Latent growth curve analyses showed that intraindividual changes in forgiveness were positively correlated with changes in adjustment. Latent difference score analyses indicated that adjustment predicted subsequent change in forgiveness, but that forgiveness did not predict subsequent change in adjustment. The results suggest that adjustment facilitates forgiveness, but not that forgiveness facilitates adjustment. © 2007 Elsevier Inc. All rights reserved.
Created from Fastlane, Scopus look-up
Keywords: Forgiveness; Latent difference score analysis; Latent growth curve analysis; Psychological adjustment

For whom are internet-based occupational mental health interventions effective? Moderators of internet-based problem-solving training outcome - Junge, Magdalena N.; Lehr, Dirk; Bockting, Claudi L. H.; Berking, Matthias; Riper, Heleen; Cuijpers, Pim; Ebert, David; Heleen, Riper (Internet Interventions, 2015)
Internet-based problem-solving training (IPST) effectively reduces depressive symptoms in employees. Yet, it is unknown which employees benefit most from this particular treatment. The study aimed to identify predictors and moderators of treatment outcome in IPST offered to employees with depressive symptoms. Within a randomized controlled trial (N = 150), designed to test the effectiveness of IPST, variables that predict and moderate the effects of IPST when compared with a waitlist control group (WLC) were explored. The outcome was change in depression severity, assessed using the Center for Epidemiological Studies Depression Scale (CES-D). Both depression severity and other psychopathological symptoms and potential predictors/moderators were assessed as self-reports at baseline (t1) and in follow-up assessments after seven weeks (t2), three months (t3) and six months (t4). Higher depression severity at baseline predicted improvement in depressive symptomology in follow-up assessments after seven weeks, and three- and six months. Depression severity moderated the effectiveness of IPST assessed at six-month follow-up. Simple slope analyses revealed that the long-term effectiveness of the intervention was more pronounced among participants with high (CES-D range: 33–44, M = 37.0, SD = 3.2) and moderate (CES-D range: 14–32, M = 23.1, SD = 5.6) depression baseline scores, compared to participants displaying low depression baseline scores (CES-D range: 5–13, M = 9.0, SD = 2.2). No indication was found that participants presenting low depression severity at baseline significantly benefitted from IPST in the long-term. IPST might be appropriate for employees with a wide range of different characteristics. While there appears to be no reason to exclude employees with severe depression from Internet-based occupational mental health interventions, for employees low in depression severity, watchful waiting or potentially no intervention should be considered. These findings may not apply to other low-intensity interventions and/or target groups.
Keywords: Depression; Internet-based intervention; Problem-solving therapy; Occupational health; Predictors; Moderators

For whom does it work? Moderators of outcome on the effect of a transdiagnostic Internet-based maintenance treatment after inpatient psychotherapy: Randomized controlled trial - Ebert, David Daniel; Gollwitzer, Mario; Riper, Heleen; Cuijpers, Pim; Baumeister, Harald; Berking, Matthias (Journal of Medical Internet Research, 2013)
Background: Recent studies provide evidence for the effectiveness of Internet-based maintenance treatments for mental disorders. However, it is still unclear which participants might or might not profit from this particular kind of treatment delivery. Objective: The study aimed to identify moderators of treatment outcome in a transdiagnostic Internet-based maintenance treatment (TIMT) offered to patients after inpatient psychotherapy for mental disorders in routine care. Methods: Using data from a randomized controlled trial (N=400) designed to test the effectiveness of TIMT, we performed secondary analyses to identify factors moderating the effects of TIMT (intervention) when compared with those of a treatment-as-usual control condition. TIMT involved an online self-management module, asynchronous patient-therapist communication, a peer support group, and online-based progress monitoring. Participants in the control condition had unstructured access to outpatient psychotherapy, standardized outpatient face-to-face continuation treatment, and psychotropic management. Self-reports of psychopathological symptoms and potential moderators were assessed at the start of inpatient treatment (T1), at discharge from inpatient treatment/start of TIMT (T2), and at 3-month (T3) and 12-month follow-up (T4). Results: Education level, positive outcome expectations, and diagnoses significantly moderated intervention versus control differences regarding changes in outcomes between T2 and T3. Only education level moderated change differences between T2 and T4. The effectiveness of the intervention (vs control) was more pronounced among participants with a low (vs high) education level (T2-T3: B=-0.32, SE 0.16, P=.049; T2-T4: B=-0.42, SE 0.21, P=.049), participants with high (vs low) positive outcome expectations (T2-T3: B=-0.12, SE 0.05, P=.02) and participants with anxiety disorder (vs mood disorder) (T2-T3: B=-0.43, SE 0.21, P=.04). Simple slope analyses revealed that despite some subgroups benefiting less from the intervention than others, all subgroups still benefited significantly. Conclusions: This transdiagnostic Internet-based maintenance treatment might be suitable for a wide range of participants differing in various clinical, motivational, and demographic characteristics. The treatment is especially effective for participants with low education levels. These findings may generalize to other Internet-based maintenance treatments. Trial Registration: International Standard Randomized Controlled Trial Number (ISRCTN): 28632626; http://www.controlled-trials.com/isrctn/pf/ 28632626 (Archived by WebCite at http://www.webcitation.org/6IqZjTLrx). © David Daniel Ebert, Mario Gollwitzer, Heleen Riper, Pim Cuijpers, Harald Baumeister, Matthias Berking.
Created from Fastlane, Scopus look-up
Keywords: Continuation treatment; Guided self-help; Internet-based intervention; Maintenance treatment; Mental disorders/inpatient psychotherapy; Moderators; Predictors; Randomized controlled trial; Relapse prevention; Transdiagnostic treatment

French validation of the Emotion Regulation Skills Questionnaire Validation française du Questionnaire de Compétences en matière de Régulation Émotionnelle - Nardelli, Carla; Montreuil, Tina; Naoufal, Michael; Berking, Matthias; Baeyens, Céline; Bortolon, Catherine (European Review of Applied Psychology-Revue Europeenne De Psychologie Appliquee, 2024)
Background: Emotion regulation (ER) has become the target of multiple clinical interventions, given its transdiagnostic features. The goal of this study was to validate a French version of the Emotion Regulation Skills Questionnaire (ERSQ, Berking & Znoj, 2008), which provides an overview of the ER skills described in the Adaptive Coping with Emotions model. Method: This online study was comprised of different questionnaires designed to analyse the psychometric properties of the ERSQ in both French and Canadian non-clinical populations (n = 658). Results: The nine subscales based on the nine factors show a satisfactory internal consistency. The scale also demonstrates good convergent validity and acceptable test-retest validity. The proposed nine-factor model shows an adequate fit to the data, with all approximate fit indices showing acceptable model fit. Limitation: This online study can be associated with common limits of self-reported measures. Moreover, our results should be replicated in future studies, for example in clinical samples, to validate its discriminant capacity. Conclusions: The French version of the ERSQ can be considered as a reliable instrument for assessing ER skills. Contrary to other related questionnaires, the ERSQ measures multiple dimensions considered as possible targets of psychological interventions.
CRIS-Team Scopus Importer:2024-02-16
Keywords: Assessment; Emotion regulation; Emotion regulation skills; Reliability; Validity

GET.ON Mood Enhancer: efficacy of Internet-based guided self-help compared to psychoeducation for depression: an investigator-blinded randomised controlled trial - Ebert, David; Lehr, Dirk; Baumeister, Harald; Boß, Leif; Riper, Heleen; Cuijpers, Pim; Reins, Jo Annika; Buntrock, Claudia; Berking, Matthias (Trials, 2014)
Background Major depressive disorder (MDD) imposes a considerable disease burden on individuals and societies. A large number of randomised controlled trials (RCTs) have shown the efficacy of Internet-based guided self-help interventions in reducing symptoms of depression. However, study quality varies considerably. The aim of this study is to evaluate the efficacy of a new Internet-based guided self-help intervention (GET.ON Mood Enhancer) compared to online-based psychoeducation in an investigator-blinded RCT. Methods/design A RCT will be conducted to compare the efficacy of GET.ON Mood Enhancer with an active control condition receiving online psychoeducation on depression (OPD). Both treatment groups will have full access to treatment as usual. Adults with MDD (n = 128) will be recruited and randomised to one of the two conditions. Primary outcome will be observer-rated depressive symptoms (HRSD-24) by independent assessors blind to treatment conditions. Secondary outcomes include changes in self-reported depressive symptom severity, anxiety and quality of life. Additionally, potential negative effects of the treatments will systematically be evaluated on several dimensions (for example, symptom deteriorations, attitudes toward seeking psychological help, relationships and stigmatisation). Assessments will take place at baseline, 6 and 12 weeks after randomisation. Discussion This study evaluates a new Internet-based guided self-help intervention for depression using an active control condition (psychoeducation-control) and an independent, blinded outcome evaluation. This study will further enhance the evidence for Internet-based guided self-help interventions for MDD.

Guided internet-based cognitive behavioral therapy for insomnia: Health-economic evaluation from the societal and public health care perspective alongside a randomized controlled trial - Buntrock, Claudia; Lehr, Dirk; Smit, Filip; Horvath, Hanne; Berking, Matthias; Spiegelhalder, Kai; Riper, Heleen; Ebert, David Daniel (Journal of Medical Internet Research, 2021)
Background: The evidence base for internet-based cognitive behavioral therapy for insomnia (iCBT-I) is firm; however, little is known about iCBT-I's health-economic effects. Objective: This study aimed to evaluate the cost-effectiveness and cost-utility of iCBT-I in reducing insomnia among schoolteachers. Methods: Schoolteachers (N=128) with clinically significant insomnia symptoms and work-related rumination were randomized to guided iCBT-I or a wait list control group, both with unrestricted access to treatment as usual. Health care use, patient and family expenditures, and productivity losses were self-assessed and used for costing from a societal and a public health care perspective. Costs were related to symptom-free status (score <8 on the insomnia severity index) and quality-adjusted life years (QALYs) gained. Sampling error was handled using nonparametric bootstrapping. Results: Statistically significant differences favoring the intervention group were found for both health outcomes (symptom-free status yes or no: β=.30; 95% CI 0.16-0.43; QALYs: β=.019, 95% CI 0.01-0.03). From a societal perspective, iCBT-I had a 94% probability of dominating the wait list control for both health outcomes. From a public health care perspective, iCBT-I was more effective but also more expensive than the wait list control, resulting in an incremental cost-effectiveness ratio of €650 per symptom-free individual. In terms of QALYs, the incremental cost-effectiveness ratio was €11, 285. At a willingness-to-pay threshold of €20, 000 per QALY gained, the intervention's probability of being cost-effective was 89%. Conclusions: Our trial indicates that iCBT could be considered as a good value-for-money intervention for insomnia.
CRIS-Team Scopus Importer:2021-06-11
Keywords: Behavior; Cognitive behavioral therapy; Cost-effectiveness; Cost-utility; Economic evaluation; Economics; ICBT-I; Insomnia; Internet-based cognitive behavioural therapy; Perspective; Public health; Sleep

Hair Cortisol Research in Posttraumatic Stress Disorder - 10 Years of Insights and Open Questions. A Systematic Review - Gmelch, Lena Marie; Capito, Klara; Steudte-Schmiedgen, Susann; Kirschbaum, Clemens; Berking, Matthias (Current Neuropharmacology, 2023)
Background: Cortisol is one of the most extensively studied biomarkers in the context of trauma/posttraumatic stress disorder (PTSD). For more than a decade, hair cortisol concentrations (HCC) have been measured in this context, leading to a two-staged dysregulation model. Specifically, an elevated secretion during/immediately after trauma exposure eventually reverts to hyposecretion with increasing time since trauma exposure has been postulated. Objective: The aim of our systematic review was to re-evaluate the two-staged secretion model with regard to the accumulated diagnostic, prognostic, and intervention-related evidence of HCC in lifetime trauma exposure and PTSD. Further, we provide an overview of open questions, particularly with respect to reporting standards and quality criteria. Method: A systematic literature search yielded 5,046 records, of which 31 studies were included. Results: For recent/ongoing (traumatic) stress, the predictions of cortisol hypersecretion could be largely confirmed. However, for the assumed hyposecretion temporally more distal to trauma exposure, the results are more ambiguous. As most studies did not report holistic overviews of trauma history and confounding influences, this may largely be attributable to methodological limitations. Data on the prognostic and intervention-related benefits of HCC remain sparse. Conclusion: Over the last decade, important insights could be gained about long-term cortisol secretion patterns following lifetime trauma exposure and PTSD. This systematic review integrates these insights into an updated secretion model for trauma/PTSD. We conclude with recommendations for improving HCC research in the context of trauma/PTSD in order to answer the remaining open questions. <br
Keywords: Posttraumatic stress disorder; trauma; hair cortisol; diagnostic; prognostic; intervention-related; biomarker

Harnessing multimodal approaches for depression detection using large language models and facial expressions - Sadeghi, Misha; Richer, Robert; Egger, Bernhard; Schindler-Gmelch, Lena; Rupp, Lydia; Rahimi, Farnaz; Berking, Matthias; Eskofier, Björn (npj Mental Health Research, 2024)
Detecting depression is a critical component of mental health diagnosis, and accurate assessment is essential for effective treatment. This study introduces a novel, fully automated approach to predicting depression severity using the E-DAIC dataset. We employ Large Language Models (LLMs) to extract depression-related indicators from interview transcripts, utilizing the Patient Health Questionnaire-8 (PHQ-8) score to train the prediction model. Additionally, facial data extracted from video frames is integrated with textual data to create a multimodal model for depression severity prediction. We evaluate three approaches: text-based features, facial features, and a combination of both. Our findings show the best results are achieved by enhancing text data with speech quality assessment, with a mean absolute error of 2.85 and root mean square error of 4.02. This study underscores the potential of automated depression detection, showing text-only models as robust and effective while paving the way for multimodal analysi
Keywords: Depression detection; mental health assessment; large language models; text analysis; E-DAIC dataset; speech quality assessment; visual features; facial expressions

How to promote usage of telehealth interventions for farmers' mental health? A qualitative study on supporting and hindering aspects for acceptance and satisfaction with a personalized telephone coaching for depression prevention - Thielecke, Janika; Buntrock, Claudia; Freund, Johanna; Braun, Lina; Ebert, David D.; Berking, Matthias; Baumeister, Harald; Titzler, Ingrid (Internet Interventions, 2023)
Low-threshold and remotely delivered preventive interventions, like telephone coaching, are warranted for farmers who experience multiple risk factors for depression, live in underserved areas, and show low help-seeking behavior. Factors facilitating uptake and actual use of effective remote interventions are important to reduce depression disease burden. This study aimed at identifying factors that potentially can influence acceptance of and satisfaction with a telephone coaching in this occupational group. Semi-structured interviews were based on the ‘Unified Theory of Acceptance and Use of Technology’, the ‘Evaluation’, and ‘Discrepancy’ models for satisfaction. Interviews were conducted with 20 of 66 invited participants of a 6-months telephone coaching during an effectiveness or implementation study. Audio-recorded interviews were transcribed and analyzed (deductive-inductive qualitative content analysis). Independent coding by two persons resulted in good agreement (Κ = 0.80). Participants validated results via questionnaire. Overall, 32 supporting (SF) and 14 hindering factors (HF) for acceptance and satisfaction were identified and organized into five dimensions: Coaching result (SF = 9, HF = 3), coach (SF = 9, HF = 1), organization (SF = 5, HF = 2), the telephone as communication medium (SF = 4, HF = 5) and participant characteristics (SF = 5, HF = 3). Most named SFs were ‘Flexible appointment arrangement’ (n = 19/95 %) and ‘low effort’ (n = 17/85 %), while most reported HFs were ‘lack of visual cues’ (n = 12/60 %) and ‘social/professional involvement restricts change process’ (n = 10/50 %). The perceived changes initiated by coaching, a low effort through telephone conduct, and the indicated personalization were identified as important influencing factors on acceptance and satisfaction based on interviewees' statements. Both may be further enhanced by offering choice and advice for delivery formats (e.g., video-calls) and training of coaches in farm-related issues. Study registration: German Clinical Trial Registrations: DRKS00017078 and DRKS00015655.
CRIS-Team Scopus Importer:2023-09-29
Keywords: Acceptance; Depression; Farmers; Interviews; Satisfaction; Telephone coaching

How to reach the Farmers for Participation in digital Prevention Services: 'Lessons learned' from a national Depression Prevention Project - Thielecke, Janika; Freund, Johanna; Buntrock, Claudia; Braun, L.; Baumeister, H.; Berking, Matthias; Ebert, D. D.; Titzler, Ingrid (GESUNDHEITSWESEN, 2022)
CRIS-Team WoS Importer:2022-09-16

Implementing internet- and tele-based interventions to prevent mental health disorders in farmers, foresters and gardeners (ImplementIT): study protocol for the multi-level evaluation of a nationwide project - Freund, Johanna; Titzler, Ingrid; Thielecke, Janika; Braun, Lina; Baumeister, Harald; Berking, Matthias; Ebert, David (BMC Psychiatry, 2020)
BACKGROUND: Farmers are a vulnerable population for developing depression or other mental health disorders due to a variety of risk factors in their work context. Beyond face-to-face resources, preventive internet- and tele-based interventions could extend available treatment options to overcome barriers to care. The German Social Insurance Company for Agriculture, Forestry and Horticulture (SVLFG) implements several guided internet- and mobile-based interventions and personalised tele-based coaching for this specific target group provided by external companies within a nation-wide prevention project for their insured members. The current study aims to evaluate the implementation process and to identify determinants of successful implementation on various individual and organisational levels. METHODS: The current study includes two groups of participants: 1) insured persons with an observable need for prevention services, and 2) staff-participants who are involved in the implementation process. The Reach, Effectiveness, Adoption, Implementation and Maintenance (RE-AIM) framework and the Consolidated Framework for Implementation Research (CFIR) will be used to track and evaluate the implementation process. A mixed-method approach will provide insights on individual and organizational level (e.g. degree of normalization, readiness for change) and helps to identify determinants of successful implementation. In-depth insights on experiences of the participants (e.g. acceptance, satisfaction, barriers and facilitating factors of intervention use) will be yielded through qualitative interviews. Focus groups with field workers provide insights into barriers and facilitators perceived during their consultations. Furthermore, intervention as well as implementation costs will be evaluated. According to the stepwise, national rollout, data collection will occur at baseline and continuously across 24 months. DISCUSSION: The results will show to what extent the implementation of the internet- and tele-based services as a preventive offer will be accepted by the participants and involved employees and which critical implementation aspects will occur within the process. If the implementation of the internet- and tele-based services succeeds, these services may be feasible in the long-term. TRIAL REGISTRATION: German Clinical Trial Registration: DRKS00017078 . Registered on 18.04.2019.
CRIS-Team Scopus Importer:2020-09-11
Keywords: Farmers; Implementation; Internet- and tele-based interventions; Mental health; Prevention; RE-AIM framework

Increasing intentions to use mental health services among university students. Results of a pilot randomized controlled trial within the World Health Organization's World Mental Health International College Student Initiative - Mortier, Philippe; Bruffaerts, Ronny; Alonso, Jordi; Karyotaki, Eirini; Berking, Matthias; Cuijpers, Pim; Kessler, Ronald C.; Auerbach, Randy P.; Baumeister, Harald; Ebert, David; Franke, Marvin; Kählke, Fanny; et al. (International Journal of Methods in Psychiatric Research, 2019)
Keywords: health behavior; risk factors; psychoeducation; public mental health

Increasing the acceptance of internet-based mental health interventions in primary care patients with depressive symptoms. A randomized controlled trial - Ebert, David; Berking, Matthias; Cuijpers, Pim; Lehr, Dirk; M., Pörtner; Baumeister, Harald (Journal of Affective Disorders, 2015)
Conclusion: Primary care patients' acceptance of IBIs for depressive symptoms was low but could be increased significantly using a brief acceptance facilitating intervention on the basis of an informational video. Future studies should further examine the potential of acceptance facilitating interventions for patients and health care providers to exploit the public health impact of IBIs. (C) 2015 Elsevier BM. All rights reserved.
Keywords: Depression; Acceptance; Randomized-controlled trial; Internet-based intervention; Implementation; e-health

Inpatient Cognitive Behavioral Analysis System of Psychotherapy (CBASP) for treatment resistant and chronically depressed patients: adverse effects related to response and relapse - Spies, J.; Zimmermann, J.; Radtke, M.; Becker, M.; Jacobi, Frank; Normann, C.; Berking, Matthias; Brakemeier, E. L. (23rd World Congress on Psychosomatic Medicine, 2015)

Internet and Computer-Based Cognitive Behavioral Therapy for Anxiety and Depression in Youth: A Meta-Analysis of Randomized Controlled Outcome Trials - Ebert, David; Zarski, Anna-Carlotta; Christensen, Helen; Stikkelbroek, Yvonne; Cuijpers, Pim; Berking, Matthias; Heleen, Riper (PLoS ONE, 2015)
Results provide evidence for the efficacy of cCBT in the treatment of anxiety and depressive symptoms in youth. Hence, such interventions may be a promising treatment alternative when evidence based face-to-face treatment is not feasible. Future studies should examine long-term effects of treatments and should focus on obtaining patient-level data from existing studies, to perform an individual patient data meta-analysis.

Internet- and mobile-based intervention for depression in adults with chronic back pain: A health economic evaluation - Paganini, Sarah; Terhorst, Yannik; Sander, Lasse Bosse; Lin, Jiaxi; Schlicker, Sandra; Ebert, David Daniel; Berking, Matthias; Riper, Heleen; Baumeister, Harald (Journal of Affective Disorders, 2022)
Background: Depression and comorbid chronic back pain (CBP) lead to high personal and economic burden. Internet- and mobile-based interventions (IMI) might be a cost-effective adjunct to established interventions. Methods: A health economic evaluation was embedded into an observer-blinded, multicenter RCT (societal and health care perspective). We randomly assigned participants (≥18 years) with CBP and diagnosed depression from 82 orthopedic clinics across Germany to intervention (IG + treatment as usual [TAU]) or TAU control group (CG). The IG received a guided IMI. Primary outcomes were depression response and quality-adjusted life years (QALYs) at 6-months follow-up. Multiple imputation was used to address missing data. Incremental cost-effectiveness/cost-utility ratios (ICER/ICUR) and the probability of being cost-effective at different willingness-to-pay thresholds were calculated. Statistical uncertainty was estimated using bootstrapping techniques (N = 10,000). Results: Between October 2015 and July 2017 210 participants were randomly assigned to IG (n = 105) and CG (n = 105). Depression response did not differ significantly between groups. QALYs were significantly higher in the IG compared to the CG. Taking the societal perspective and assuming a commonly used willingness-to-pay of €34,000/QALY, the intervention's likelihood of being cost-effective was 64%. Limitations: The main limitation is that the study was powered to detect clinical but not health economic differences between groups. Conclusion: The IMI is considered cost-effective (vs. CG) for individuals with depression and CBP (societal perspective). These results are promising when considering the high individual and economic burden of this patient group. Further research is needed to adequately inform political decision makers before implementation into routine care.
CRIS-Team Scopus Importer:2022-07-01
Keywords: Chronic pain; Comorbidity; Cost-effectiveness; Cost-utility; Depressive disorder; E-Health

Internet- and mobile-based psychological interventions for sexual dysfunctions: a systematic review and meta-analysis - Zarski, Anna-Carlotta; Velten, Julia; Knauer, Johannes; Berking, Matthias; Ebert, David Daniel (npj Digital Medicine, 2022)
Sexual dysfunctions are highly prevalent and undertreated. Internet- and mobile-based psychological interventions (IMIs) could be a promising addition to close this treatment gap, given their accessibility, anonymity, and scalability. This systematic review and meta-analysis investigated the efficacy of IMIs for sexual dysfunctions. A comprehensive literature search was conducted in August 2021 on randomized controlled trials investigating the effects of IMIs on sexual functioning and satisfaction compared to a control condition. Twelve RCTs with 14 comparisons were reviewed with six IMIs targeting female and six IMIs targeting male sexual dysfunctions and n = 952 participants were evaluated in the meta-analysis. IMIs were significantly more effective than control conditions (k = 11 waitlist control group, k = 3 online discussion board) at post-treatment for female sexual functioning (g = 0.59, CI: 0.28-0.90, I-2 = 0%) and satisfaction (g = 0.90, CI: 0.02-1.79, I-2 = 82%), and male sexual functioning (g = 0.18, CI: 0.02-0.34, I-2 = 0%). No significant effect was found for male sexual satisfaction (g = 0.69, CI: -0.13-1.51, I-2 = 88%) with substantial heterogeneity in studies. Most studies showed high dropout, with ten studies indicating some concern of risk of bias, and two studies showing high risk of bias. The results suggest that IMIs can be an effective treatment for sexual dysfunctions, although additional high-quality research is needed. Given the limited availability of specialized treatment for sexual dysfunctions and individual preferences for discrete treatment options, IMIs seem to be a valuable addition to routine care, empowering individuals to promote their sexual health on a guided self-help basis.
CRIS-Team WoS Importer:2022-09-23

Internet- and mobile-based stress management for employees with adherence-focused guidance: efficacy and mechanism of change - Ebert, David; Lehr, Dirk; Heber, Elena; Riper, Heleen; Cuijpers, Pim; Berking, Matthias (Scandinavian Journal of Work Environment & Health, 2016)
Conclusion The iSMI investigated in this study was found to be effective in reducing typical symptoms of stress. However, several important work-related health symptoms were not significantly affected by the intervention. Internet-based guided self-help interventions could be an acceptable, effective approach to reduce a range of negative consequences associated with work-related stress. Future studies should investigate the comparative (cost-) effectiveness of guided and unguided stress management interventions.
Keywords: internet intervention; mental health; randomized controlled trial; RCT; work stress; internet intervention; mental health; randomized controlled trial; RCT; work stress

Internet-based approaches in prevention and treatment of depressive symptoms in adolescents and young adults - Wiencke, Carmen; Lehr, Dirk; Ebert, David; Sieland, Bernhard; Riper, Heleen; Berking, Matthias (Praxis der Kinderpsychologie und Kinderpsychiatrie, 2014)
Epidemiological findings indicate that up to 18.5 % of the German adolescents suffer from depressive symptoms and that younger adults display the highest risk for relevant symptoms of depression (9.9 %) within the German adult population. Internet-based interventions have been shown to be useful for preventing and treating depression and are more easily disseminated in internet-savvy generations. Available programs are usually based on principles of cognitive behavioural therapy. They differ significantly with regard to target groups, structure, content, degree of guidance provided by online-coaches and evidence for their efficacy. Whereas some studies could not prove the use of the trainings there are others that show large effect sizes (up to d = 0.84) for the reduction of depressive symptoms. In Germany there are some online counseling programs for children and adolescents in (acute) crises available. However, at this point no structured intervention program for the treatment of depression exists. © Vandenhoeck & Ruprecht GmbH & Co. KG, Göttingen 2014.
Keywords: Adolescents; Depression; E-mental health; Guided self-help; Internet

Internet based cognitive behavioral interventions: State of the art and implementation possibilities in rehabilitation Internetbasierte kognitiv-behaviorale Behandlungsansätze: State of the Art und Einsatzmöglichkeiten in der Rehabilitation - Lin, J.; Ebert, D. D.; Lehr, D.; Berking, Matthias; Baumeister, H. (Rehabilitation, 2013)
Internet-based health interventions (IHIs) provide a way to treat people via the Internet. The spectrum is wide, comprising interventions for mental disorders and somatic diseases as well as health and risk behavior change interventions. Numerous international studies have demonstrated the efficacy of IHIs for the aforementioned areas. Through the resource-saving applications IHIs are cost-efficient, not least suggesting their usefulness for medical rehabilitation. The present overview starts with a description of IHIs with a differentiation of technical-formal and thematic aspects. In doing so, the focus lies primarily on cognitive-behavioral treatment approaches, as the best scientifically investigated IHIs to date. An overview of the empirical evidence of IHIs is given, followed by a discussion of the implementation possibilities in medical rehabilitation. © Georg Thieme Verlag KG Stuttgart - New York.
Created from Fastlane, Scopus look-up
Keywords: cognitive-behavioral therapy; internet therapy; internet-based health interventions; rehabilitation; self-help

Internet-Based Cognitive Behavioral Therapy for Insomnia: A Health Economic Evaluation - Thiart, Hanne; Ebert, David; Lehr, Dirk; Nobis, Stephanie; Buntrock, Claudia; Berking, Matthias; Smit, Filip; Riper, Heleen (Sleep, 2016)
Conclusions: Focusing on sleep improvement using iCBT-I may be a cost-effective strategy in occupational health care.
Keywords: cost-benefit; cost-effectiveness; employer perspective; insomnia; Internet; randomized controlled trial; self-help; cost-benefit; cost-effectiveness; employer perspective; insomnia; Internet; randomized controlled trial; self-help

Internet-Based Guided Self-Help for Vaginal Penetration Difficulties: Results of a Randomized Controlled Pilot Trial - Zarski, Anna-Carlotta; Berking, Matthias; Fackiner, Christina; Rosenau, Christian; Ebert, David (Journal of Sexual Medicine, 2017)
Conclusion: This randomized controlled trial showed promising effects of an internet-based intervention by increasing participants' ability to have intercourse and non-intercourse penetration while experiencing high treatment satisfaction. The WCG also showed improvement, although participants had vaginismus for an average duration of 6 years. Internet-based interventions could be a treatment modality to complement other methods in stepped care for vaginal penetration difficulties. Copyright (C) 2017, International Society for Sexual Medicine. Published by Elsevier Inc. All rights reserved.
Keywords: Vaginismus; Genito-Pelvic Pain/Penetration Disorder; Sexual Dysfunction Disorder; Female Sexual Functioning; Internet Intervention; Randomized Controlled Trial

Internet-based treatment of major depression for patients on a waiting list for inpatient psychotherapy: Protocol for a multi-centre randomised controlled trial - Reins, Jo A.; Ebert, David D.; Lehr, Dirk; Riper, Heleen; Cuijpers, Pim; Berking, Matthias (BMC Psychiatry, 2013)
Background: Major depressive disorder (MDD) is a prevalent and severe disorder. Although effective treatments for MDD are available, many patients remain untreated, mainly because of insufficient treatment capacities in the health care system. Resulting waiting periods are often associated with prolonged suffering and impairment as well as a higher risk of chronification. Web-based interventions may help to alleviate these problems. Numerous studies provided evidence for the efficacy of web-based interventions for depression. The aim of this study is to evaluate a new web-based guided self-help intervention (GET.ON-Mood Enhancer-WL) specifically developed for patients waiting to commence inpatient therapy for MDD.Methods: In a two-armed randomised controlled trial (n = 200), the web-based guided intervention GET.ON-Mood Enhancer-WL in addition to treatment as usual (TAU) will be compared with TAU alone. The intervention contains six modules (psycho education, behavioural activation I & II, problem solving I & II, and preparation for subsequent inpatient depression therapy). The participants will be supported by an e-coach, who will provide written feedback after each module. Inclusion criteria include a diagnosis of MDD assessed with a structured clinical interview [SCID] and a waiting period of at least three weeks before start of inpatient treatment. The primary outcome is observer-rated depressive symptom severity (HRSD24). Further (explorative) questions include whether remission will be achieved earlier and by more patients during inpatient therapy because of the web-based preparatory intervention.Discussion: If GET.ON-Mood Enhancer-WL is proven to be effective, patients may start inpatient therapy with reduced depressive symptom severity, ideally leading to higher remission rates, shortened inpatient therapy, reduced costs, and decreased waiting times.Trial registration: German Clinical Trial Registration (DRKS): DRKS00004708. © 2013 Reins et al.; licensee BioMed Central Ltd.
Created from Fastlane, Scopus look-up
Keywords: Inpatient treatment; Internet therapy; Major depression; Remission; Waiting time

Internet interventions for mental health in university students: A systematic review and meta-analysis. - Harrer, Mathias; Adam, Sophia; Baumeister, Harald; Cuijpers, Pim; Karyotaki, Eirini; Auerbach, Randy P.; Kessler, Ronald C.; Bruffaerts, Ronny; Berking, Matthias; Ebert, David D. (International Journal of Methods in Psychiatric Research, 2018)
Mental health disorders are highly prevalent among university students. Universities could be an optimal setting to provide evidence-based care through the Internet. As part of the World Mental Health International College Student initiative, this systematic review and meta-analysis synthesizes data on the efficacy of Internet-based interventions for university students' mental health. A systematic literature search of bibliographical databases (CENTRAL, MEDLINE, and PsycINFO) for randomized trials examining psychological interventions for the mental health (depression, anxiety, stress, sleep problems, and eating disorder symptoms), well-being, and functioning of university students was performed through April 30, 2018. Forty-eight studies were included. Twenty-three studies (48%) were rated to have low risk of bias. Small intervention effects were found on depression (g = 0.18, 95% confidence interval [CI; 0.08, 0.27]), anxiety (g = 0.27, 95% CI [0.13, 0.40]), and stress (g = 0.20, 95% CI [0.02, 0.38]). Moderate effects were found on eating disorder symptoms (g = 0.52, 95% CI [0.22-0.83]) and role functioning (g = 0.41, 95% CI [0.26, 0.56]). Effects on well-being were non-significant (g = 0.15, 95% CI [-0.20, 0.50]). Heterogeneity was moderate to substantial in many analyses. After adjusting for publication bias, effects on anxiety were not significant anymore. Internet interventions for university students' mental health can have significant small-to-moderate effects on a range of conditions. However, more research is needed to determine student subsets for which Internet-based interventions are most effective and to explore ways to increase treatment effectiveness. OBJECTIVES METHOD RESULTS DISCUSSION

Internet- und mobilisierte Interventionen zur Präventionen Behandlung psychischer Störungen - Ebert, David; Zarski, Anna-Carlotta; Berking, Matthias; Baumeister, Harald (eHealth in Deutschland, 2016)

Is the association between various emotion-regulation skills and mental health mediated by the ability to modify emotions? Results from two cross-sectional studies - Berking, Matthias; Poppe, Christine; Luhmann, Maike; Wupperman, Peggilee; Jaggi, Verena; Seifritz, Erich (Journal of Behavior Therapy and Experimental Psychiatry, 2012)
Background and objectives: In order to clarify mechanisms underlying the association between emotion regulation and psychopathology, we tested whether the ability to modify negative emotions mediates the associations of other emotion-regulation skills with psychopathological symptoms in two studies. Methods: The first study included 151 college students; the second included 121 psychiatric inpatients. Bootstrapping-enhanced mediation analyses were utilized to assess associations between self-reports of emotion-regulation skills and psychopathology, as well as potential mediation effects. Results: In both samples, the ability to modify emotions completely mediated the association between symptoms and skills for most skills, but not for the skill of accepting/tolerating negative emotions. Limitations: Major limitations include the use of a cross-sectional design as well as exclusive use of self-report data. Conclusions: The ability to modify negative emotions may be the common pathway by which many emotion-regulation skills exert their influence on mental health; however, the skill of accepting/tolerating negative emotions may be beneficial to mental health regardless of whether or not it facilitates modification of emotions. © 2011 Elsevier Ltd. All rights reserved.
Created from Fastlane, Scopus look-up
Keywords: Emotion regulation; Mediation; Psychopathology; Skills

Koordination der Forschung an Hochschulambulanzen für Psychotherapie - Hoyer, Juergen; Velten, Julia; Benecke, Cord; Berking, Matthias; Heinrichs, Nina; In-Albon, Tina; Lincoln, Tania; Lutz, Wolfgang; Schlarb, Angelika; Schoettke, Henning; Willutzki, Ulrike; Margraf, Juergen (Zeitschrift für Klinische Psychologie und Psychotherapie, 2015)
Background: Outpatient university clinics for psychotherapy (as they have been established in accordance with the German psychotherapy law of 1999) are important facilitators of psychotherapy research. These clinics gather a considerable amount of data on therapy outcome as well as on patient and therapist characteristics. Setting up closer research cooperation between clinics offers the opportunity to systematically analyze and evaluate data. Objective: To present the results of a survey that assessed the most relevant features of outpatient university clinics in Germany. Based on our results, we propose recommendations for an improved integration of the data. Method: We identified and contacted N = 53 outpatient university clinics in Germany. The clinics received a questionnaire that assessed the number of patients treated per year, the instruments used for clinical psychological assessment, and the measurements for general psychological distress and disorder-specific symptoms. Results: The response rate was 100%. Overall, about 10,000 new patients children, adolescents, and adults are treated in these clinics per year. Instruments used for diagnostic purposes and for assessing general psychological distress are highly comparable, whereas a variety of different measurements for disorder-specific symptoms are in use. The software for handling these data is diverse and to some extent incompatible. Conclusion: We highlight the opportunities and challenges associated with the implementation of such research collaboration.
Keywords: psychotherapy research; health care research; outpatient clinics for psychotherapy; diagnostics of mental disorders

Let it go – A randomized controlled pilot study exploring the utility of sadness in an emotion-based approach-avoidance modification training in the context of stress - Rupp, Lydia; Keinert, Eva Marie; Böhme, Stephanie; Schindler-Gmelch, Lena; Schuller, Björn; Eskofier, Björn; Berking, Matthias (52. Kongress der European Association for Behavioral and Cognitive Therapies, 2022)

Let it go – A randomized controlled pilot study exploring the utility of sadness in an emotion-based approach-avoidance modification training in the context of stress - Rupp, Lydia; Keinert, Eva Marie; Böhme, Stephanie; Schindler-Gmelch, Lena; Schuller, Björn W.; Eskofier, Björn; Berking, Matthias (Kongress der Deutschen Gesellschaft für Verhaltensmedizin, 2022)

Let It Go – A Randomized Controlled Pilot Study Exploring the Utility of Sadness in an Emotion-Based Approach-Avoidance Modification Training in the Context of Stress - Rupp, Lydia; Keinert, Eva Marie; Böhme, Stephanie; Gmelch, Lena Marie; Streit, Hannah; Schuller, Björn W.; Eskofier, Björn; Berking, Matthias (Deutscher Psychotherapie Kongress, 2022)

Log in and breathe out: Efficacy and cost-effectiveness of an online sleep training for teachers affected by work-related strain - study protocol for a randomized controlled trial - Thiart, Hanne; Lehr, Dirk; Ebert, David Danie; Sieland, Bernhard; Berking, Matthias; Riper, Heleen (Trials, 2013)
Background: Insomnia and work-related stress often co-occur. Both are associated with personal distress and diminished general functioning, as well as substantial socio-economic costs due to, for example, reduced productivity at the work place and absenteeism. Insomnia complaints by people experiencing work-related stress are correlated with a deficient cognitive detachment from work. Diffuse boundaries between work and private life can additionally complicate the use of recreational activities that facilitate cognitive detachment.Cognitive behavioral therapy for insomnia is effective but rarely implemented. Internet-based cognitive behavioral therapy for insomnia could potentially reduce this deficit given its demonstrated effectiveness. Less is known, however, about the efficacy of internet-based cognitive behavioral therapy for insomnia in populations affected by high work stress. Thus, the aim of the present study is to evaluate the efficacy and cost-effectiveness of a newly developed, guided online training which is based on Cognitive Behavioral Therapy for insomnia and tailored to teachers affected by occupational stress.Methods/Design: In a two-arm randomized controlled trial (N = 128), the effects of a guided online sleep training will be compared to a waitlist-control condition. German teachers with significant clinical insomnia complaints (Insomnia Severity Index ≥15) and work-related rumination (Irritation Scale, subscale Cognitive Irritation ≥15) will be included in the study. The primary outcome measure will be insomnia severity. Additionally, an economic evaluation from a societal perspective will be conducted. Data from the intention-to-treat sample will be analyzed two and six months after randomization.Discussion: To the best of our knowledge, this is the first study to evaluate an online sleep training tailored to a specific population with work stress, that is, teachers. If this type of intervention is effective, it could reduce the paucity of cognitive behavioral therapy for insomnia and augment the support for teachers in coping with their insomnia problems.Trial registration: German Clinical Trial Register (DRKS): DRKS00004700. © 2013 Thiart et al.; licensee BioMed Central Ltd.
Created from Fastlane, Scopus look-up
Keywords: CBT-I; Cost-effectiveness; Insomnia; Internet; Occupational health; Stress; Teachers

Log in and breathe out: internet-based recovery training for sleepless employees with work-related strain - results of a randomized controlled trial - Thiart, Hanne; Lehr, Dirk; Ebert, David; Berking, Matthias; Heleen, Riper (Scandinavian Journal of Work Environment & Health, 2015)
Objectives The primary purpose of this randomized controlled trial (RCT) was to evaluate the efficacy of a guided internet-based recovery training for employees who suffer from both work-related strain and sleep problems (GET.ON Recovery). The recovery training consisted of six lessons, employing well-established methods from cognitive behavioral therapy for insomnia (CBT-I) such as sleep restriction, stimulus control, and hygiene interventions as well as techniques targeted at reducing rumination and promoting recreational activities. Methods In a two-arm RCT (N=128), the effects of GET.ON Recovery were compared to a waitlist-control condition (WLC) on the basis of intention-to-treat analyses. German teachers with clinical insomnia complaints (Insomnia Severity Index =15) and work-related rumination (Irritation Scale, cognitive irritation subscale =15) were included. The primary outcome measure was insomnia severity. Results Analyses of covariance (ANCOVA) revealed that, compared to the WLC, insomnia severity of the intervention group decreased significantly stronger (F=74.11, P<0.001) with a d=1.45 [95% confidence interval (95% CI) 1.06–1.84] The number needed to treat (NNT) was <2 for reliable change and NNT <4 for reduction in expert-rated diagnosis of primary insomnia. Conclusion The training significantly reduces sleep problems and fosters mental detachment from work and recreational behavior among adult stressed employees at post-test and 6-months follow up. Given the low threshold access this training could reach out to a large group of stressed employees when results are replicated in other studies.
Keywords: CBT-I; cognitive behavioral therapy for insomnia; guided self-help; insomnia; internet; internet-based training; occupational health; online; randomized controlled trial; recovery; recovery training; recreation; sleepless; sleepless employee; stress; teacher

Lower Emotion Regulation Competencies Mediate the Association between Impulsivity and Craving during Alcohol Withdrawal Treatment - Reichl, Daniela; Enewoldsen, Niklas; Weisel, Kiona; Saur, Sebastian; Fuhrmann, Lukas; Lang, Catharina; Berking, Matthias; Zink, Mathias; Ahnert, Andreas; Falkai, Peter; Kraus, Thomas; Hillemacher, Thomas; et al. (Substance Use & Misuse, 2022)
There is evidence that craving mediates the relationship between Impulsive Personality Traits (IPTs) and relapse during the treatment of an Alcohol Use Disorder (AUD). To provide tailored interventions, a deeper understanding of the relation between IPTs and craving, namely mediating processes, is important. Based on previous literature, we proposed that lower emotion regulation competencies mediate the relation between attentional as well as non-planning IPTs and craving. To investigate these interrelations, we used data from the baseline assessment (n = 320) of the SmartAssistEntz project (pre-registered in the German Clinical Trials Register [DRKS00017700]). Inpatients with a primary AUD diagnosis were interviewed using standardized self-report measures (IPTs: BIS-15, emotion regulation competencies: ERSQ, craving: OCDS-G short version) during their withdrawal treatment. Indirect effects were calculated using the SPSS macro PROCESS v3.5. Attentional as well as non-planning, but not motor, IPTs were associated with craving. Emotion regulation competencies mediated the relationship between attentional as well as non-planning IPTs and craving. Given their mediating role in the present study, it is interesting to investigate if addressing emotion regulation competencies can mitigate the negative influences of attentional and non-planning IPTs. The direct effect of attentional IPTs implicates alternate mediating processes, which should also be investigated in future research.
CRIS-Team Scopus Importer:2022-03-04
Keywords: alcohol use disorder; attentional; AUD; impulse control; indirect; Motor; non-planning; withdrawal treatment

Method Paper of a Project for Coordinating Research at the University Outpatient Clinics for Psychotherapy in Germany - Velten, Julia; Margraf, Juergen; Benecke, Cord; Berking, Matthias; In-Albon, Tina; Lincoln, Tania; Lutz, Wolfgang; Schlarb, Angelika; Schoettke, Henning; Willutzki, Ulrike; Hoyer, Juergen (Zeitschrift für Klinische Psychologie und Psychotherapie, 2017)
University outpatient clinics are important facilitators of psychological treatments for children, adolescents, and adults with diverse mental disorders and are important contributors to psychotherapy research in Germany. Since 2013, a steering committee has initiated and realized a project aiming to coordinate research efforts in these clinics. In 2016, unith. ev, a network of university training centers for psychotherapy, took over the sponsorship of this project. The main goal of the project is to aggregate and analyze longitudinal treatment data - including patient, therapist, and treatment characteristics - across all participating outpatient clinics. The start of data assessment is planned for 2018. This paper describes legal, methodological, and technical challenges, the current state of the project, as well as a pilot study planned for 2017.
Keywords: psychotherapy research; health-care research; outpatient clinics for psychological therapy; assessment of mental disorders

Mindfulness and modification therapy for behavioral dysregulation: Results from a pilot study targeting alcohol use and aggression in women - Wupperman, Peggilee; Marlatt, G. Alan; Cunningham, Amy; Bowen, Sarah; Berking, Matthias; Mulvihill-Rivera, Nicole; Easton, Caroline (Journal of Clinical Psychology, 2012)
Objectives: Increasing evidence suggests that deficits in mindfulness (awareness, attentiveness, and acceptance of the present moment) play a role in a range of disorders involving behavioral dysregulation. This paper adds to that literature by describing a transdiagnostic psychotherapy (Mindfulness & Modification Therapy; MMT) developed to target behavioral dysregulation. Design: An open-treatment pilot-trial investigated the feasibility, acceptability, and pre-post effects of MMT targeting women (N = 14) court-referred for alcohol abuse/dependence and aggression. Results: Pre-post comparisons revealed significant decreases in alcohol use, drug use, and aggression. In addition, the retention rate was 93%. Conclusion: Preliminary evidence suggests that MMT is a feasible and acceptable treatment that decreases dysregulated behaviors such as substance use and aggression, while also potentially increasing retention. © 2011 Wiley Periodicals, Inc.
Created from Fastlane, Scopus look-up
Keywords: Aggression; Anger; Behavior dysregulation; Emotion regulation; Intervention; Mindfulness; Substance; Transdiagnostic

Mit einem «Warum» im Herzen lässt sich fast jedes «Wie» ertragen: Psychotherapeutische Entschlussförderung - Margraf, Matthias; Berking, Matthias (Verhaltenstherapie, 2005)
Background: Behavioral changes often involve a conflict between aversive short-term and positive long-term consequences for the patients. These conflicts often have a negative impact on the accomplishment of behavioral changes planned and agreed upon in therapy. The objective of this study is to clarify whether the probability of patients accomplishing planned behavior changes can be increased by fostering motivational and volitional pro-cesses (decision making). Methods: Based on general motivational approaches, the prescriptive commitment model 'PRAEMO' was developed. From this model the commitment enhancing intervention 'EFI' was deduced and its efficacy exemplarily evaluated in a sample of 63 inpatients with assertiveness skills deficits in a randomized controlled design. Results: The rate of patients, who after discharge actually performed an assertiveness behavior that had been planned in therapy, was significantly higher in the decision-enhancing condition EFI (91%) than in the control condition with a conventional cognitive-behavioral intervention (66%). Conclusions: Starting from a thorough analysis of the commitment process, effective commitment-enhancing interventions can be deduced. These help patients to effectively accomplish planned behavior changes. © 2005 S. Karger GmbH.
Created from Fastlane, Scopus look-up
Keywords: Commitment; Decision-making; Motivational enhancement; Psychotherapy; Volition

Modifying dysfunctional beliefs with emotion-enhanced smartphone interventions: Pilot study of an emotion-based approach-avoidance modification training for individuals with elevated stress - Keinert, Eva Marie; Böhme, Stephanie; Schindler-Gmelch, Lena; Streit, Hannah; Rupp, Lydia; Eskofier, Björn; Berking, Matthias (52. Kongress der European Association for Behavioral and Cognitive Therapies, 2022)

MOOD AND SLEEP RECIPROCALLY REINFORCE EACH OTHER OVER THE COURSE OF TREATMENT FOR MAJOR DEPRESSIVE DISORDER - Hannig, Wiebke; Radkovsky, Anna; Wirtz, Carolin Maria; Ebert, David; Bockting, Claudia; Berking, Matthias (Psychosomatic Medicine, 2014)

Multimodal, Valence-enhanced Approach-Avoidance Modification Training in Social Phobia and other Mental Disorders: Study protocol of Seven Randomized Controlled Trials - Streit, Hannah; Beitner, Lena; Rupp, Lydia; Keinert, Eva Marie; Meixner, Marie; Wichmann, Lenka; Hager, Malin; Eskofier, Björn; Schuller, Björn W.; Berking, Matthias (2. Deutscher Psychotherapie Kongress, 2023)

Negative affect as mediator between emotion regulation and medically unexplained symptoms - Schwarz, Jeanine; Rief, Winfried; Radkovsky, Anna; Berking, Matthias; Kleinstaeuber, Maria (Journal of psychosomatic research, 2017)
Keywords: Emotion regulation; Medically unexplained symptoms; Anxiety; Depression

Negative Effects in digital Interventions: Results from an Implementation Project (ImplementIT) for the Prevention of Depression in Farmers - Freund, Johanna; Titzler, Ingrid; Thielecke, Janika; Braun, L.; Baumeister, H.; Berking, Matthias; Ebert, David (GESUNDHEITSWESEN, 2022)
CRIS-Team WoS Importer:2022-09-16

Negative Effekte bei digitalen Interventionen: Ergebnisse aus einem Implementierungsprojekt (ImplementIT) zur Prävention von Depression bei Landwirt*innen - Freund, Johanna; Titzler, Ingrid; Thielecke, Janika; Braun, Lina; Baumeister, Harald; Berking, Matthias; Ebert, David Daniel (Gesundheitswesen, 2022)
Depressive Störungen haben erhebliche Auswirkungen auf den Einzelnen und die Gesellschaft, weshalb präventive Maßnahmen sehr bedeutsam sind. Landwirt*innen und verwandte Berufsgruppen sind vielen Risikofaktoren für psychische Erkrankungen ausgesetzt. Deshalb wird das Potenzial von Gesundheitsangeboten wie maßgeschneiderte internet-basierte Interventionen (IBIs) sowie eines Telefoncoachings (TC) im nationalen Modellvorhaben „Mit uns im Gleichgewicht“ der Sozialversicherung für Landwirtschaft, Forsten und Gartenbau (SVLFG) evaluiert. Nur wenig ist derzeit über das Risiko digitaler Präventionsangebote bekannt. Ziel der Implementierungsstudie ist daher die Untersuchung der von Teilnehmenden berichteten negativen Effekte der internet- und tele-basierten Interventionen.<br

Niedrigschwellige Intervention zur Reduktion sozialer Ängste: Entwicklung einer Smartphone-basierten Intervention unter Einbezug von Betroffenen - Fuhrmann, Lukas; Berking, Matthias (Gesundheitswesen, 2019)
Viele Betroffene einer sozialen Angststörung (SAS) leiden Jahrzehnte unter starken privaten und beruflichen Einschränkungen bis sie überhaupt in Erwägung ziehen, professionelle Hilfe aufzusuchen. Ein vielversprechender Ansatz könnten niedrigschwellige, schnell verfügbare, anonym nutzbare und in den Alltag integrierbare Smartphone-basierte Interventionen (SBI) sein. Bisher erforschte SBIs zur SAS wurden a) aus Internet-basierten Interventionen übernommen und b) haben keine Betroffenen in die Interventionsentwicklung involviert. Im Rahmen dieses Vortrages soll daher unter Berücksichtigung von Rückmeldungen Betroffener eine genuin fürs Smartphone erstellte SBI vorgestellt werden.<br

Noise Robust Recognition of Depression Status and Treatment Response from Speech via Unsupervised Feature Aggregation - Gerczuk, Maurice; Amiriparian, Shahin; Kathan, Alexander; Bauer, Jonathan; Berking, Matthias; Schuller, Björn W. (2023 45th Annual International Conference of the IEEE Engineering in Medicine & Biology Society (EMBC), 2023)
In the presented work, we utilise a noisy dataset of clinical interviews with depression patients conducted over the telephone for the purpose of depression classification and automated detection of treatment response. Compared to most previous studies dealing with depression recognition from speech, our data set does not include a healthy group of subjects that have never been diagnosed with depression. Furthermore, it contains measurements at different time points for individual subjects, making it suitable for machine learning-based detection of treatment response. In our experiments, we make use of an unsupervised feature quantisation and aggregation method achieving 69.2% Unweighted Average Recall (UAR) when classifying whether patients are currently in remission or experiencing a major depressive episode (MDE). The performance of our model matches cutoff-based classification via Hamilton Rating Scale for Depression (HRSD) scores. Finally, we show that using speech samples, we can detect response to treatment with a UAR of 68.1%.
CRIS-Team Scopus Importer:2024-12-16

Nutzung von Anschlussmaßnahmen nach stationärem Alkoholentzug: Annahmen zum Stand der Vernetzung im deutschen Suchthilfesystem - Reichl, Daniela; Enewoldsen, Niklas; Tegethoff, Paulina; Gendlina, Taisia; Saur, Sebastian; Lang, Catharina; Fuhrmann, Lukas; Weisel, Kiona; Berking, Matthias; Zink, Mathias; Ahnert, Andreas; Falkai, Peter; et al. (Sucht, 2023)
Aims: The present study addresses potential problems with treatment transition by investigating the use of aftercare treatments by inpatients after alcohol withdrawal treatment without immediate transition to rehabilitation. Methods: We analyzed the control group of the SmartAssistEntz project. Therefor, 181 individuals were interviewed three and six weeks, as well as three and six months after their withdrawal treatment, assessing information regarding the use and evaluation of different aftercare treatments. Results: Over the course of the study, more than half of the participants reported using at least one aftercare treatment. Mostly and most continuously used were drug counseling offers (20-35 % of the participants). Rehabilitation treatments were reported by 8-14 % of the participants six weeks after withdrawal treatment, and by 27-33 % six months thereafter. The treatments were mostly considered to be "helpful", whereby self-help groups performed worst. The reason for the lack of aftercare was mostly waiting time (12-22 % of the cases). The use of rehabilitation treatment during the first three months after withdrawal treatment was associated with a reduced risk of relapse. Conclusions: Particularly drug counseling offers seem to be a low-threshold and subjectively helpful measure following inpatient withdrawal treatment. At the same time, regarding abstinence, the visit of rehabilitation treatments seems to be decisive. Thus, their use should be promoted more intensely.
CRIS-Team Scopus Importer:2023-12-01
Keywords: aftercare treatment; alcohol; health care; withdrawal treatment

Online intervention for prevention of major depression: In Reply - Ebert, David; Buntrock, Claudia; Cuijpers, Pim; Berking, Matthias (Journal of the American Medical Association, 2016)

Optimizing speech elicitation tasks for machine learning-based depression assessment - Bauer, Jonathan; Gerczuk, Maurice; Schuller, Björn W.; Berking, Matthias (Human Factors in Design, Engineering, and Computing, 2024)
THEORETICAL BACKGROUND: The field of machine learning-based speech analysis may provide unobtrusive, time-efficient and cost-effective ways of automated depression assessment. Systematically optimizing speech elicitation tasks may further improve the accuracy of this approach. We hypothesized that machine learning-based depression classification would perform better if trained on recordings of individuals reading anti-depressive statements with the instruction to intone them as convincingly as possible compared to readings of anti-depressive statements without instructions regarding intonation.METHODS: To test this hypothesis, we recruited a sample of 48 clinically depressed individuals, 48 sub-clinically depressed individuals, and 48 non-depressed individuals. Participants from each group were randomly allocated to either the experimental or the control condition. In both conditions, participants read aloud scripted anti-depressive self-statements. Participants in the experimental condition received instructions to heighten the prosodic expression of conviction in their voice, whereas participants in the control condition received no such instructions. Separate classification models aimed at detecting current depression were trained for each condition and with a selection of different machine learning methods. RESULTS: We found that models trained on data from the experimental condition were more accurate and reliable than those trained on data from the control condition. While the former models reached balanced accuracies between 65–76%, the latter only reached balanced accuracies between 36–61%.DISCUSSION: Our results suggest that features of speech elicitation tasks have substantial influence on model performance for automated depression classification. The present findings highlight that speech elicitation tasks including voice modulation instructions can improve the validity and reliability of machine learning-based depression classificatio
Keywords: Depression Assessment; Machine Learning; Voice; Speech; Major Depressive Disorder

Overcome procrastination: Enhancing emotion regulation skills reduce procrastination - Eckert, Marcus; Ebert, David; Lehr, Dirk; Sieland, Bernhard; Berking, Matthias (Learning and individual differences, 2016)
In a first study, cross-sectional analyses indicated that ER skills and procrastination were associated and that these connections were mediated by the ability to tolerate aversive emotions. In a second study, cross lagged panel analyses showed that (1) the ability to modify aversive emotions reduced subsequent procrastination and that (2) procrastination affected the subsequent ability to tolerate aversive emotions. Finally, in a third study, a two-arm randomized control trial (RCT) was conducted. Results indicated that systematic training of the ER skills tolerate and modify aversive emotions reduced procrastination. Thus, in order to overcome procrastination, emotion-focused strategies should be considered. (C) 2016 The Authors. Published by Elsevier Inc.
Keywords: Procrastination; Emotion regulation; Emotion-focused intervention; Training; Procrastination; Emotion regulation; Emotion-focused intervention; Training

Patient-Centered Design of an e-Mental Health App - Glomann, Leonhard; Hager, Viktoria; Lukas, Christian; Berking, Matthias (Advances in Artificial Intelligence, Software and Systems Engineering, 2019)
Clinically diagnosed patients who suffer psychological illnesses are usually well supported during ambulatory treatments. Once back in their personal environment, the likelihood increases for them to relapse into past conscious or subconscious habitual patterns. The key to a successful and long-lasting medical attendance is regarded as an individually tailored and constantly available support. In this respect, an e-Mental Health app, acting as a constant companion, is envisaged to support an ongoing personal treatment of a patient during or after an ambulatory treatment. As part of the "mindtastic" project, the app "mindtastic Phoenix" is being created in a cooperation between the University of Erlangen-Nurnberg's Chair of Clinical Psychology and Psychotherapy, the related information technology department and the service design company LINC Interactionarchitects. This paper describes the design process of this e-Mental Health app and highlights the deviations from the design process of conventional apps.
Keywords: eHealth; mHealth; Mental health; Interdisciplinary; Human-Centered Design; Patient-Centered Design

Patientenziele in der Psychotherapie - Michalak, Johannes; Grosse Holtforth, Martin; Berking, Matthias (Psychotherapeut, 2007)
The present article gives an overview of current research on goals of psychotherapy clients. It mainly focuses on four aspects: (1) basic research on personal goals, (2) general life goals of clients and how they relate to psychopathology, (3) explicit treatment goals, (4) goal-centered psychotherapeutic interventions. The major aims of the article are to show how basic research has influenced clinical research and to illustrate the therapeutic implications of these findings. © 2006 Springer Medizin Verlag.
Created from Fastlane, Scopus look-up
Keywords: Concept of goals in psychotherapy; General and specific goals; Goal-centered psychotherapy; Goals and psychopathology

Patient's experience with blended video- and internet based cognitive behavioural therapy service in routine care - Etzelmueller, Anne; Radkovsky, Anna; Hannig, Wiebke; Berking, Matthias; Ebert, David (Internet Interventions, 2018)
Keywords: Patient's experience; Routine care; Depression; Internet-based self-help; Video-based psychotherapy; Blended therapy

Personalised Deep Learning for Monitoring Depressed Mood from Speech - Gerczuk, Maurice; Triantafyllopoulos, Andreas; Amiriparian, Shahin; Kathan, Alexander; Bauer, Jonathan; Berking, Matthias; Schuller, Björn (2022 10th E-Health and Bioengineering Conference, EHB 2022, 2022)
We utilise a longitudinal dataset of 17 526 speech samples collected from 30 patients with major depressive disorder and 11 sub-clinically depressed individuals to perform a personalised prediction of depressed mood. The data has been recorded via a smartphone app over a two-week ecological momentary assessment with three recording sessions per day. Each session's speech samples are accompanied by a self-assessed rating on the discrete visual analogue mood scale (VAMS) from 0-10. As these ratings are highly subjective, a personalised machine learning method is leveraged. For this purpose, the beginning of the recording period is utilised to train both a shared model backbone, and adapt personalised layers added at the end to each speaker's speech. Our approach yields a Spearman's correlation coefficient (ρ) of 0.79 on the test set, compared to the non-personalised baseline of ρ=0.61. Furthermore, we analyse our results with regard to the type of speech sample – reading three depression-related questions, answering them, and freely formulating an uplifting spontaneous thought. Here, we find that personalisation boosts performance across all types, especially for the fixed content question readings. Overall, our work highlights the efficacy of personalised machine learning for depressed mood monitoring.
Created from Fastlane, Scopus look-up
Keywords: computational paralinguistics; depression; digital health; personalisation

Preventing Depression in Adults With Subthreshold Depression: Health-Economic Evaluation Alongside a Pragmatic Randomized Controlled Trial of a Web-Based Intervention - Buntrock, Claudia; Berking, Matthias; Smit, Filip; Lehr, Dirk; Nobis, Stephanie; Riper, Heleen; Cuijpers, Pim; Ebert, David (Journal of Medical Internet Research, 2017)
Background: Psychological interventions for the prevention of depression might be a cost-effective way to reduce the burden associated with depressive disorders. Objective: To evaluate the cost-effectiveness of a Web-based guided self-help intervention to prevent major depressive disorder (MDD) in people with subthreshold depression (sD). Methods: A pragmatic randomized controlled trial was conducted with follow-up at 12 months. Participants were recruited from the general population via a large statutory health insurance company and an open access website. Participants were randomized to a Web-based guided self-help intervention (ie, cognitive-behavioral therapy and problem-solving therapy assisted by supervised graduate students or health care professionals) in addition to usual care or to usual care supplemented with Web-based psycho-education (enhanced usual care). Depression-free years (DFYs) were assessed by blinded diagnostic raters using the telephone-administered Structured Clinical Interview for DSM-IV Axis Disorders at 6- and 12-month follow-up, covering the period to the previous assessment. Costs were self-assessed through a questionnaire. Costs measured from a societal and health care perspective were related to DFYs and quality-adjusted life years (QALYs). Results: In total, 406 participants were enrolled in the trial. The mean treatment duration was 5.84 (SD 4.37) weeks. On average, participants completed 4.93 of 6 sessions. Significantly more DFYs were gained in the intervention group (0.82 vs 0.70). Likewise, QALY health gains were in favor of the intervention, but only statistically significant when measured with the more sensitive SF-6D. The incremental per-participant costs were €136 (£116). Taking the health care perspective and assuming a willingness-to-pay of €20,000 (£17,000), the intervention’s likelihood of being cost-effective was 99% for gaining a DFY and 64% or 99% for gaining an EQ-5D or a SF-6D QALY. Conclusions: Our study supports guidelines recommending Web-based treatment for sD and adds that this not only restores health in people with sD, but additionally reduces the risk of developing a MDD. Offering the intervention has an acceptable likelihood of being more cost-effective than enhanced usual care and could therefore reach community members on a wider scale. Trial registration: German Clinical Trials Register: DRKS00004709; http://www.drks.de/DRKS00004709 (Archived by WebCite at http://www.webcitation.org/6kAZVUxy9)
Keywords: prevention; major depressive disorders; Internet; early intervention; cost effectiveness

Prosody-focused feedback enhances the efficacy of anti-depressive self-statements in depressed individuals – A randomized controlled trial - Bauer, Jonathan; Schindler-Gmelch, Lena; Gerczuk, Maurice; Schuller, Björn; Berking, Matthias (Behaviour Research and Therapy, 2025)
This study was aimed to evaluate whether the efficacy of invoking anti-depressive self-statements to cope with depressed mood can be enhanced for depressed individuals by systematically guiding them to amplify the expression of conviction in their voice. Accordingly, we recruited N = 144 participants (48 clinically depressed individuals, 48 sub-clinically depressed individuals, and 48 non-depressed individuals). Participants were randomly assigned to an experimental or control condition. Across study conditions, participants completed a mood induction procedure, then read aloud scripted anti-depressive self-statements designed to reduce depressed mood. Participants in the experimental condition received instructions to heighten the prosodic expression of conviction in their voice; participants in the control condition received no prosodic expression instructions. Results showed that depressed participants achieved a more pronounced decrease of depressed mood in the experimental condition than in the control condition. Further, the results indicated no effects in sub-clinically depressed and non-depressed individuals. Finally, heightened conviction expressed by participants in the experimental condition was associated with lower depressed mood and diminished depressive symptom severity. Overall, our findings suggest that fostering the prosodic expression of conviction in depressed persons’ voices, while they vocalize anti-depressive self-statements, represents a promising method for augmenting the efficacy of cognitive interventions for depressio
CRIS-Team Scopus Importer:2025-02-17
Keywords: Major depressive disorder; Cognitive restructuring; Prosody; Voice; Interacting cognitive subsystems; Embodiment

Prospective associations of negative mood and emotion regulation in the occurrence of binge eating in binge eating disorder - Svaldi, Jennifer; Werle, Dustin; Naumann, Eva; Eichler, Eva; Berking, Matthias (Journal of Psychiatric Research, 2019)
Retrospective and experimental data demonstrate the importance of emotion regulation (ER) in the maintenance of binge episodes in binge eating disorder (BED). The current study tested whether mood and ER prospectively influence binge episodes in individuals with BED via ecological momentary assessment (EMA). Individuals with BED (n = 79) completed two weeks of EMA. Each sampling point consisted of a series of questions pertaining to participants’ mood, ER, and eating behaviour. Successful application of adaptive ER strategies predicted subsequent abstinence, while rumination predicted subsequent binge episodes. However, neither successful application of adaptive ER, nor maladaptive ER, moderated the association between negative mood and probability of binge episodes. This naturalistic study emphasizes the importance of promoting the successful application of adaptive ER skills and cessation of rumination in treatment interventions designed to decrease the occurrence of binge episodes in BED.
CRIS-Team Scopus Importer:2019-06-04
Keywords: Acceptance; Ambulatory assessment; Binge eating disorder; Ecological momentary assessment; Emotion regulation; Rumination

Prospective Effects of Emotion-Regulation Skills on Emotional Adjustment - Berking, Matthias; Orth, Ulrich; Wupperman, Peggilee; Meier, Laurenz L.; Caspar, Franz (Journal of Counseling Psychology, 2008)
Deficits in emotion-regulation skills have widely been shown to be associated with poor emotional adjustment. However, it is still unclear whether these deficits are a cause or a consequence of poor adjustment. The purpose of the present research was to clarify the reciprocal effects between these 2 concepts. In 2 studies (Ns = 446 and 635), self-reports of emotion regulation and emotional adjustment were assessed twice with a 2-week interval. Cross-lagged regression analyses demonstrated that self-reports of emotion regulation predicted subsequent adjustment, over and above the effects of previous adjustment, whereas emotional adjustment did not predict subsequent emotion regulation. Thus, a focus on emotion-regulation skills may be important in the prevention and treatment of affect-related mental health problems. © 2008 American Psychological Association.
Created from Fastlane, Scopus look-up
Keywords: affect; emotion regulation; emotional adjustment; risk factors; skills

Psychological interventions to improve sleep in college students: A meta-analysis of randomized controlled trials - Saruhanjan, Karina; Zarski, Anna-Carlotta; Bauer, Tobias; Baumeister, Harald; Cuijpers, Pim; Spiegelhalder, Kai; Auerbach, Randy P.; Kessler, Ronald C.; Bruffaerts, Ronny; Karyotaki, Eirini; Berking, Matthias; Ebert, David Daniel (Journal of Sleep Research, 2020)
Sleep disturbances and insomnia are common in college students, and reduce their quality of life and academic performance. The aim of this meta-analysis was to evaluate the efficacy of psychological interventions aimed at improving sleep in college students. A meta-analysis was conducted with 10 randomized controlled trials with passive control conditions (N = 2,408). The overall mean effect size (Hedges’ g) of all sleep-related outcomes within each trial was moderate to large (g = 0.61; 95% confidence interval: 0.41−0.81; numbers-needed-to-treat = 3). Effect sizes for global measures of sleep disturbances were g = 0.79; 95% confidence interval: 0.52−1.06; and for sleep-onset latency g = 0.65; 95% confidence interval: 0.36−0.94. The follow-up analyses revealed an effect size of g = 0.56; 95% confidence interval: 0.45−0.66 for the combined sleep-related outcomes based on three studies. No significant covariates were identified. These results should be interpreted cautiously due to an overall substantial risk of bias, and in particular with regard to blinding of participants and personnel. Nevertheless, they provide evidence that psychological interventions for improving sleep are efficacious among college students. Further research should explore long-term effects and potential moderators of treatment efficacy in college students.
CRIS-Team Scopus Importer:2020-07-24
Keywords: insomnia; meta-analysis; sleep disturbances; students

PSYCHOLOGICAL TREATMENT of DEPRESSION in COLLEGE STUDENTS: A METAANALYSIS - Cuijpers, Pim; Cristea, Ioana A.; Ebert, David; Koot, Hans M.; Auerbach, Randy P.; Bruffaerts, Ronny; Kessler, Ronald C.; Berking, Matthias (Depression and Anxiety, 2016)
Background Expanded efforts to detect and treat depression among college students, a peak period of onset, have the potential to bear high human capital value from a societal perspective because depression increases college withdrawal rates. However, it is not clear whether evidence-based depression therapies are as effective in college students as in other adult populations. The higher levels of cognitive functioning and IQ and higher proportions of first-onset cases might lead to treatment effects being different among college students relative to the larger adult population. Methods We conducted a metaanalysis of randomized trials comparing psychological treatments of depressed college students relative to control groups and compared effect sizes in these studies to those in trials carried out in unselected populations of depressed adults. Results The 15 trials on college students satisfying study inclusion criteria included 997 participants. The pooled effect size of therapy versus control was g = 0.89 (95% CI: 0.66-1.11; NNT = 2.13) with moderate heterogeneity (I = 57; 95% CI: 23-72). None of these trials had low risk of bias. Effect sizes were significantly larger when students were not remunerated (e.g. money, credit), received individual versus group therapy, and were in trials that included a waiting list control group. No significant difference emerged in comparing effect sizes among college students versus adults either in simple mean comparisons or in multivariate metaregression analyses. Conclusions This metaanalysis of trials examining psychological treatments of depression in college students suggests that these therapies are effective and have effect sizes comparable to trials carried out among depressed adults.
Keywords: behavioral activation therapy; cognitive behavior therapy; college students; depression; metaanalysis; psychotherapy

Psychological treatment of generalized anxiety disorder: A meta-analysis - Cuijpers, Pim; Sijbrandij, Marit; Koole, Sander; Huibers, Marcus; Berking, Matthias; Andersson, Gerhard (Clinical Psychology Review, 2014)
Recent years have seen a near-doubling of the number of studies examining the effects of psychotherapies for generalized anxiety disorder (GAD) in adults. The present article integrates this new evidence with the older literature through a quantitative meta-analysis. A total of 41 studies (with 2132 patients meeting diagnostic criteria for GAD) were identified through systematic searches in bibliographical databases, and were included in the meta-analysis. Most studies examined the effects of cognitive behavior therapy (CBT). The majority of studies used waiting lists as control condition. The pooled effect of the 38 comparisons (from 28 studies) of psychotherapy versus a control group was large (g = 0.84; 95% CI: 0.71–0.97) with low to moderate heterogeneity. The effects based on self-report measures were somewhat lower than those based on clinician-rated instruments. The effects on depression were also large (g = 0.71; 95% CI: 0.59–0.82). There were some indications for publication bias. The number of studies comparing CBT with other psychotherapies (e.g., applied relaxation) or pharmacotherapy was too small to draw conclusions about comparative effectiveness or the long-term effects. There were some indications that CBT was also effective at follow-up and that CBT was more effective than applied relaxation in the longer term.
Keywords: Generalized anxiety disorder; Cognitive behavior therapy; Psychotherapy; Meta-analysis; Randomized trial; Comparative outcome studies

Psychometric Evaluation of the German Version of the Substance Use Recovery Evaluator (SURE) - Reichl, Daniela; Enewoldsen, Niklas; Berking, Matthias; Fuhrmann, Lukas; Lang, Catharina; Saur, Sebastian; Weisel, Kiona; Steins-Loeber, Sabine (Diagnostica, 2022)
Consumption patterns and abstinence are popular, albeit insufficient, indicators in the recovery process from an alcohol use disorder (AUD). To meet the requirement of suitable measurement tools for a patient-centered recovery, we developed a German version of the Substance Use Recovery Evaluator (SURE), which we then evaluated in individuals with AUD at 6 weeks (2 subsamples: n = 135 and 120) and 6 months (n = 224) after withdrawal treatment. In the first subsample, we identified the factorial structure and calculated reliability and validity indices. In the second subsample, we checked the factorial structure by a confirmative analysis. The tool was shown to be reliable and valid. The original 5-factor structure showed a good fit, although a 3-factor structure was more suitable. These results were largely confirmed in the third sample. Despite some study limitations, the German version is a psychometrically valid measurement tool to assess the recovery from an AUD.
CRIS-Team WoS Importer:2022-10-07

Reducing problematic alcohol use in employees: economic evaluation of guided and unguided web-based interventions alongside a three-arm randomized controlled trial - Buntrock, Claudia; Freund, Johanna; Smit, Filip; Riper, Heleen; Lehr, Dirk; Boss, Leif; Berking, Matthias; Ebert, David Daniel (Addiction, 2021)
Aims: To perform an economic evaluation of guided and unguided internet-based interventions to reduce problematic alcohol consumption in employees compared with a waiting-list control condition (WLC) with unrestricted access to treatment-as-usual. Design: A cost-effectiveness analysis (CEA) and cost–utility analysis (CUA) from a societal and a cost–benefit analysis from the employer's perspective with a 6-month time horizon. Setting: Open recruitment in the German working population. Participants: Employees (178 males, 256 females, mean age 47 years) consuming at least 14 (women) or 21 (men) standard units of alcohol (SUAs) per week and scoring ≥ 8 (men) or 6 (women) on the Alcohol Use Disorders Identification Test. Measurements: On-line questionnaires administered to assess SUAs and assess quality of life (AQoL-8D) and resource use. Outcome measure was responder (≤ 14/≤ 21 SUAs) for the CEA and quality-adjusted life years (QALYs) for the CUA. Net benefit regression was used to estimate cost-effectiveness for each study arm. Bootstrapping and sensitivity analyses were performed to account for uncertainty. Interventions: Five weekly modules including personalized normative feedback, motivational interviewing, goal setting, problem-solving and emotion regulation, provided with adherence-focused guidance [n = 142; responders: n = 73 (51.4%); QALYs = 0.364, standard error (SE) = 0.006] or without guidance [n = 146; n = 66 (45.2%); 0.359, 0.007]. Controls were on a waiting-list [n = 144; n = 38 (26.4%); 0.342, 0.007]. Findings: From a societal perspective, the guided intervention had a probability of 55% (54%) of being the most efficient strategy at a willingness-to-pay (WTP) of €0 per responder (QALY) gained, compared with the unguided intervention and the control condition. At a WTP of €20 000 per QALY gained, the probability was 78%. From an employer's perspective, the guided intervention had a higher probability of a positive return on investment (81%) compared with the unguided intervention (58%). Conclusion: A guided internet-based intervention to reduce problematic alcohol consumption in employees appears to be both cost-beneficial and cost-effective.
CRIS-Team Scopus Importer:2021-11-12
Keywords: Cost-effectiveness; cost–utility; economic evaluation; employees; internet-based intervention; problematic alcohol consumption; QALY

Reducing procrastination using a smartphone-based treatment program: A randomized controlled pilot study - Lukas, Christian; Berking, Matthias (Internet Interventions, 2017)

Reducing symptoms of major depressive disorder through a systematic training of general emotion regulation skills: protocol of a randomized control trial - Ehret, Anna; Kowalsky, Judith; Rief, Winfried; Hiller, Wolfgang; Berking, Matthias (BMC Psychiatry, 2014)
Major Depressive Disorder is one of the most challenging mental health problems of our time. Although effective psychotherapeutic treatments are available, many patients fail to demonstrate clinically significant improvements. Difficulties in emotion regulation have been identified as putative risk and maintaining factors for Major Depressive Disorder. Systematically enhancing adaptive emotion regulation skills should thus help reduce depressive symptom severity. However, at this point, no study has systematically evaluated effects of increasing adaptive emotion regulation skills application on symptoms of Major Depressive Disorder. In the intended study, we aim to evaluate stand-alone effects of a group-based training explicitly and exclusively targeting general emotion regulation skills on depressive symptom severity and assess whether this training augments the outcome of subsequent individual cognitive behavioral therapy for depression.

Reducing the dreaded: Change of avoidance motivation in psychotherapy - Grosse Holtforth, Martin; Grawe, Klaus; Egger, Oliver; Berking, Matthias (Psychotherapy Research, 2005)
All humans avoid aversive experiences. Avoidance motivational goals are defined as ontogenetically developed mental representations of avoided transactions, and avoidance motivation as the totality of an individual's avoidance motivational goals. Based on previous research, avoidance motivation is hypothesized to contribute to the development and maintenance of psychopathology. The authors tested the hypotheses that the intensity of avoidance motivation is reduced by outpatient psychotherapy, that the intensity of avoidance motivation after therapy approaches normality, and that change in avoidance motivation is related to other kinds of therapy outcomes. Seventy-six outpatients completed a self-report measure of avoidance motivational goals before and after therapy. All hypotheses were confirmed. Explorative analyses found differential patterns of change of avoidance motivational goals as well as relationships with psychotherapy outcomes. The authors discuss the role of avoidance motivation in psychotherapy practice and research and outline areas for future research. © 2005 Society for Psychotherapy Research.
Created from Fastlane, Scopus look-up

Reduction of incongruence in inpatient psychotherapy - Berking, Matthias; Grosse Holtforth, Martin; Jacobi, Claus (Clinical Psychology & Psychotherapy, 2003)
According to consistency theory, incongruence between individual perceptions and goals reduces well-being and increases the risk for the development and further maintenance of psychopathological disorders. Successful psychotherapy should therefore reduce the level of incongruence and therapy outcome should be associated with the reduction of incongruence. To test these hypotheses the level of incongruence was assessed in a sample of 62 inpatients undergoing cognitive-behavioural therapy (CBT) before and after treatment using the Incongruence Questionnaire. Pre-post differences were then correlated with other outcome measures and factor analysis was used to assess the underlying dimensionality of all outcome measures. The level of congruence was reduced substantially by inpatient CBT, changes were positively related to other measures of psychotherapy outcome and incongruence loaded strongly on only one of two emerging factors. Incongruence can be seen as an independent construct. It seems advisable to assess level of incongruence at the beginning of each psychotherapy for effective planning of treatment and at the end of therapy for a comprehensive outcome measurement. The reduction of high levels of incongruence must be seen as an important higher level goal in psychotherapy. Further research has to clarify under what conditions the reduction of incongruence is especially important and what methods are most effective to do so. Copyright © 2003 John Wiley & Sons, Ltd.
Created from Fastlane, Scopus look-up

Reliability and validity of assessing user satisfaction with web-based health interventions - Boss, Leif; Lehr, Dirk; Reis, Dorota; Vis, Christiaan; Riper, Heleen; Berking, Matthias; Ebert, David (Journal of Medical Internet Research, 2016)
Background: The perspective of users should be taken into account in the evaluation of Web-based health interventions. Assessing the users' satisfaction with the intervention they receive could enhance the evidence for the intervention effects. Thus, there is a need for valid and reliable measures to assess satisfaction with Web-based health interventions. Objective: The objective of this study was to analyze the reliability, factorial structure, and construct validity of the Client Satisfaction Questionnaire adapted to Internet-based interventions (CSQ-I). Methods: The psychometric quality of the CSQ-I was analyzed in user samples from 2 separate randomized controlled trials evaluating Web-based health interventions, one from a depression prevention intervention (sample 1, N=174) and the other from a stress management intervention (sample 2, N=111). At first, the underlying measurement model of the CSQ-I was analyzed to determine the internal consistency. The factorial structure of the scale and the measurement invariance across groups were tested by multigroup confirmatory factor analyses. Additionally, the construct validity of the scale was examined by comparing satisfaction scores with the primary clinical outcome. Results: Multigroup confirmatory analyses on the scale yielded a one-factorial structure with a good fit (root-mean-square error of approximation =.09, comparative fit index =.96, standardized root-mean-square residual =.05) that showed partial strong invariance across the 2 samples. The scale showed very good reliability, indicated by McDonald omegas of .95 in sample 1 and .93 in sample 2. Significant correlations with change in depressive symptoms (r=-.35, P<.001) and perceived stress (r=-.48, P<.001) demonstrated the construct validity of the scale. Conclusions: The proven internal consistency, factorial structure, and construct validity of the CSQ-I indicate a good overall psychometric quality of the measure to assess the user's general satisfaction with Web-based interventions for depression and stress management. Multigroup analyses indicate its robustness across different samples. Thus, the CSQ-I seems to be a suitable measure to consider the user's perspective in the overall evaluation of Web-based health interventions.
Keywords: Clinical effectiveness; Evaluation; Internet; Mental health; Personal satisfaction

Reliability and validity of the Japanese version of the Emotion Regulation Skills Questionnaire - Fujisato, Hiroko; Ito, Masaya; Takebayashi, Yoshitake; Hosogoshi, Hiroki; Kato, Noriko; Nakajima, Shun; Miyamae, Mitsuhiro; Oe, Yuki; Usami, Satoshi; Kanie, Ayako; Horikoshi, Masaru; Berking, Matthias (Journal of Affective Disorders, 2017)
Conclusions: The Japanese version of the ERSQ showed adequate reliability and validity.
Keywords: Emotion regulation; Assessment; Validity; Reliability; Culture; Mental disorder

Restoring depleted resources: Efficacy and mechanisms of change of an internet-based unguided recovery training for better sleep and psychological detachment from work - Ebert, David; Berking, Matthias; Thiart, Hanne; Heleen, Riper; Laferton, Johannes; Cuijpers, Pim; Sieland, Bernhard; Lehr, Dirk (Health Psychology, 2015)
Keywords: Insomnia; Internet-based self-help; Mediators; Prevention; Work stress

Sadness-Based Approach-Avoidance Modification Training for Subjective Stress in Adults: Pilot Randomized Controlled Trial - Rupp, Lydia; Keinert, Eva Marie; Böhme, Stephanie; Gmelch, Lena Marie; Eskofier, Björn; Schuller, Björn W.; Berking, Matthias (JMIR Formative Research, 2023)
Background: A key vulnerability factor in mental health problems is chronic stress. There is a need for easy-to-disseminate and effective interventions to advance the prevention of stress-related illnesses. App-based stress management trainings can fulfill this need. As subjectively experienced stress may be influenced by dysfunctional beliefs, modifying their evaluations might reduce subjective stress. Approach-avoidance modification trainings (AAMT) can be used to modify stimulus evaluations and are promising candidates for a mobile stress intervention. As the standard training reactions of the AAMT (swiping and joystick motion) have little valence, emotions could be incorporated as approach and avoidance reactions to enhance the effectiveness of AAMTs. Objective: We aimed to evaluate the feasibility of a mobile emotion-enhanced AAMT that engages users to display sadness to move stress-enhancing beliefs away and display positive emotions to move stress-reducing beliefs toward themselves (emotion-based AAMT using sadness and positive emotions [eAAMT-SP]). We explored the clinical efficacy of this novel intervention. Methods: We allocated 30 adult individuals with elevated stress randomly to 1 of 3 conditions (eAAMT-SP, a swipe control condition, and an inactive control condition). We evaluated the feasibility of the intervention (technical problems, adherence, usability, and acceptability). To explore the clinical efficacy of the intervention, we compared pretest-posttest differences in perceived stress (primary clinical outcome) and 3 secondary clinical outcomes (agreement with and perceived helpfulness of dysfunctional beliefs, emotion regulation, and depressive symptoms) among the conditions. Results: The predetermined benchmarks of 50% for intervention completion and 75% for feasibility of the study design (completion of the study design) were met, whereas the cutoff for technical feasibility of the study design (95% of trials without technical errors) was not met. Effect sizes for usability and acceptability were in favor of the eAAMT-SP condition (compared with the swipe control condition; intelligibility of the instructions: g=−0.86, distancing from dysfunctional beliefs: g=0.22, and approaching functional beliefs: g=0.55). Regarding clinical efficacy, the pretest-posttest effect sizes for changes in perceived stress were g=0.80 for the comparison between the eAAMT-SP and inactive control conditions and g=0.76 for the comparison between the eAAMT-SP and swipe control conditions. Effect sizes for the secondary clinical outcomes indicated greater pretest-posttest changes in the eAAMT-SP condition than in the inactive control condition and comparable changes in the swipe control condition. Conclusions: The findings regarding the feasibility of the intervention were satisfactory except for the technical feasibility of the intervention, which should be improved. The effect sizes for the clinical outcomes provide preliminary evidence for the therapeutic potential of the intervention. The findings suggest that extending the AAMT paradigm through the use of emotions may increase its efficacy. Future research should evaluate the eAAMT-SP in sufficiently powered randomized controlled trial
Keywords: stress (262); emotion (46); eHealth (1701); approach-avoidance (1); mental health (1497); somatic health (1); chronic stress (3); intervention (495); stress-related illness (1); app-based (6); stress management (29); belief (10); training (138); mobile phone (2614)

Self-compassion as an emotion regulation strategy in major depressive disorder - Diedrich, Alice; Grant, Michaela; Hofmann, Stefan G.; Hiller, Wolfgang; Berking, Matthias (Behaviour Research and Therapy, 2014)
Cognitive reappraisal and acceptance are two presumably adaptive emotion regulation strategies in depression. More recently, self-compassion has been discussed as another potentially effective strategy for coping with depression. In the present study, we compared the effectiveness of self-compassion with a waiting condition, reappraisal, and acceptance in a clinically depressed sample, and tested the hypothesis that the intensity of depressed mood would moderate the differential efficacy of these strategies. In an experimental design, we induced depressed mood at four points in time in 48 participants meeting criteria for major depressive disorder. After each mood induction, participants were instructed to wait, reappraise the situation, accept their negative emotions, or employ self-compassion to regulate their depressed mood. Self-ratings of depressed mood were assessed before and after each mood induction and regulation phase. Results showed that the reduction of depressed mood was significantly greater in the self-compassion condition than in the waiting condition. No significant differences were observed between the self-compassion and the reappraisal condition, and between the self-compassion and the acceptance condition in patients' mood ratings. However, the intensity of self-rated depressed mood at baseline was found to moderate the comparative effectiveness of self-compassion and reappraisal with a trend of self-compassion being more effective than reappraisal in high depressed mood at baseline. These findings support the use of self-compassion as another adaptive emotion regulation strategy for patients with major depressive disorder, especially for those suffering from high levels of depressed mood. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Depression; Self-compassion; Cognitive reappraisal; Acceptance; Emotion regulation; Mood

Self-compassion enhances the efficacy of explicit cognitive reappraisal as an emotion regulation strategy in individuals with major depressive disorder - Diedrich, Alice; Hofmann, Stefan G.; Cuijpers, Pim; Berking, Matthias (Behaviour Research and Therapy, 2016)
Cognitive reappraisal has been shown to be an effective strategy to regulate depressed mood in healthy and remitted depressed individuals. However, individuals currently suffering from a clinical depression often experience difficulties in utilizing this strategy. Therefore, the goal of this study was to examine whether the efficacy of explicit cognitive reappraisal in major depressive disorder can be enhanced through the use of self-compassion and emotion-focused acceptance as preparatory strategies. Thereby, explicit cognitive reappraisal refers to purposefully identifying, challenging, and modifying depressiogenic cognitions to reduce depressed mood. To test our hypotheses, we induced depressed mood at four points in time in 54 participants (64.8% female; age M = 35.59, SD = 11.49 years) meeting criteria for major depressive disorder. After each mood induction, participants were instructed to either wait, or employ self-compassion, acceptance, or reappraisal to regulate their depressed mood. Depressed mood was assessed before and after each mood induction and regulation period on a visual analog scale. Results indicated that participants who had utilized self-compassion as a preparatory strategy experienced a significantly greater reduction of depressed mood during reappraisal than did those who had been instructed to wait prior to reappraisal. Participants who had used acceptance as a preparatory strategy did not experience a significantly greater reduction of depressed mood during subsequent reappraisal than those in the waiting condition. These findings provide preliminary evidence that the efficacy of explicit cognitive reappraisal is moderated by the precursory use of other emotion regulation strategies. In particular, they suggest that depressed individuals might benefit from using self-compassion to facilitate the subsequent use of explicit cognitive reappraisal.
Keywords: Cognitive reappraisal; Depression; Emotion regulation; Emotion-focused acceptance; Mood; Self-compassion

Self-compassion is more effective than acceptance and reappraisal in decreasing depressed mood in currently and formerly depressed individuals - Ehret, Anna; Joormann, Jutta; Berking, Matthias (Journal of Affective Disorders, 2018)
Keywords: Self-compassion; Vulnerability; Affect regulation; Depression

Self-conscious emotions and depression: Rumination explains why shame but not guilt is maladaptive - Orth, Ulrich; Berking, Matthias; Burkhardt, Simone (Personality and social psychology bulletin, 2006)
Feelings of shame and guilt are factors associated with depression. However, studies simultaneously investigating shame and guilt suggest that only shame has a strong unique effect, although it is not yet clear which psychological processes cause shame and not shame-free guilt to be related to depression. The authors hypothesized that shame, in contrast to guilt, elicits rumination, which then leads to depression. Therefore, in this study we investigated event-related shame and guilt, eventrelated rumination, and depression among 149 mothers and fathers following family breakup due to marital separation. Data were analyzed using latent variable modeling. The results confirm that shame but not guilt has a strong unique effect on depression. Moreover, the results show that the effect of shame is substantially mediated by rumination. The results are discussed against the background of self-discrepancies and self-esteem. © 2006 by the Society for Personality and Social Psychology, Inc.
Created from Fastlane, Scopus look-up
Keywords: Depression; Guilt; Negative life events; Rumination; Shame

Self-guided internet-based and mobile-based stress management for employees: Results of a randomised controlled trial - Ebert, David; Heber, Elena; Berking, Matthias; Riper, Heleen; Cuijpers, Pim; Funk, Burkhardt; Lehr, Dirk (Occupational and Environmental Medicine, 2016)
Objective This randomised controlled trial (RCT) aimed to evaluate the efficacy of a self-guided internet-based stress management intervention (iSMI) for employees compared to a 6-month wait-list control group (WLC) with full access for both groups to treatment as usual. M e t h o d A sample of 264 employees with elevated symptoms of perceived stress (Perceived Stress Scale, PSS-10 =22) was randomly assigned to either the iSMI or to the WLC. The iSMI consisted of seven sessions and one booster session including problem-solving and emotion regulation techniques. Self-report data were assessed at baseline, at 7 weeks and at 6 months following randomisation. The primary outcome was perceived stress (PSS-10). The secondary outcomes included other relevant mental-related and work-related health outcomes. Data were analysed based on intention-to-treat principles. Results The iSMI participants showed a significantly higher reduction in perceived stress from baseline to post-treatment at 7 weeks (d=0.96, 95% CI 0.70 to 1.21) and to the 6-month follow-up (d=0.65, 95% CI 0.40 to 0.89) compared to the WLC. Significant differences with small to moderate effect sizes were also found for depression, anxiety, emotional exhaustion, sleeping problems, worrying, mental health-related quality of life, psychological detachment, emotion regulation skills and presenteeism, in favour of the experimental group. At the 6-month follow-up, all outcomes remained significantly better for the experimental group with the exception of work engagement, physical health-related quality of life and absenteeism, which were not found to significantly differ between the iSMI and WLC groups. Conclusions The iSMI investigated in this study was found to be effective in reducing typical mental-related and work-related health symptoms of stressed employees. Internet-based self-guided interventions could be an acceptable, effective and potentially costeffective approach to reduce the negative consequences associated with work-related stress.

Severely Burdened Individuals Do Not Need to Be Excluded From Internet-Based and Mobile-Based Stress Management: Effect Modifiers of Treatment Outcomes From Three Randomized Controlled Trials. - Weisel, Kiona; Lehr, Dirk; Heber, Elena; Zarski, Anna-Carlotta; Berking, Matthias; Riper, Heleen; Ebert, David (Journal of Medical Internet Research, 2018)
Although internet-based and mobile-based stress management interventions (iSMIs) may be a promising strategy to reach employees suffering from high chronic stress, it remains unknown whether participants with high symptom severity of depression or anxiety also benefit from iSMIs or should be excluded. This study aimed to evaluate the efficacy of iSMIs in subgroups with high symptom severity and to test whether baseline symptom severity moderates treatment outcome. Data from three randomized controlled trials (N=791) were pooled to identify effect modifiers and to evaluate efficacy in subgroups with different levels of initial symptom severity. The outcomes perceived stress (Perceived Stress Scale, PSS), depression severity (Center for Epidemiological Depression Scale, CES-D), and anxiety (Hospital Anxiety and Depression Scale, HADS) symptom severity were assessed at baseline, 7-week postassessment, and 6-month follow-up. Potential moderators were tested in predicting differences in the change of outcome in multiple moderation analyses. Simple slope analyses evaluated efficacy of the iSMI comparing the intervention group with the waitlist control group in subgroups with low, moderate, and severe initial symptomology based on means and SDs of the study population. In addition, subgroups with clinical values of depression (CES-D≥16) and anxiety (HADS≥8) at baseline were explored, and response rates (RRs; 50% symptom reduction) and symptom-free (SF) status (CES-D<16, HADS<8) were reported. =1.06-1.21), and effects were sustained at 6-month follow-up. Symptom severity moderated treatment outcomes, as individuals with higher symptom severity at baseline benefited significantly more from the intervention than individuals with lower symptom severity. Furthermore, 82.9% (656/791) of individuals had clinical depression values at baseline, of which significantly more individuals in the intervention group reached at least 50% symptom reduction or fell under clinical cut-off (RR: 29.2%, 93/318; SF: 39.6%, 126/318) compared with the waitlist control group (RR: 8.0%, 27/338; SF: 18.6%, 63/338) at postassessment. Significantly more individuals with clinical anxiety values at baseline (HADS≥8, 85.3%, 675/791) in the intervention group achieved at least 50% symptom reduction or fell under clinical cut-off (RR: 27.7%, 94/339; SF: 39.8%, 135/339) compared with the WLC (RR: 4.8%, 16/336; SF: 15.5%, 52/336). Highly burdened individuals benefit greatly from iSMIs and therefore should not be excluded from participation. Stress management may be a valid entry point to reach highly burdened individuals who otherwise may not seek treatment. 1) German Clinical Trials Register DRKS00005112; https://www.drks.de/DRKS00005112 (Archived by WebCite at http://www.webcitation.org/6zmIZwvdA); 2) German Clinical Trials Register DRKS00005384; https://www.drks.de/ DRKS00005384 (Archived by WebCite at http://www.webcitation.org/6zmIerdtr); and 3) German Clinical Trials Register DRKS00004749; https://www.drks.de/DRKS00004749 (Archived by WebCite at http://www.webcitation.org/6zmIjDQPx). BACKGROUND OBJECTIVE METHODS RESULTS CONCLUSIONS TRIAL REGISTRATION

Smartphone-based emotion recognition skills training for alexithymia - A randomized controlled pilot study - Lukas, Christian Aljoscha; Trevisi Fuentes, Hugo; Berking, Matthias (Internet Interventions, 2019)
Background: Neurobiological studies suggest that deficits in emotion recognition are common phenomena in alexithymia. Thus, effective treatments for alexithymia often include skills training in the domain of emotion recognition. Given that smartphone-based interventions (SBIs)offering skills training have been shown to be promising adjuncts to psychological treatments, a blended SBI facilitating the training of emotional skills might be effective in reducing alexithymia. Methods: In this pilot trial, N = 29 individuals reporting elevated alexithymia levels were randomly assigned to a blended SBI including a psychoeducation session and 14 days of training with the mindtastic alexithymia app (MT-ALEX)or a psychoeducation-only control condition. Primary outcome was emotion recognition skills as assessed in a computer-based two-choice task paradigm. Results: On average, participating in the SBI was associated with a significant increase in computer-assessed emotion recognition skills compared to the control condition (d = 0.97). Conclusions: Study findings provide preliminary evidence that SBIs can improve emotion recognition skills in alexithymic individuals. Research using larger samples and targeting clinical populations is necessary to further evaluate the potential of MT-ALEX.
CRIS-Team Scopus Importer:2019-05-16
Keywords: Alexithymia; Emotion recognition; Mobile intervention; Smartphone; Training

Specificity of Emotion Regulation Processes in Depression: A Network Analysis - Depoorter, Jente; De Raedt, Rudi; Berking, Matthias; Hoorelbeke, Kristof (Cognitive Therapy and Research, 2024)
Background: Maladaptive emotion regulation has received a lot of attention as a potential mechanism underlying major depressive disorder (MDD). However, less is known about the role of adaptive emotion regulation skills and its specificity for MDD. The Adaptive Coping with Emotions model provides a framework for this, distinguishing early (Awareness, Sensations, Clarity, Understanding) and later processes (Modification, Acceptance, Tolerance, Readiness to confront and Effective Self-Support) relevant for emotion regulation. Methods: The current study (N = 291) applied Network Analysis with Fused Graphical Lasso to jointly estimate emotion regulation networks in MDD (N = 160) and a control sample (N = 131). Within the two obtained network models, we investigated how different aspects of emotion regulation cluster together. In addition, level of centrality and unique associations between constructs were modeled. Permutation tests were applied to identify significant differences between both networks. Results: Two communities were detected, with one including variables related to preparatory processes in emotion regulation and the other including variables related to regulation processes. Additionally, ‘Identifying and Labeling’ was ranked among the most central nodes. Furthermore, our results suggest similar pathways connecting emotion regulation skills in MDD and controls. Conclusions: The results highlight the existence of different processes in emotion regulation and provide further evidence for emotion regulation as a transdiagnostic concept.
CRIS-Team Scopus Importer:2024-09-13
Keywords: Depression; Emotion regulation; Emotion regulation skills; MDD; Network analysis

Standalone smartphone apps for mental health-a systematic review and meta-analysis - Weisel, Kiona; Fuhrmann, Lukas; Berking, Matthias; Baumeister, Harald; Cuijpers, Pim; Ebert, David (npj Digital Medicine, 2019)
While smartphone usage is ubiquitous, and the app market for smartphone apps targeted at mental health is growing rapidly, the evidence of standalone apps for treating mental health symptoms is still unclear. This meta-analysis investigated the efficacy of standalone smartphone apps for mental health. A comprehensive literature search was conducted in February 2018 on randomized controlled trials investigating the effects of standalone apps for mental health in adults with heightened symptom severity, compared to a control group. A random-effects model was employed. When insufficient comparisons were available, data was presented in a narrative synthesis. Outcomes included assessments of mental health disorder symptom severity specifically targeted at by the app. In total, 5945 records were identified and 165 full-text articles were screened for inclusion by two independent researchers. Nineteen trials with 3681 participants were included in the analysis: depression (k = 6), anxiety (k = 4), substance use (k = 5), self-injurious thoughts and behaviors (k = 4), PTSD (k = 2), and sleep problems (k = 2). Effects on depression (Hedges' g = 033, 95 %CI 0.10-0.57, P = 0.005, NNT = 5.43, I-2 = 59%) and on smoking behavior (g = 0.39, 95%CI 0.21-0.57, NNT = 4.59, P <= 0.001, I-2 = 0%) were significant. No significant pooled effects were found for anxiety, suicidal ideation, self-injury, or alcohol use (g=-0.14 to 0.18). Effect sizes for single trials ranged from g = -0.05 to 0.14 for PTSD and g = 0.72 to 0.84 for insomnia. Although some trials showed potential of apps targeting mental health symptoms, using smartphone apps as standalone psychological interventions cannot be recommended based on the current level of evidence.
CRIS-Team WoS Importer:2020-01-03

STARK mit Depression: Ein multimodales Approach-Avoidance Modification Training für Jugendliche mit Depression – Ein Studienprotokoll - Hager, Malin; Keinert, Eva Marie; Berking, Matthias (4. Deutscher Psychotherapie Kongress, 2025)

Successful Application of Adaptive Emotion Regulation Skills Predicts the Subsequent Reduction of Depressive Symptom Severity but neither the Reduction of Anxiety nor the Reduction of General Distress during the Treatment of Major Depressive Disorder - Wirtz, Carolin Maria; Radkovsky, Anna; Ebert, David; Berking, Matthias (PLoS ONE, 2014)
Conclusions: Although general ER skills might be relevant for a broad range of psychopathological symptoms, they might be particularly important for the maintenance and treatment of depressive symptoms.

Successful Emotion Regulation Skills Application Predicts Subsequent Reduction of Symptom Severity During Treatment of Major Depressive Disorder - Radkovsky, Anna; Mcardle, John J.; Bockting, Claudi L. H.; Berking, Matthias (Journal of Consulting and Clinical Psychology, 2014)
Objective: Deficits in emotion regulation (ER) skills are considered a putative maintaining factor for major depressive disorder (MDD) and hence a promising target in the treatment of MDD. However, to date, the association between the successful application of arguably adaptive ER skills and changes in depressive symptom severity (DSS) has yet to be investigated over the course of treatment. Thus, the primary aim of this study was to clarify reciprocal prospective associations between successful ER skills application and DSS over the course of inpatient cognitive behavioral therapy for MDD. Additionally, we explored whether such associations would differ across specific ER skills. Method: We assessed successful ER skills application and DSS 4 times during the first 3 weeks of treatment in 152 inpatients (62.5% women, average age 45.6 years) meeting criteria for MDD. We first tested whether successful skills application and depression were cross-sectionally associated by computing Pearson's correlations. Then, we utilized latent curve modeling to test whether changes in successful skills application were negatively associated with changes in DSS during treatment. Finally, we used latent change score models to clarify whether successful skills application would predict subsequent reduction of DSS. Results: Cross-sectionally, successful ER skills application was associated with lower levels of DSS at all assessment times, and an increase of successful skills application during treatment was associated with a decrease of DSS. Moreover, successful overall ER skills application predicted subsequent changes in DSS (but not vice versa). Finally, strength of associations between successful application and DSS differed across specific ER skills. Among a broad range of potentially adaptive skills, only the abilities to tolerate negative emotions and to actively modify undesired emotions were significantly associated with subsequent improvement in DSS. Conclusions: Systematically enhancing health-relevant ER skills with specific interventions may help reduce DSS in patients suffering from MDD.
Keywords: emotion regulation; skills; depression; treatment; latent change score model

Suicidal Thoughts and Behaviors Among First-Year College Students: Results From the WMH-ICS Project - Mortier, Philippe; Auerbach, Randy P.; Alonso, Jordi; Bantjes, Jason; Benjet, Corina; Cuijpers, Pim; Ebert, David; Green, Jennifer Greif; Hasking, Penelope; Nock, Matthew K.; O'Neill, Siobhan; Pinder-Amaker, Stephanie; et al. (Journal of the American Academy of Child and Adolescent Psychiatry, 2018)
Objective: College entrance may be a strategically well-placed “point of capture” for detecting late adolescents with suicidal thoughts and behaviors (STB). However, a clear epidemiological picture of STB among incoming college students is lacking. We present the first cross-national data on prevalence as well as socio-demographic and college-related correlates for STB among first-year college students. Method: Web-based self-report surveys were obtained from 13,984 first-year students (response rate 45.5%) across 19 colleges in 8 countries (Australia, Belgium, Germany, Mexico, Northern Ireland, South Africa, Spain, and the United States). Results: Lifetime prevalence of suicidal ideation, plans, and attempts was 32.7%, 17.5%, and 4.3%, respectively. The 12-month prevalence was 17.2%, 8.8%, and 1.0%, respectively. About three-fourths of STB cases had onset before the age of 16 years (Q3 = 15.8), with persistence figures in the range of 41% to 53%. About one-half (53.4%) of lifetime ideators transitioned to a suicide plan; 22.1% of lifetime planners transitioned to an attempt. Attempts among lifetime ideators without plan were less frequent (3.1%). Significant correlates of lifetime STB were cross-nationally consistent and generally modest in effect size (median adjusted odds ratio [aOR] = 1.7). Nonheterosexual orientation (aOR range 3.3−7.9) and heterosexual orientation with some same-sex attraction (aOR range 1.9−2.3) were the strongest correlates of STB, and of transitioning from ideation to plans and/or attempts (aOR range 1.6−6.1). Conclusion: The distribution of STB in first-year students is widespread, and relatively independent of socio-demographic risk profile. Multivariate risk algorithms based on a high number of risk factors are indicated to efficiently link high-risk status with effective preventive interventions.
Created from Fastlane, Scopus look-up

Support after return to alcohol use: a mixed-methods study on how abstinence motivation and app use change after return to alcohol use in an app-based aftercare intervention for individuals with alcohol use disorder - Lang, Catharina; Weisel, Kiona; Saur, Sebastian; Fuhrmann, Lukas; Schönleber, Antonie; Reichl, Daniela; Enewoldsen, Niklas; Steins-Loeber, Sabine; Berking, Matthias (Addiction Science & Clinical Practice, 2024)
Background: As the return to alcohol use in individuals with alcohol use disorder (AUD) is common during treatment and recovery, it is important that abstinence motivation is maintained after such critical incidences. Our study aims to explore how individuals with AUD participating in an app-based intervention with telephone coaching after inpatient treatment perceived their abstinence motivation after the return to alcohol use, whether their app use behavior was affected and to identify helpful factors to maintain abstinence motivation. Methods: Using a mixed-methods approach, ten participants from the intervention group of the randomized controlled trial SmartAssistEntz who returned to alcohol use and recorded this in the app Appstinence, a smartphone application with telephone coaching designed for individuals with AUD, were interviewed about their experiences. The interviews were recorded, transcribed and coded using qualitative content analysis. App use behavior was additionally examined by using log data. Results: Of the ten interviewees, seven reported their abstinence motivation increased after the return to alcohol use. Reasons included the reminder of negative consequences of drinking, the desire to regain control of their situation as well as the perceived support provided by the app. App data showed that app use remained stable after the return to alcohol use with an average of 58.70 days of active app use (SD = 25.96, Mdn = 58.50, range = 24–96, IQR = 44.25) after the return to alcohol use which was also indicated by the participants’ reported use behavior. Conclusions: The findings of the study tentatively suggest that the app can provide support to individuals after the return to alcohol use to maintain and increase motivation after the incidence. Future research should (1) focus on specifically enhancing identification of high risk situations and reach during such critical incidences, (2) actively integrate the experience of the return to alcohol use into app-based interventions to better support individuals in achieving their personal AUD behavior change goals, and (3) investigate what type of support individuals might need who drop out of the study and intervention and discontinue app use altogether. Trial registration: The primary evaluation study is registered in the German Clinical Trials Register (DRKS, registration number DRKS00017700) and received approval of the ethical committee of the Friedrich-Alexander University Erlangen-Nuremberg (193_19 B).
CRIS-Team Scopus Importer:2024-05-10
Keywords: Abstinence motivation; Alcohol Use Disorder; App; Intervention; Mixed methods; Qualitative interviews; Relapse prevention; Telephone coaching

Teachers' emotion regulation skills facilitate implementation of health-related intentions - Eckert, Marcus; Ebert, David; Lehr, Dirk; Sieland, Bernhard; Jazaieri, Hooria; Berking, Matthias (American Journal of Health Behavior, 2015)
Objectives: Many teachers report high levels of job-related stress. Successful outcomes in stress-management trainings depend on participants actively engaging in skill-building exercises. However, despite good intentions to engage in such exercises on a regular basis, many participants ultimately fail to do so. The present study seeks to understand whether general emotion regulation (ER) skills moderate the relation between the intention to engage in skill-building exercises and actually engaging in these exercises. Methods: ER skills, the intention to engage in autonomous skill-building exercises, and the extent to which individuals actually engaged in such exercises were assessed in a sample of 119 teachers participating in stress-management training. Results: ER skills significantly moderated the association between the intention and engagement in skill-building practice. The greater the ER skills, the more coupled was the relation between the intention and actual practices. Conclusion: Findings are consistent with the hypotheses. Thus, skill-building trainings should support participants scoring low in ER skills in effectively coping with aversive affective states cued through skill-building exercises.
Keywords: Adaptively cope with stress; Emotion regulation; Engaging in health-related intention; Health-behavior; Intention-behaviorgap; Stress-management training

Telephone coaching for the prevention of depression in depression in farmers: Results from a pragmatic from a pragmatic randomized controlled trial - Thielecke, Janika; Buntrock, Claudia; Titzler, Ingrid; Braun, Lina; Freund, Johanna; Berking, Matthias; Baumeister, Harald; Ebert, David D. (Journal of Telemedicine and Telecare, 2022)
Introduction Farmers have a high risk for depression (MDD). Preventive measures targeting this often remotely living population might reduce depression burden. The study aimed to evaluate the effectiveness of personalized telephone coaching in reducing depressive symptom severity and preventing MDD in farmers compared to enhanced treatment as usual (TAU + ). Methods In a two-armed, pragmatic randomized controlled trial (N = 314) with post-treatment at 6 months, farming entrepreneurs, collaborating family members and pensioners with elevated depressive symptoms (PHQ-9 >= 5) were randomized to personalized telephone coaching or TAU + . The coaching was provided by psychologists and consists on average of 13 (+/- 7) sessions a 48 min (+/- 15) over 6 months. The primary outcome was depressive symptom severity (QIDS-SR16). Results Coaching participants showed a significantly greater reduction in depressive symptom severity compared to TAU + (d = 0.39). Whereas reliable symptom deterioration was significantly lower in the intervention group compared to TAU + , no significant group differences were found for reliable improvement and in depression onset. Further significant effects in favor of the intervention group were found for stress (d = 0.34), anxiety (d = 0.30), somatic symptoms (d = 0.39), burnout risk (d = 0.24-0.40) and quality of life (d = 0.28). Discussion Limiting, we did not apply an upper cutoff score for depressive symptom severity or controlled for previous MDD episodes, leaving open whether the coaching was recurrence/relapse prevention or early treatment. Nevertheless, personalized telephone coaching can effectively improve mental health in farmers. It could play an important role in intervening at an early stage of mental health problems and reducing disease burden related to MDD.
CRIS-Team WoS Importer:2022-07-01

The 6-month effectiveness of Internet-based guided self-help for depression in adults with Type 1 and 2 diabetes mellitus - Ebert, David; Nobis, S.; Lehr, D.; Baumeister, H.; Riper, H.; Auerbach, R. P.; Snoek, F.; Cuijpers, P.; Berking, Matthias (Diabetic Medicine, 2017)
Conclusions The trial indicates that Internet-based guided self-help treatments for depression in people with diabetes can have sustained effects on depressive symptoms, well-being and emotional distress associated with diabetes.

The affective response to health-related information and its relationship to health anxiety: An ambulatory approach - Jasper, Fabian; Hiller, Wolfgang; Berking, Matthias; Rommel, Timo; Witthofft, Michael (Cognition & Emotion, 2015)
Affective reactions to health-related information play a central role in health anxiety. Therefore, using ambulatory assessment, we analysed the time course of negative affect in a control group (CG, n = 60) which only rated their negative affect and an experimental group (EG, n = 97) which also rated the presence of somatic symptoms (e.g., back pain). By means of mixed regression models, we observed a decline of negative affect following the symptom self-ratings in the EG and a stable affect in the CG. The decline of negative affect was not moderated by the degree of health anxiety. Our findings might indicate that evaluating one's health status leads to a general reduction of negative affect in healthy individuals. The results of the study are in line with a bidirectional symptom perception model and underline the crucial role of affect regulation in the processing of health-related information.
Keywords: Negative affect; Somatic symptoms; Health behavior; Emotions; Anxiety; Self-perception

The Affect Regulation Training (ART): A Transdiagnostic Approach to the Prevention and Treatment of Mental Disorders - Berking, Matthias; Lukas, Christian (Current Opinion in Psychology, 2015)

The affect regulation Training - Berking, Matthias; Schwarz, Jeanine (Handbook of emotion regulation, 2014)

The assessment of successful emotion regulation skills use: Development and validation of an English version of the Emotion Regulation Skills Questionnaire - Grant, Michaela; Salsman, Nicholas; Berking, Matthias (PLoS ONE, 2018)

The benefit of web- and computer-based interventions for stress: A systematic review and meta-analysis - Heber, Elena; Ebert, David; Lehr, Dirk; Cuijpers, Pim; Berking, Matthias; Nobis, Stephanie; Riper, Heleen (Journal of Medical Internet Research, 2017)
Background: Stress has been identified as one of the major public health issues in this century. New technologies offer opportunities to provide effective psychological interventions on a large scale. Objective: The aim of this study is to investigate the efficacy of Web- and computer-based stress-management interventions in adults relative to a control group. Methods: A meta-analysis was performed, including 26 comparisons (n=4226). Cohen d was calculated for the primary outcome level of stress to determine the difference between the intervention and control groups at posttest. Analyses of the effect on depression, anxiety, and stress in the following subgroups were also conducted: risk of bias, theoretical basis, guidance, and length of the intervention. Available follow-up data (1-3 months, 4-6 months) were assessed for the primary outcome stress. Results: The overall mean effect size for stress at posttest was Cohen d=0.43 (95% CI 0.31-0.54). Significant, small effects were found for depression (Cohen d=0.34, 95% CI 0.21-0.48) and anxiety (Cohen d=0.32, 95% CI 0.17-0.47). Subgroup analyses revealed that guided interventions (Cohen d=0.64, 95% CI 0.50-0.79) were more effective than unguided interventions (Cohen d=0.33, 95% CI 0.20-0.46; P=.002). With regard to the length of the intervention, short interventions (≤4 weeks) showed a small effect size (Cohen d=0.33, 95% CI 0.22-0.44) and medium-long interventions (5-8 weeks) were moderately effective (Cohen d=0.59; 95% CI 0.45-0.74), whereas long interventions (≥9 weeks) produced a nonsignificant effect (Cohen d=0.21, 95% CI -0.05 to 0.47; P=.006). In terms of treatment type, interventions based on cognitive behavioral therapy (CBT) and third-wave CBT (TWC) showed small-to-moderate effect sizes (CBT: Cohen d=0.40, 95% CI 0.19-0.61; TWC: Cohen d=0.53, 95% CI 0.35-0.71), and alternative interventions produced a small effect size (Cohen d=0.24, 95% CI 0.12-0.36; P=.03). Early evidence on follow-up data indicates that Web- and computer-based stress-management interventions can sustain their effects in terms of stress reduction in a small-to-moderate range up to 6 months. Conclusions: These results provide evidence that Web- and computer-based stress-management interventions can be effective and have the potential to reduce stress-related mental health problems on a large scale.
Keywords: Internet-based interventions; Mental health; Meta-analysis; Randomized controlled trial; Review; Stress

The Effect of Digital Mindfulness Interventions on Depressive, Anxiety, and Stress Symptoms in Pregnant Women: A Systematic Review and Meta-Analysis - Mefrouche, Monique L.; Siegmann, Eva-Maria; Böhme, Stephanie; Berking, Matthias; Kornhuber, Johannes (European Journal of Investigation in Health, Psychology and Education, 2023)
Introduction. Pregnancy is a unique time in a woman’s life that can be both exciting and challenging. It is also a period that can be associated with significant stress, anxiety, and depression, which can have negative consequences for both the mother and the baby. Mindfulness interventions are known to be a well-suited treatment and prevention method for psychiatric symptoms in pregnancy, and web-based applications have been explored. We here present an up-to-date systematic review and meta-analysis of randomized–controlled trials to investigate the effect of digital-based mindfulness interventions on depressive, anxiety, and stress symptoms during pregnancy. Methods. The systematic literature search and data extraction was performed by two independent raters. It resulted in 13 eligible studies overall comprising 1373 participants. We conducted random-effects meta-analyses for depressive, anxiety, and stress symptoms after completion of a digital mindfulness intervention (compared to a control group). Results. Digital mindfulness intervention methods were significantly able to reduce depression (g = −0.47, 95% CI [−0.9; −0.09]) and anxiety symptoms (g = −0.41, 95% CI [−0.77; −0.05]), but not stress symptoms. These effects were moderated by the attrition rate (βDepression = 0.025, pDepression < 0.01; βAnxiety = 0.022, pAnxiety < 0.01; βStress = 0.022, pStress < 0.01). Primiparity also had a significant influence on the intervention effect regarding depression symptoms (β = 0.033, p = 0.024). Conclusions. Digital mindfulness interventions are a promising method to reduce mental health symptoms in pregnant women. We identified certain parameters moderating this effect, for example, primiparity and the attrition rate.
CRIS-Team Scopus Importer:2023-10-27
Keywords: anxiety; depression; digital; meta-analysis; mindfulness; pregnancy; stress

The effects of cognitive and behavioural therapies for anxiety disorders on depression: a meta-analysis - Cuijpers, P.; Cristea, I. A.; Weitz, E.; Gentili, C.; Berking, Matthias (Psychological Medicine, 2016)
Conclusions. Patients participating in trials of cognitive behavioural therapy for anxiety disorders have high levels of depression. These treatments have considerable effects on depression, and these effects are comparable to those of treatment of primary MDD.
Keywords: Cognitive behavioural therapy; generalized anxiety disorder; major depression; panic disorder; social anxiety disorder; Cognitive behavioural therapy; generalized anxiety disorder; major depression; panic disorder; social anxiety disorder

The effects of psychotherapy for adult depression on suicidality and hopelessness: A systematic review and meta-analysis - Cuijpers, Pim; De Beurs, Derek P.; Van Spijker, Bregje A.J.; Berking, Matthias; Andersson, Gerhard; Kerkhof, Ad J.F.M. (Journal of Affective Disorders, 2013)
Background: Although treatment guidelines suggest that suicidal patients with depression should be treated for depression with psychotherapy, it is not clear whether these psychological treatments actually reduce suicidal ideation or suicide risk. Methods: We conducted a systematic review and meta-analysis of studies on psychotherapy for depression in which outcomes on suicidality were reported. We also focused on outcomes on hopelessness because this is strongly associated with suicidal behavior in depression. Results: Thirteen studies (with 616 patients) were included, three of which examined the effects of psychotherapy for depression on suicidal ideation and suicide risk, and eleven on hopelessness. No studies were found with suicide attempts or completed suicides as the outcome variables. The effects on suicidal ideation and suicide risk were small (g=0.12; 95% CI: -0.20-0.44) and not statistically significant. A power calculation showed that these studies only had sufficient power to find an effect size of g=0.47. The effects on hopelessness were large (g=1.10; 95% CI: 0.72-1.48) and significant, although heterogeneity was very high. Furthermore, significant publication bias was found. After adjustment of publication bias the effect size was reduced to g=0.60. Discussion: At this point, there is insufficient evidence for the assumption that suicidality in depressed patients can be reduced with psychotherapy for depression. Although psychotherapy of depression may have small positive effects on suicidality, available data suggest that psychotherapy for depression cannot be considered to be a sufficient treatment. The effects on hopelessness are probably higher. © 2012 Elsevier B.V.
Created from Fastlane, Scopus look-up
Keywords: Depression; Meta-analysis; Psychological treatment; Psychotherapy; Suicide

The efficacy of a transdiagnostic emotion regulation skills training in the treatment of binge-eating disorder-Results from a randomized controlled trial - Berking, Matthias; Eichler, Eva; Naumann, Eva; Svaldi, Jennifer (British Journal of Clinical Psychology, 2022)
Objectives Deficits in emotion regulation (ER) have been shown to be associated with binge-eating disorder (BED). To further clarify the causal nature of this association, we tested whether systematically enhancing ER skills would reduce symptoms of BED. Methods We randomly allocated N = 101 individuals meeting the criteria for BED to a transdiagnostic ER skills training or to a waitlist control condition (WLC). Primary outcome was the reduction in binges during the treatment-vs.-waiting period as assessed with the Eating Disorder Examination (EDE) interview. Results Mixed-model ANOVAs indicated that the average pre-to-post decrease in binges assessed with the EDE was significantly greater in the ER skills training condition than in the WLC (d = 0.66). These effects were stable over the 6-month follow-up period (d = 0.72). Remission rates at post/follow-up were 34.4/45.0% in the skills training and 7.5/20.0% in the WLC. Additionally, we found a greater reduction in general eating disorder psychopathology, of food consumption in a bogus taste test and of depression in the ER skills training condition. Moreover, the greater reduction in binge-eating episodes in the training condition was (partially) mediated by a greater increase in ER skills. Conclusions The findings provide further support for the assumed importance of deficits in ER as a maintaining factor and, hence, as a target in the treatment of BED. As ER skills trainings have been shown to also reduce other kinds of psychopathology, they might be considered a promising transdiagnostic add-on component to disorder-specific interventions.
CRIS-Team WoS Importer:2022-05-27

The EmpkinS-EKSpression Reappraisal Training Augmented With Kinesthesia in Depression - Keinert, Eva Marie; Schindler-Gmelch, Lena; Rupp, Lydia; Sadeghi, Misha; Richer, Robert; Capito, Klara; Eskofier, Björn; Berking, Matthias (JMIR Formative Research, 2025)
Background: Harboring dysfunctional depressogenic cognitions contributes to the development and maintenance of depression. A central goal of cognitive behavioral therapy (CBT) for depression is to invalidate such cognitions via cognitive reappraisal (CR). However, relatively low remission rates and high dropout rates in CBT demonstrate the need for further improvement. Potentially, the effects of CBT could be enhanced by addressing not only dysfunctional depressogenic cognitions but also body states associated with depression. This may be done, for example, by systematically pairing the invalidation of depressogenic cognitions with the performance of antidepressive kinesthesia. Objective: This study aimed to examine the feasibility and clinical potential of a smartphone-based cognitive restructuring task that required users to deliberately perform antidepressive kinesthesia in conjunction with the rejection of depressogenic statements and the affirmation of antidepressive statements. This feasibility study was conducted as a precursor to a large-scale randomized controlled trial. Methods: In total, 10 healthy participants engaged in a single 90-120-minute session of smartphone-based CR training. During the training, they completed 2 phases in which they were required to reject 20 depressogenic and affirm 20 antidepressive statements, respectively. Diagnostic assessments were conducted 1 week (T1) before and directly prior (T2) to the training, and again directly posttraining (T3) and at a 2-week follow-up posttraining (T4). Feasibility outcomes assessed at T3 included intervention safety recorded by study therapists, compliance, technical feasibility, usability assessed using the Short Version of the User Experience Questionnaire (UEQ-S), and acceptability assessed using the UEQ-S and self-developed items. Preliminary clinical potential was evaluated via single-item ratings of current depressed and positive mood assessed continuously during the training. Feasibility outcomes were analyzed descriptively, and clinical potential was examined using paired-sample t tests of pre and post ratings of mood at each training phase. Results: Overall, the results indicated that the training was safe, feasible, and usable (UEQ-S pragmatic quality scale: mean 1.45, SD 0.71). However, acceptance was limited (UEQ-S hedonic quality scale: mean 1.05, SD 0.79). While 80% (8/10) of the participants were generally satisfied with the training, 80% (8/10) would recommend it to a friend, 90% (9/10) found it interesting, and 80% (8/10) rated it as “leading edge,” 40% (4/10) to 70% (7/10) did not consider it particularly helpful and 50% (5/10) found it repetitive. Preliminary results regarding clinical potential were promising, with significant increases in positive mood (rejection: Hedges g=0.63; affirmation: Hedges g=0.25), whereas changes in depressed mood were not significant. Conclusions: This study evaluated the feasibility and acceptability of a smartphone-based CR training augmented with validating and invalidating kinesthesia. This provided valuable insights for further optimizing the intervention for the subsequent randomized controlled trial, but also potential similar interventions. If future studies confirm their clinical potential, such interventions offer a promising approach to enhancing CBT for depression. Trial Registration: OSF Registries pw6ma; https://osf.io/pw6m
Keywords: depression; cognitive reappraisal; facial expression; kinesthesia; smartphone-based intervention; mobile phone

The impact of experiential avoidance on the reduction of depression in treatment for borderline personality disorder - Berking, Matthias; Neacsiu, Andrada; Comtois, Katherine Anne; Linehan, Marsha Marie (Behaviour Research and Therapy, 2009)
Background: Reducing symptoms of depression is an important target in the treatment of borderline personality disorder (BPD). Although current treatments for BPD are effective in reducing depression, the average post-treatment level of depression remains high. Aim: To test whether experiential avoidance (EA) impedes the reduction of depression during treatment for BPD. Method: EA and depression were assessed in 81 clients at baseline and 4-month intervals during 1 year of therapy. Simple correlations, hierarchical linear modeling, and latent difference score models were used to investigate the association between self-reports of EA and both self-reports and observer-based ratings of depression. Results: EA was positively associated with greater severity of depression at all points of assessment, and changes in EA were positively associated with changes in depression. Moreover, EA significantly predicted less subsequent reduction in depression whereas no such effect was found for depression on subsequent EA. Conclusion: The findings are consistent with the hypothesis that EA impedes the reduction of depression in the treatment of BPD and should thus be considered an important treatment target. © 2009 Elsevier Ltd.
Created from Fastlane, Scopus look-up
Keywords: Borderline personality disorder; Depression; Experiential avoidance; Outcome; Treatment

The influence of emotion regulation on posttraumatic stress symptoms among Japanese people - Fujisato, Hiroko; Ito, Masaya; Berking, Matthias; Horikoshi, Masaru (Journal of Affective Disorders, 2020)
Background: Emotion regulation (ER) is associated with posttraumatic stress symptoms (PTSS). However, most findings are from cross-sectional studies and are hence unable to clarify whether deficits in ER longitudinally contribute to the worsening and maintenance of PTSS. In addition, no studies consider the process of how ER affects PTSS. To further clarify causal pathways, we tested prospective associations between ER and subsequent PTSS by gender in individuals who had experienced traumatic events. Methods: We used data from an online survey of 1,794 Japanese participants aged 18–83 years who had experienced at least one traumatic event. They completed the Emotion Regulation Skills Questionnaire at baseline, as well as the PTSD Checklist for DSM-5 at baseline and four months later. Results: Multi-group structural equation modeling by gender revealed that participants’ ER predicted their PTSS four months later, even after controlling for symptoms at baseline. The findings indicate that identifying undesired emotions and then dealing with them decreases subsequent PTSS. ER had a greater effect on later PTSS in males than in females. Limitations: The use of an online survey and the exclusive use of self-report instruments might limit the generalizability of our results and the validity of the assessment. Conclusions: Deficits in ER likely contribute to worsening and maintenance of PTSS. The process of identifying and subsequently dealing with emotions may be important for the clinical suppression of PTSS.
CRIS-Team Scopus Importer:2020-09-11
Keywords: Emotion regulation; Longitudinal study; Posttraumatic stress disorder; Posttraumatic stress symptoms; Structural equation modeling

The more I got, the less I need? Efficacy of Internet-based guided self-help compared to online psychoeducation for major depressive disorder - Reins, Jo Annika; Boss, Leif; Lehr, Dirk; Berking, Matthias; Ebert, David (Journal of Affective Disorders, 2019)
Background: This study's aims were to compare the efficacy and negative effects of guided Internet-based cognitive behavior therapy (iCBT) and online psychoeducation (OPE) in people with major depression.Methods: A total of 131 individuals were randomized. Assessments took place at baseline (T1), six weeks (T2), and three months (T3). The primary endpoint was change in observer-based depression severity from T1 to T2. Potential negative effects were analyzed in terms of suicidal ideations, symptom deterioration, attitudes toward seeking further help, and other adverse events.Results: iCBT (n = 65) and OPE (n = 66) both reduced depressive symptoms from T1 to T2, with large changes observed for iCBT and medium for OPE (iCBT: Cohen's d = 1.09; OPE: d = 0.60). Differences between groups were significant at the primary endpoint (d = 0.36, p = 0.028). OPE continued to have a positive effect from post-treatment to follow-up, while the effect of iCBT remained stable, with differences between groups not being significant anymore at follow-up. Participants who had undergone prior psychotherapy benefited from both treatments; but for those without prior psychotherapy, iCBT was superior also at follow-up. In the iCBT group 26.2% of the participants reported at least one side-effect.Limitations: The history of psychotherapy was imbalanced between the groups. Some negative effects were assessed in the iCBT group only.Conclusions: Both iCBT and OPE were effective in reducing depressive symptoms, but with iCBT having a more rapid effect. iCBT was specifically superior in those with no prior history of psychotherapy. Negative effects occurred frequently and should be considered when implementing iCBT. Trial registration: German clinical trials register: DRKS00005025
Keywords: Major depressive disorder; Internet-based cognitive behavior therapy; Psychoeducation; Active control; Negative effects of psychotherapy; History of psychotherapy

The need for a behavioral science focus in research on mental health and mental disorders - Wittchen, Hans-Ulrich; Knappe, Susanne; Andersson, Gerhard; Araya, Ricardo; Banos Rivera, Rosa; Barkham, Michael; Bech, Per; Beckers, Tom; Berger, Thomas; Berking, Matthias (International Journal of Methods in Psychiatric Research, 2014)
Psychology as a science offers an enormous diversity of theories, principles, and methodological approaches to understand mental health, abnormal functions and behaviours and mental disorders. A selected overview of the scope, current topics as well as strength and gaps in Psychological Science may help to depict the advances needed to inform future research agendas specifically on mental health and mental disorders. From an integrative psychological perspective, most maladaptive health behaviours and mental disorders can be conceptualized as the result of developmental dysfunctions of psychological functions and processes as well as neurobiological and genetic processes that interact with the environment. The paper presents and discusses an integrative translational model, linking basic and experimental research with clinical research as well as population-based prospective-longitudinal studies. This model provides a conceptual framework to identify how individual vulnerabilities interact with environment over time, and promote critical behaviours that might act as proximal risk factors for ill-health and mental disorders. Within the models framework, such improved knowledge is also expected to better delineate targeted preventive and therapeutic interventions that prevent further escalation in early stages before the full disorder and further complications thereof develop. In contrast to conventional “personalized medicine” that typically targets individual (genetic) variation of patients who already have developed a disease to improve medical treatment, the proposed framework model, linked to a concerted funding programme of the “Science of Behaviour Change”, carries the promise of improved diagnosis, treatment and prevention of health-risk behaviour constellations as well as mental disorders. Copyright © 2013 John Wiley & Sons, Ltd.
Keywords: behaviour change; agenda; psychology; mental health; health behaviour; mental disorder; personalized medicine; translation

Therapieverfahren. Lesen, Hören, Lernen im Web - Berking, Matthias; Rief, Winfried (2012)

Theta/beta neurofeedback in children with ADHD: Feasibility of a short-term setting and plasticity effects. - Van Doren, Jessica; Heinrich, Hartmut; Bezold, Mareile; Reuter, Nina; Kratz, Oliver; Horndasch, Stefanie; Berking, Matthias; Ros, Thomas; Gevensleben, Holger; Moll, Gunther; Studer, Petra (International Journal of Psychophysiology, 2016)
Neurofeedback (NF) is increasingly used as a therapy for attention-deficit/hyperactivity disorder (ADHD), however behavioral improvements require 20 plus training sessions. More economic evaluation strategies are needed to test methodological optimizations and mechanisms of action. In healthy adults, neuroplastic effects have been demonstrated directly after a single session of NF training. The aim of our study was to test the feasibility of short-term theta/beta NF in children with ADHD and to learn more about the mechanisms underlying this protocol. Children with ADHD conducted two theta/beta NF sessions. In the first half of the sessions, three NF trials (puzzles as feedback animations) were run with pre- and post-reading and picture search tasks. A significant decrease of the theta/beta ratio (TBR), driven by a decrease of theta activity, was found in the NF trials of the second session demonstrating rapid and successful neuroregulation by children with ADHD. For pre-post comparisons, children were split into good vs. poor regulator groups based on the slope of their TBR over the NF trials. For the reading task, significant EEG changes were seen for the theta band from pre- to post-NF depending on individual neuroregulation ability. This neuroplastic effect was not restricted to the feedback electrode Cz, but appeared as a generalized pattern, maximal over midline and right-hemisphere electrodes. Our findings indicate that short-term NF may be a valuable and economical tool to study the neuroplastic mechanisms of targeted NF protocols in clinical disorders, such as theta/beta training in children with ADHD.

The value of treatment-goal themes for treatment planning and outcome evaluation of psychiatric inpatients - Grosse Holtforth, Martin; Reubi, Ingrid; Ruckstuhl, Lorenz; Berking, Matthias; Grawe, Klaus (International Journal of Social Psychiatry, 2004)
Background: The taxonomy of treatment-goal themes of the Bern Inventory of Treatment Goals (BIT-T) has shown to be a comprehensive coding system for outpatient use. Aim: The current study examines the value of the BIT-T for treatment planning and outcome evaluation of psychiatric inpatients. Method: The 1991 treatment goals of 675 predominantly non-psychotic psychiatric inpatients were coded using the BIT-T. Ratings of goal-related changes by patients and length of stay were used as outcome criteria. Results: The BIT-T showed to be reliable and exhaustive. Distributions of goal themes are partially associated with diagnoses. Goal-related improvements as well as length of hospital stay differed depending on the themes of patients' treatment goals. Conclusions: Coding of treatment-goal themes with the BIT-T provides researchers as well as practitioners with valuable information that goes beyond psychopathological diagnoses. This information can be used clinically for treatment planning as well as outcome evaluation. Copyright © 2004 Sage Publications (London, Thousand Oaks and New Delhi).
Created from Fastlane, Scopus look-up

Touchscreen-based assessment of food approach biases: Investigating reliability and item-specific preferences - Kahveci, Sercan; van Alebeek, Hannah; Berking, Matthias; Blechert, Jens (Appetite, 2021)
Strong cravings for unhealthy foods and implicit tendencies to approach them threaten the physical and mental health of vulnerable populations. Yet, implicit measures of food approach tendencies have methodological limitations, as existing approach-avoidance tasks (AAT) are often unreliable and require specialized hardware. We propose a novel method to measure approach biases: on a touchscreen, participants slide their hand either toward a food item (and away from control images) or away from it (and toward control images) in separate blocks. Adequate attention to the stimuli is ensured by the coupling of stimulus category to the required response. We found that this touchscreen-variant of the AAT yielded reliable bias scores when approach and avoidance were defined as movements relative to the stimulus rather than to the body. Compared to control images, we found an approach bias for low-calorie foods but not for high-calorie foods. This bias additionally varied on a food-by-food basis depending on the participant's desire to eat individual food items. Correlations with state and trait cravings were inconclusive. Future research needs to address the order effects that were found, in which participants avoiding foods in the first block showed larger biases than participants approaching food in the first block, likely due to insufficient opportunity to practice the task. Our findings highlight the need for approach bias retraining paradigms to use personalized stimulus sets. The task can enrich the methodological repertoire of research on eating disorders, obesity and cognitive bias modification.
CRIS-Team Scopus Importer:2021-05-14
Keywords: Approach-avoidance; Craving; Eating behavior; Embodied cognition; Evaluative coding; Reliability; Touchscreen

Training emotionaler Kompetenzen - Berking, Matthias (Springer, 2015)

Training emotionaler Kompetenzen - Berking, Matthias (Springer, 2017)
In diesem Buch erfahren Psychologische und Ärztliche Psychotherapeuten, Klinische Psychologen, Psychiater, Mitarbeiter in Beratungsstellen und Gesundheitscoaches, wie sie ihre Klienten darin unterstützen können, kompetent mit belastenden Gefühlen umzugehen. Diese Fähigkeit ist von zentraler Bedeutung für Wohlbefinden und psychische Gesundheit. Das Training emotionaler Kompetenzen (TEK) ist ein transdiagnostisch orientiertes Interventionsprogramm, welches immer dann eingesetzt werden kann, wenn Defizite in der Emotionsregulation als Ursache für reduziertes Wohlbefinden oder psychische Störungen angesehen werden. Das TEK ist primär als Gruppentraining konzipiert, kann aber auch im Einzelsetting eingesetzt werden. Anwendungsfelder ergeben sich (1) in der Behandlung psychischer Störungen in psychotherapeutischen Praxen, Ambulanzen und Kliniken, (2) in der Prävention psychischer Erkrankungen bei Risikogruppen, (3) für die Förderung der Persönlichkeitsentwicklung im nicht-klinischen Bereich. <br
Keywords: Affekt; Akzeptanz; Atem; Beratung; Emotion; Emotionsregulation; Entspannung; Kompetenztraining; Muskelentspannung; Neurowissenschaften; Psychische Gesundheit; Psychotherapie; Ressourcenorientierung; Selbstmanagement; Selbstwirksamkeit; Stressbewältigung; Trainingsmanual; Wahrnehmung; Manual

Training emotionaler Kompetenzen - Berking, Matthias; Hondong, Sinja (Psychotherapie im Dialog, 2018)

Training emotionaler Kompetenzen (TEK) - Berking, Matthias; Rupprecht, Raphael (Handbuch Emotionsregulation, 2020)
Die Welt ist nicht primär auf unsere Bedürfnisbefriedigung ausgerichtet. Doch selbst wenn wir unsere Bedürfnisse für eine Weile gut befriedigen können, neigen wir dazu, uns an diesen Zustand zu gewöhnen und dann mehr von der Welt zu fordern. In der Folge kommt es zwingend zu Zuständen mangelnder Bedürfnisbefriedigung bzw. mangelnder Zielerreichung. Und damit kommt es auch unvermeidlicherweise zu subjektiv unerwünschten Gefühlen. Wie wir mit diesen Gefühlen umgehen, trägt nachweislich zur Entstehung und Aufrechterhaltung psychischer Störungen bei. Vor diesem Hintergrund wurde das Training Emotionaler Kompetenzen (TEK) entwickelt. Ziel des Kapitels ist es, in die theoretischen Hintergründe, die dem Training zugrunde liegen, und die praktischen Vorgehensweisen, die im Training zum Einsatz kommen Vorgehensweisen.<br

Trainings emotionaler, sozialer und kommunikativer Fertigkeiten - Helbig-Lang, Sylvia; Klose, Michael; Berking, Matthias (Zeitschrift für Klinische Psychologie und Psychotherapie, 2020)
Schwierigkeiten in der Gestaltung interpersoneller Beziehungen sind ein häufiger Risikofaktor für die Entstehung und Aufrechterhaltung psychischer Störungen. Diese Schwierigkeiten können in der Wahrnehmung und im Ausdruck eigener oder fremder Emotionen oder in der Beurteilung der Angemessenheit sowie der Ausführung sozialen und kommunikativen Verhaltens begründet sein. Dementsprechend bilden Trainings emotionaler, sozialer und kommunikativer Fertigkeiten eine häufig angewendete Gruppe therapeutischer Programme, die auf intra- und interpersoneller Ebene ansetzen können und verschiedene Interventionen zum Aufbau von Fertigkeiten nutzen. Dazu zählen sowohl Verhaltensübungen und Rollenspiele als auch kognitive und Entspannungstechniken. Häufig stellen Fertigkeitstrainings einen Baustein in einem komplexen Behandlungsprogramm psychischer Störungen, sie können jedoch auch einzeln, vor allem im Rahmen von Prävention oder Rehabilitation eingesetzt werden.<br

Transdiagnostic Tailored Internet- and Mobile-Based Guided Treatment for Major Depressive Disorder and Comorbid Anxiety: Study Protocol of a Randomized Controlled Trial. - Weisel, Kiona; Zarski, Anna-Carlotta; Berger, Thomas; Schaub, Michael P.; Krieger, Tobias; Moser, Christian T.; Berking, Matthias; Ebert, David (Frontiers in Psychiatry, 2018)
The present study will provide evidence on the efficacy, potential cost-effectiveness, and moderators of a transdiagnostic tailored guided internet- and mobile-based treatment protocol. German Register of Clinical Studies DRKS00011690 (https://www.drks.de/drks_web/). TRIAL REGISTRATION

Treating internet use disorders via the internet? Results of a two-Armed randomized controlled trial - Bernstein, Karina; Schaub, Michael Patrick; Baumeister, Harald; Berking, Matthias; Ebert, David Daniel; Zarski, Anna-Carlotta (Journal of Behavioral Addictions, 2023)
Background and aims: Internet Use Disorders (IUDs) are emerging as a societal challenge. Evidence-based treatment options are scarce. Digital health interventions may be promising to deliver psychological treatment to individuals with IUDs directly in their online setting. The aim of this study was to evaluate the efficacy of a digital health intervention for IUDs compared to a waitlist control group (WCG). Methods: In a two-Armed randomized controlled trial, N = 130 individuals showing IUDs (Internet Addiction Test; IAT ≥49) were randomly allocated to the intervention group (IG; n = 65) or WCG (n = 65). The intervention consisted of 7 sessions based on cognitive behavioral therapy. The primary outcome was IUD symptom severity measured via the IAT at post treatment 7 weeks after randomization. Secondary outcomes included IUD symptoms (Compulsive Internet Use Scale; CIUS), quality of life, depressive and anxiety symptoms, and other psychosocial variables associated with IUDs. Results: Participants were on average 28.45 years old (SD = 10.59) and 50% identified as women, 49% as men, and 1% as non-binary. The IG (n = 65) showed significantly less IUD symptom severity (IAT) (d = 0.54, 95% CI 0.19-0.89) and symptoms (d = 0.57, 95% CI 0.22-0.92) than the WCG (n = 65) at post-Treatment. Study attrition was 20%. Effects on all other secondary outcomes were not significant. On average, participants completed 67.5% of the intervention. Discussion and Conclusions: A digital health intervention could be a promising first step to reduce IUD symptom severity.
CRIS-Team Scopus Importer:2023-11-10
Keywords: cognitive behavioral therapy for IUDs; digital health intervention; guided self-help; internet use disorders; online CBT; randomized controlled trial

Treatment of comorbid alcohol use disorders and depression with cognitive-behavioural therapy and motivational interviewing: a meta-analysis. - Riper, Heleen; Andersson, Gerhard; Hunter, Sarah B.; de Wit, Jessica; Berking, Matthias; Cuijpers, Pim (Addiction (Abingdon, England), 2014)
BACKGROUND AND AIMS To review published studies on the effectiveness of combining cognitive-behavioural therapy (CBT) and motivational interviewing (MI) to treat comorbid clinical and subclinical alcohol use disorder (AUD) and major depression (MDD) and estimate the effect of this compared with usual care. METHODS We conducted systematic literature searches in PubMed, PsycINFO and Embase up to June 2013 and identified additional studies through cross-references in included studies and systematic reviews. Twelve studies comprising 1721 patients met our inclusion criteria. The studies had sufficient statistical power to detect small effect sizes. RESULTS CBT/MI proved effective for treating subclinical and clinical AUD and MDD compared with controls, with small overall effect sizes at post-treatment [g=0.17, confidence interval (CI)=0.07-0.28, P<0.001 for decrease of alcohol consumption and g=0.27, CI: 0.13-0.41, P<0.001 for decrease of symptoms of depression, respectively]. Subgroup analyses revealed no significant differences for both AUD and MDD. However, digital interventions showed a higher effect size for depression than face-to-face interventions (g= 0.73 and g=0.23, respectively, P=0.030). CONCLUSIONS Combined cognitive-behavioural therapy and motivational interviewing for clinical or subclinical depressive and alcohol use disorders has a small but clinically significant effect in treatment outcomes compared with treatment as usual.

Turning good intentions into actions by using the health action process approach to predict adherence to internet-based depression prevention: Secondary analysis of a randomized controlled trial - Zarski, Anna-Carlotta; Berking, Matthias; Reis, Dorota; Lehr, Dirk; Buntrock, Claudia; Schwarzer, Ralf; Ebert, David (Journal of Medical Internet Research, 2018)
Keywords: Adherence; Depression prevention; Health action process approach; Internet Intervention

Usability and Naturalness of Videoconference-Based Exposure and Response Prevention for Obsessive–Compulsive Disorder at the Patients’ Homes: A Pilot Study - Netter, Anna-Lena; Hessler, Johannes Balthasar; Diedrich, Alice; Lehr, Dirk; Berking, Matthias; Pfeuffer, Simone; Voderholzer, Ulrich (Journal of Cognitive Psychotherapy: An International Quarterly, 2018)

User Experience and Effects of an Individually Tailored Transdiagnostic Internet-Based and Mobile-Supported Intervention for Anxiety Disorders: Mixed-Methods Study - Weisel, Kiona; Zarski, Anna-Carlotta; Berger, Thomas; Krieger, Tobias; Moser, Christian T.; Schaub, Michael P.; Görlich, Dennis; Berking, Matthias; Ebert, David D. (Journal of Medical Internet Research, 2020)
BACKGROUND: Internet interventions have been shown to be effective in treating anxiety disorders. Most interventions to date focus on single disorders and disregard potential comorbidities. OBJECTIVE: The aim of this mixed-methods study was to investigate feasibility, user experience, and effects of a newly developed individually tailored transdiagnostic guided internet intervention for anxiety disorders. METHODS: This study is an uncontrolled, within-group, baseline, postintervention pilot trial with an embedded qualitative and quantitative process and effect evaluation. In total, 49 adults with anxiety disorders (generalized anxiety disorder n=20, social phobia n=19, agoraphobia without panic n=12, panic with agoraphobia n=6, panic without agoraphobia n=4, subclinical depression n=41) received access to the 7-session intervention. We examined motivation and expectations, intervention use, user experience, impact, and modification requests. Qualitative data were assessed using semistructured interviews and analyzed by qualitative content analysis. Quantitative outcomes included symptom severity of anxiety and depression (Hamilton Anxiety Rating Scale [HAM-A], Quick Item Inventory of Depressive Symptomatology clinician rating [QIDS-C]), diagnostic status in clinical interviews (Mini International Neuropsychiatric Interview [MINI]), and web-based self-reports (Generalized Anxiety Disorder-7 [GAD-7], Center for Epidemiological Studies Depression Scale [CES-D], Beck Anxiety Inventory [BAI], Panic and Agoraphobia Scale [PAS], Social Phobia Scale [SPS], Patient Health Questionnaire-9 [PHQ-9]) at baseline and postassessment. Quantitative data was analyzed by comparing within-group means expressed as Cohen d. RESULTS: Anxiety symptom severity (HAM-A d=1.19) and depressive symptoms (QIDS-C d=0.42) improved significantly, and 54% (21/39) no longer were diagnosed as having any anxiety disorder. The main positive effects were the general improvement of disease burden and attentiveness to feelings and risk situations while the main negative effects experienced were lack of change in disease burden and symptom deterioration. The most prevalent reasons for participation were the advantages of online treatment, symptom burden, and openness toward online treatment. Helpful factors included support, psychoeducation and practicing strategies in daily life; the main hindering factors were too little individualization and being overwhelmed by the content and pace. CONCLUSIONS: The intervention was found to be feasible and results show preliminary data indicating potential efficacy for improving anxiety and depression. The next step should be the evaluation within a randomized controlled trial. Concerning intervention development, it was found that future interventions should emphasize individualization even more in order to further improve the fit to individual characteristics, preferences, and needs.
CRIS-Team Scopus Importer:2020-10-02
Keywords: anxiety; depression; internet intervention; tailored; transdiagnostic

Using the Consolidated Framework for Implementation Research to evaluate a nationwide depression prevention project (ImplementIT) from the perspective of health care workers and implementers: Results on the implementation of digital interventions for farmers - Freund, Johanna; Ebert, David Daniel; Thielecke, Janika; Braun, Lina; Baumeister, Harald; Berking, Matthias; Titzler, Ingrid (Frontiers in Digital Health, 2023)
Introduction: Depression has a significant impact on individuals and society, which is why preventive measures are important. Farmers represent an occupational group exposed to many risk factors for depression. The potential of guided, tailored internet-based interventions and a personalized telephone coaching is evaluated in a German project of the Social Insurance for Agriculture, Forestry and Horticulture (SVLFG). While user outcomes are promising, not much is known about actual routine care use and implementation of the two digital health interventions. This study evaluates the implementation from the perspective of social insurance employees to understand determinants influencing the uptake and implementation of digital interventions to prevent depression in farmers. Methods: The data collection and analysis are based on the Consolidated Framework for Implementation Research (CFIR). Health care workers (n = 86) and implementers (n = 7) completed online surveys and/or participated in focus groups. The surveys consisted of validated questionnaires used in implementation research, adapted items from the CFIR guide or from other CFIR studies. In addition, we used reporting data to map implementation based on selected CFIR constructs. Results: Within the five CFIR dimensions, many facilitating factors emerged in relation to intervention characteristics (e.g., relative advantage compared to existing services, evidence and quality) and the inner setting of the SVLFG (e.g., tension for change, compatibility with values and existing working processes). In addition, barriers to implementation were identified in relation to the outer setting (patient needs and resources), inner setting (e.g., available resources, access to knowledge and information) and characteristics of individuals (e.g., self-efficacy). With regard to the implementation process, facilitating factors (formal implementation leaders) as well as hindering factors (reflecting and evaluating) were identified. Discussion: The findings shed light on the implementation of two digital prevention services in an agricultural setting. While both offerings seem to be widely accepted by health care workers, the results also point to revealed barriers and contribute to recommendations for further service implementation. For instance, special attention should be given to “patient needs and resources” by raising awareness of mental health issues among the target population as well as barriers regarding the inner setting. Clinical Trial Registration: German Clinical Trial Registration: [DRKS00017078]. Registered on 18.04.2019
CRIS-Team Scopus Importer:2023-02-17
Keywords: consolidated framework for implementation research (CFIR); depression; farmers; implementation; internet-based intervention; mental health; prevention; telephone coaching

Validation of Machine Learning-Based Assessment of Major Depressive Disorder from Paralinguistic Speech Characteristics in Routine Care - Bauer, Jonathan; Gerczuk, Maurice; Schindler-Gmelch, Lena; Amiriparian, Shahin; Ebert, David Daniel; Krajewski, Jarek; Schuller, Björn W.; Berking, Matthias (Depression and Anxiety, 2024)
For reviewers For editors Table of Contents Depression and Anxiety/ 2024/ Article On this page Abstract Introduction Results Discussion Conclusions Data Availability Conflicts of Interest Acknowledgments References Copyright Related Articles Research Article | Open Access Volume 2024 | Article ID 9667377 | https://doi.org/10.1155/2024/9667377 Show citation Validation of Machine Learning-Based Assessment of Major Depressive Disorder from Paralinguistic Speech Characteristics in Routine Care Jonathan F. Bauer ,1Maurice Gerczuk ,2Lena Schindler-Gmelch ,1Shahin Amiriparian ,2David Daniel Ebert ,3Jarek Krajewski ,4Björn Schuller ,2,5and Matthias Berking 1 1Department for Clinical Psychology and Psychotherapy, Friedrich-Alexander-Universität Erlangen-Nürnberg, 91052 Erlangen, Germany 2Chair of Embedded Intelligence for Health Care & Wellbeing, University of Augsburg, 86159 Augsburg, Germany 3Department for Sport and Health Sciences, Technical University Munich, 80992 Munich, Germany 4Rhenish University of Applied Science Cologne, 50676 Cologne, Germany 5Group on Language, Audio, & Music, Imperial College London, London SW7 2AZ, UK Show less Academic Editor: Giulia Landi Received 24 Mar 2023 Revised 14 Mar 2024 Accepted 22 Mar 2024 Published 09 Apr 2024 Abstract New developments in machine learning-based analysis of speech can be hypothesized to facilitate the long-term monitoring of major depressive disorder (MDD) during and after treatment. To test this hypothesis, we collected 550 speech samples from telephone-based clinical interviews with 267 individuals in routine care. With this data, we trained and evaluated a machine learning system to identify the absence/presence of a MDD diagnosis (as assessed with the Structured Clinical Interview for DSM-IV) from paralinguistic speech characteristics. Our system classified diagnostic status of MDD with an accuracy of 66% (sensitivity: 70%, specificity: 62%). Permutation tests indicated that the machine learning system classified MDD significantly better than chance. However, deriving diagnoses from cut-off scores of common depression scales was superior to the machine learning system with an accuracy of 73% for the Hamilton Rating Scale for Depression (HRSD), 74% for the Quick Inventory of Depressive Symptomatology–Clinician version (QIDS-C), and 73% for the depression module of the Patient Health Questionnaire (PHQ-9). Moreover, training a machine learning system that incorporated both speech analysis and depression scales resulted in accuracies between 73 and 76%. Thus, while findings of the present study demonstrate that automated speech analysis shows the potential of identifying patterns of depressed speech, it does not substantially improve the validity of classifications from common depression scales. In conclusion, speech analysis may not yet be able to replace common depression scales in clinical practice, since it cannot yet provide the necessary accuracy in depression detection. This trial is registered with DRKS0002367

Validation of the Behavioral Activation for Depression Scale (BADS)-Psychometric properties of the long and short form - Fuhr, Kristina; Hautzinger, Martin; Krisch, Katharina; Berking, Matthias; Ebert, David (Comprehensive Psychiatry, 2016)
With the development of the Behavioral Activation for Depression Scale (BADS) by Kanter, et al. [1], different behavioral aspects of depression like activation, rumination or avoidance, and functional impairment can be measured. The long and the short versions of the BADS, however, show differences in the quality of psychometric properties. We wanted to validate the short and long forms of the BADS. We therefore evaluated the factor structure, the psychometric properties, and the construct validity of the long version and the subscales in a clinically depressed German sample (n = 258) in study 1. In study 2, we explored the factor structure and the psychometric properties of the short version of the BADS in a subsyndromal sample with elevated depressive symptoms (n = 406). In study 1, our results replicated the four factor solution of the BADS-25 original version and showed good psychometric properties. However, with regard to the BADS-9 only the French factor solution of the short BADS-9 demonstrated acceptable fit with low internal consistency of the subscale Avoidance. Thus, only the total score of the short form can be recommended. (C) 2016 Elsevier Inc. All rights reserved.

Veränderung klinisch relevanter Ziele und Therapieerfolg: Eine Studie an Patienten während einer stationären Verhaltenstherapie - Berking, Matthias; Grosse Holtforth, Martin; Jacobi, Claus (Psychotherapie Psychosomatik Medizinische Psychologie, 2003)
According to the consistency theory [1] clinically relevant goals, as explicated by Grosse Holtforth and Grawe [2,3], play a prominent role in the development, maintenance and therapy of psychological disorders. Thus effective psychotherapies should "normalize" the subjective importance of these goals. These changes should be positively associated with the success of psychotherapy. To test these assumptions, clinically relevant goals of 64 inpatients undergoing cognitive behavioral therapy were assessed by the Inventory of Approach and Avoidance Goals (German: Fragebogen zur Analyse motivationaler Schemata, FAMOS) [2] before and after therapy. Results show effects of normalization, as expected, especially on scales associated with psychopathology in former studies.
Created from Fastlane, Scopus look-up
Keywords: Change mechanisms; Cognitive behavioral therapy; Consistency theory; Inpatient psychotherapy; Motivational schemata

Vermeidung und Depression - Die psychometrische Evaluation der deutschen Version der „Cognitive-Behavioral Avoidance Scale” (CBAS) - Röthlin, Philipp; Holtforth, Martin Grosse; Bergomi, Claudia; Berking, Matthias; Ottenbreit, Nicole D.; Caspar, Franz (Diagnostica, 2010)
Avoidance has been established as a central feature in the conceptualization of anxiety disorders, but apparently also plays an important role in depression. The Cognitive-Behavioral Avoidance Scale (Ottenbreit & Dobson, 2004) measures depressive avoidance. The German translation was completed by a sample of 657 subjects (187 outpatients, 376 normal controls, 94 students). The factorial structure was confirmed using CFA. The psychometric properties were very satisfactory with an internal consistency of α = .92 and a retest-reliability of r = .80 (total-scale). Construct validity was demonstrated using AAQ and EMOREG. Depression and avoidance remained correlated when anxiety was controlled, supporting the specificity of depressive avoidance. © 2009 Hogrefe Verlag Göttingen.
Created from Fastlane, Scopus look-up
Keywords: Avoidance; Confirmatory factor analysis; Depression; Psychometric evaluation

Vernetzung von Psychotherapie und Alltag: Ein webbasiertes Nachsorgekonzept zur Förderung von stationären Therapieerfolgen - Ebert, David; Tarnowski, Torsten; Berking, Matthias; Sieland, Bernhard (E-Mental-Health, 2008)
Patienten in der stationären psychosomatischen Therapie und Rehabilitation haben zuvor in der Regel über Jahre klinisch relevante Beeinträchtigungen in Wechselwirkung mit ihrer alltäglichen Rollenbewältigung entwickelt. Diesem ersten destruktiven und oft chronifizierenden Lernprozess folgt in der Klinik ein zweiter: Im „Lernsetting Stationäre Psychotherapie“ können sich die Patienten für einige Wochen ohne den Druck normaler Alltagsanforderungen auf ihre Entwicklung konzentrieren. Verlassen die Patienten danach die geschützte „therapeutische Insel“, stehen Sie vor einem dritten, noch komplexeren, korrektiven Lernprozess: Es gilt nun, die gerade erst erlernten Erlebens- und Verhaltensmuster unter Alltagsbelastungen gegen die oft über Jahre stabilisierten problematischen Muster aufrechtzuerhalten, situationsspezifisch anzupassen und Transferschwierigkeiten, wie z. B. Erwartungshaltungen der Umwelt etc. zu bewältigen. Das hier vorgestellte webbasierte Nachsorgekonzept soll Patienten bei diesem Lern- und Entwicklungsprozess unterstützen.<br

Walking the Black Dog: A systematic review and meta-analysis on the effect of walking interventions on depressive symptom severity - Rupp, Lydia; Schindler-Gmelch, Lena; Rogge, Lea; Berking, Matthias (Mental Health and Physical Activity, 2024)
Background and aims: Depression is a frequent and debilitating mental illness. The plethora of common practical and psychological barriers to evidence-based care warrant more easily accessible interventions, such as behavioral activation. Walking represents an easy-to-prescribe, highly practicable, and flexible form of behavioral activation. We conducted a systematic review and meta-analysis to assess the effects of walking interventions on depressive symptom severity. Methods: Scopus, PubMed, Web of Science, MEDLINE, APA PsycArticles, and APA PsycInfo were searched to identify German- and English-language randomized-controlled trials involving adults (age ≥18 years), that compared a walking intervention with a control group and employed self-report measures of depressive symptom severity in a pre-post design. Results: Our literature search yielded k = 10,898 records, k = 27 of which were included in the systematic review (n = 1,578, 74.2% female). Study characteristics varied substantially, with overall risk of bias being moderate to high. For the k = 15 studies included in the meta-analysis, the initial effect of SMD = -.33 in favor of walking vs. control conditions lost significance after excluding outliers and studies with high risk of bias. Of all examined moderator variables (e.g., control group type, sample type, intervention delivery frequency, age, percentage of female participants), only baseline depressive symptom status meeting clinical criteria cut-offs emerged as significant. Conclusion: While the heterogeneity in intervention designs and flexible adaptability are clear strengths of walking interventions, rigorous empirical evidence for their beneficial effects on subthreshold and clinically relevant depression remains sparse, providing future research endeavors clear imperatives.
Created from Fastlane, Scopus look-up
Keywords: Behavioral activation; Depression; Physical activity; Walking

Was beeinflusst die Akzeptanz und Zufriedenheit mit einem telefonischen Einzelfallcoaching zur Prävention von Depression in der Landwirtschaft? – Qualitative Interviews mit teilnehmenden Personen aus den grünen Berufen - Thielecke, Janika; Buntrock, Claudia; Freund, Johanna; Braun, Lina; Berking, Matthias; Baumeister, Harald; Ebert, David D.; Titzler, Ingrid (Gesundheitswesen, 2022)
Bei Landwirten und anderen grünen Berufen treffen Risikofaktoren für Depressionen (u. a. saisonale Arbeit, unvorhersehbare Wetterbedingungen) auf ein geringes Hilfesuchverhalten und unzureichende Gesundheitsversorgung im ländlichen Raum. Digitale Angebote zur Prävention von Depression, welche auf die Zielgruppe ausgerichtet sind, können die mentale Gesundheit in den grünen Berufen fördern. Um jedoch ihr volles Potential in der Gesundheitsversorgung entfalten zu können, müssen Faktoren identifiziert werden, die eine langfristige und flächendeckende Implementierung unterstützen. Diese Studie zielte daher darauf ab, Aspekte zu identifizieren, welche die Akzeptanz und Zufriedenheit mit einem präventiven Telefoncoaching in den grünen Berufen beeinflussen.<br

Was wollen Patienten wann und wo erreichen? Die Veränderungen von Therapiezielen während und nach einer stationären Verhaltenstherapie - Berking, Matthias; Dreesen, J.; Jacobi, C. (Verhaltenstherapie, 2004)
Background: In order to best use patients' motivational resources psychotherapeutic health care and treatment planning should be aligned with the patients' treatment goals. To this end, it is necessary to identify what patients want to attain in which treatment phase and setting. Methods: Patients' treatment goals for inpatient and following outpatient treatment were assessed and categorized according to the Bern Inventory of Treatment Goals (BIT-T) in a sample of 242 inpatients who received cognitive-behavior therapy and planned to undergo subsequent outpatient psychotherapy. Inpatient treatment goals were assessed both at the beginning and at the end of therapy. Results: Relative frequencies of BIT-T goal categories differed only little or moderately between the three assessment conditions. At all three conditions patients had mostly - but not exclusively - symptom-oriented goals or goals that referred to clinically relevant problems. Conclusion: Institutions in charge of inpatient and outpatient psychotherapeutic health care have to take into account that patients primarily want to achieve changes regarding their symptoms and clinically relevant problems. © 2004 S. Karger GmbH.
Created from Fastlane, Scopus look-up
Keywords: Aftercare; outpatient; Motivation; Psychotherapy; Rehabilitation; psychosomatic; Treatment goals

Web-Based and Mobile Stress Management Intervention for Employees: A Randomized Controlled Trial - Heber, Elena; Lehr, Dirk; Ebert, David; Berking, Matthias; Heleen, Riper (Journal of Medical Internet Research, 2016)
Keywords: Internet; mental health; randomized controlled trial; stress; stress management; work

Web-based intervention for depressive symptoms in adults with type 1 and type 2 diabetes mellitus - Nobis, Stephanie; Ebert, David; Lehr, Dirk; Smit, Filip; Buntrock, Claudia; Baumeister, Harald; Snoek, Frank; Berking, Matthias (British Journal of Psychiatry, 2017)

Web-based intervention for depressive symptoms in adults with types 1 and 2 diabetes mellitus: A health economic evaluation - Nobis, Stephanie; Ebert, David Daniel; Lehr, Dirk; Smit, Filip; Buntrock, Claudia; Berking, Matthias; Baumeister, Harald; Snoek, Frank; Funk, Burkhardt; Riper, Heleen (British Journal of Psychiatry, 2018)
Background: Web-based interventions are effective in reducing depression. However, the evidence for the cost-effectiveness of these interventions is scarce. Aims: The aim is to assess the cost-effectiveness of a web-based intervention (GET.ON M.E.D.) for individuals with diabetes and comorbid depression compared with an active control group receiving web-based psychoeducation. Method: We conducted a cost-effectiveness analysis with treatment response as the outcome and a cost-utility analysis with qualityadjusted life-years (QALYs) alongside a randomised controlled trial with 260 participants. Results: At a willingness-to-pay ceiling of €5000 for a treatment response, the intervention has a 97% probability of being regarded as costeffective compared with the active control group. If society is willing to pay €14 000 for an additional QALY, the intervention has a 51% probability of being cost-effective. Conclusions: This web-based intervention for individuals with diabetes and comorbid depression demonstrated a high probability of being cost-effective compared with an active control group.
Created from Fastlane, Scopus look-up

Web-based rehabilitation aftercare following inpatient psychosomatic treatment Web-basierte Rehabilitationsnachsorge nach stationärer psychosomatischer Therapie (W-RENA) - Ebert, David Daniel; Hannig, Wiebke; Tarnowski, Torsten; Sieland, Bernhard; Götzky, Benjamin; Berking, Matthias (Rehabilitation, 2013)
Background: High relapse rates following treatment for mental health disorders are a challenge for psychosomatic rehabilitation treatments. The goal of the present study is to evaluate the feasibility, acceptance and process-quality of a 12-week transdiagnostic Internet-based maintenance treatment (W-RENA) following psychosomatic rehabilitation treatment. Findings regarding effectiveness and moderators of treatment outcome that were already reported elsewhere are briefly summarized. Method: In a preliminary study we first assessed whether rehab patients have the technical requirements and abilities to successfully participate in Internet-based treatments. Patients expressing interest for participation in W-RENA (N=400) were compared with non-participants (N=1 789) with regard to sociodemographic and clinical characteristics. In a 2-arm randomized controlled trial (N=400) we subsequently compared participants of W-RENA with participants of a treatment as usual group (TAU). Self-report measures were assessed at the beginning of inpatient treatment (t1), at discharge from inpatient treatment/start of W-RENA (t2), and at 3- (t3) and 12-months follow-ups (t4). Results: The majority of assessed rehab-patients had the technical prerequisites (78.79%) and necessary skills (79.9%) to successfully participate in an Internet-based intervention. A third of the patients (32%) which were invited to take part in the intervention (and the study) expressed interest to participate. Study participants and non-participants differed only slightly. Most participants (80.6%) reported to have gained benefit from participating. Treatment achievements as well as quality of therapist alliance were rated high from both patients and therapists. Moreover, participants of the W-RENA group could stabilize their inpatient treatment outcomes up to 3- and 12-months follow-up better than controls could do (differences in symptom change from discharge to 3-months follow-up: d=0.38; to 12-months follow-up: d=0.55). Clinical significant symptom deterioration from discharge to 1-year follow-up could be reduced by 2/3 (29.45% vs. 11.45%). We could not identify any subgroup not profiting from study participation. Patients with low education benefited particularly. Conclusion: Internet-based aftercare interventions are a feasible, accepted and effective approach to successfully sustain treatment outcomes achieved in inpatient psychosomatic rehabilitation. © Georg Thieme Verlag KG Stuttgart. New York.
Created from Fastlane, Scopus look-up
Keywords: aftercare; internet therapy; internet-based guided self-help; relapse prevention; social network

Wenn Geschlechtsverkehr nicht möglich ist: Vorstellung eines internetbasierten Behandlungsprogramms für Genito-Pelvine Schmerz-Penetrationsstörung mit Falldarstellung - Zarski, Anna-Carlotta; Berking, Matthias; Hannig, Wiebke; Ebert, David (Verhaltenstherapie, 2018)
Keywords: Cognitive-behavioral therapy; Sexual dysfunction; Genito-pelvic pain/penetration disorder

Wie effektiv sind systematische Rückmeldungen des Therapieverlaufs an den Therapeuten? Eine empirische Studie in einem stationär- verhaltenstherapeutischen Setting - Berking, Matthias; Orth, Ulrich; Lutz, Wolfgang (Zeitschrift für Klinische Psychologie und Psychotherapie, 2006)
Background: Systematic feedback to therapists on their patients' progress has been shown to enhance outcome in at-risk patients in studies with predominantly moderately disturbed outpatients. Objective: Is it possible to replicate these findings in a CBT-oriented inpatient setting and are positive effects confined to at-risk patients? Methods: In a randomized controlled trial (N = 118) half of the therapists were provided with systematic feedback on their patients' progress. Results: Patients in the feedback group improved more man patients in the control group on all outcome measures. Conclusions: Systematic feedback to therapists on their patients' progress enhances outcome in inpatient CBT treatment. Future research should identify ways to reduce the monetary and psychological costs of feedback-providing systems, in order to facilitate their application in routine care settings. © Hogrefe Verlag 2006.
Created from Fastlane, Scopus look-up
Keywords: Feedback; Patient-focused research; Psychotherapy; Treatment outcome

Zero-shot personalization of speech foundation models for depressed mood monitoring - Gerczuk, Maurice; Triantafyllopoulos, Andreas; Amiriparian, Shahin; Kathan, Alexander; Bauer, Jonathan; Berking, Matthias; Schuller, Björn W. (Patterns, 2023)
The monitoring of depressed mood plays an important role as a diagnostic tool in psychotherapy. An automated analysis of speech can provide a non-invasive measurement of a patient's affective state. While speech has been shown to be a useful biomarker for depression, existing approaches mostly build population-level models that aim to predict each individual's diagnosis as a (mostly) static property. Because of inter-individual differences in symptomatology and mood regulation behaviors, these approaches are ill-suited to detect smaller temporal variations in depressed mood. We address this issue by introducing a zero-shot personalization of large speech foundation models. Compared with other personalization strategies, our work does not require labeled speech samples for enrollment. Instead, the approach makes use of adapters conditioned on subject-specific metadata. On a longitudinal dataset, we show that the method improves performance compared with a set of suitable baselines. Finally, applying our personalization strategy improves individual-level fairness.
CRIS-Team Scopus Importer:2023-11-24
Keywords: deep learning; depression monitoring; DSML 2: Proof-of-concept: Data science output has been formulated; implemented; and tested for one domain/problem; foundation models; hypernetworks; personalization; speech processing